Adhesive tape, joint body, and method for disassembling joint body

JP2025065358A5Active Publication Date: 2025-04-30DIC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2025018766
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-30
Estimated Expiration
2040-12-15

AI Technical Summary

Technical Problem

The challenge is to develop an adhesive tape that facilitates easy peeling while maintaining resistance to peeling in the thickness direction, particularly in applications where adhesive tapes are used for labeling and need to be removed from complex surfaces with varying gaps and distortions.

Method used

The adhesive tape comprises a specific layered structure including a first adhesive layer, a first substrate layer with a breaking strength of 1.0 to 100.0 MPa and breaking elongation of 400 to 1500%, a foam layer with 25% compressive strength of 40 to 160 kPa and tensile strength of 3.0 to 15.0 MPa, and a third adhesive layer. This structure allows for easy peeling by extending the substrate layer and maintaining adhesion through the foam's elasticity.

Benefits of technology

The adhesive tape achieves both ease of peeling and resistance to peeling in the thickness direction, facilitating the disassembly of products by allowing easy separation of adherends while maintaining sufficient adhesion, even under conditions of slight distortion or size variation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an adhesive tape that can be peeled easily and has peeling resistance in the thickness direction.SOLUTION: The inventive adhesive tape has a first adhesive layer, a first substrate layer and a foamed layer, and a third adhesive layer in this order. The first substrate layer has a strength at break of 1.0-100.0 MPa and an elongation at break of 400-1500%. The foam of the foamed layer has a 25% compression strength of 40-160 kPa and the foam has a tensile strength of 3.0-15.0 MPa.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive tape, a joint, and a method for dismantling a joint. [Background technology]

[0002] Because pressure-sensitive adhesive tapes have excellent workability and high adhesive reliability, they are widely used as a joining means in various industrial fields, such as office automation equipment, IT / home appliances, and automobiles, for purposes such as fixing parts in place, temporarily fixing parts in place, and as labels displaying product information (e.g., Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-89726 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, in recent years, from the viewpoint of environmental protection, there has been an increasing demand in various industrial fields such as home appliances and automobiles for recycling and reusing used products or defective products that occurred during the manufacturing process. When recycling or reusing various products, the product is disassembled and each part in the product is removed, and when removing each part, it is necessary to peel off the adhesive tape used to fix the parts or to label them. However, in recent years, adhesive tape has been provided in various places in the product, and the peeling work of the adhesive tape that bonds each part (adherend) has become complicated, so there is a demand for reducing the work cost. In addition to facilitating the peeling operation, adhesive tapes are also required to have resistance to peeling in the thickness direction of the tape. Specifically, the attachment surfaces of the components in a product (e.g., a housing and a component to be fixed to the housing) that are attached with the adhesive tape may have gaps of various sizes within the attachment surface due to slight distortion of the components. Even if such gaps exist in the adhesive tape, or even if the distortion of the components or the size of the gaps varies, the adhesive tape is required to continue adhering to each component due to the elasticity of the adhesive tape itself (resistance to peeling in the thickness direction of the tape).

[0005] Therefore, the present disclosure is an invention made in consideration of the above problems, and has an object to provide an adhesive tape that combines ease of peeling operation with resistance to peeling in the thickness direction, a bonded body in which the adhesive tape is easily peeled off and which is capable of sufficiently maintaining adhesion between adherends, and a method for dismantling the bonded body for easily dismantling the bonded body. [Means for solving the problem]

[0006] [1] The present disclosure provides a pressure-sensitive adhesive sheet comprising, in order, a first adhesive layer, a first base layer, a foam layer, and a third adhesive layer; The first base layer has a breaking strength of 1.0 to 100.0 MPa and a breaking elongation of 400 to 1500%, In the pressure-sensitive adhesive tape, the foam of the foam layer has a 25% compressive strength of 40 to 160 kPa and a tensile strength of 3.0 to 15.0 MPa. [2] In this embodiment, it is preferable to provide a second adhesive layer between the first base layer and the foam layer. [3] In this embodiment, the first adhesive layer adjacent to the first base layer is formed from an adhesive composition containing filler particles having an average particle size of 10 to 40 μm and an adhesive resin, The content of the filler particles in the adhesive layer containing the filler particles is preferably 3 to 50 parts by mass with respect to 100 parts by mass of the adhesive resin. [4] In the present embodiment, the second adhesive layer adjacent to the first base layer is formed from an adhesive composition containing filler particles having an average particle size of 10 to 40 μm and an adhesive resin, The content of the filler particles in the adhesive layer containing the filler particles is preferably 3 to 50 parts by mass with respect to 100 parts by mass of the adhesive resin. [5] In this embodiment, it is preferable that a fourth adhesive layer is provided between the second adhesive layer and the foam layer. [6] In this embodiment, it is preferable to provide a second base layer between the second adhesive layer and the fourth adhesive layer. [7] This embodiment is a bonded body comprising an adhesive tape according to any one of [1] to [6] above, a first adherend adhered onto a surface of the first adhesive layer of the adhesive tape, and a second adherend adhered onto a surface of the third adhesive layer of the adhesive tape. [8] This embodiment is a method for dismantling a joined body according to the above item [7], comprising the steps of: The method for dismantling a bonded body includes a step of stretching at least the first base material layer of the pressure-sensitive adhesive tape to separate the second adherend from the first adherend. [9] This embodiment is a bonded body comprising the adhesive tape described in [6] above, a first adherend adhered onto the surface of the first adhesive layer of the adhesive tape, and a second adherend adhered onto the surface of the third adhesive layer of the adhesive tape.

[10] This embodiment is a method for dismantling a joined body according to the above [9], The method for dismantling a bonded body includes a step of separating the second adherend from the first adherend by stretching at least the first base material layer of the adhesive tape while leaving the second base material layer of the adhesive tape on the surface of the second adherend. Effect of the Invention

[0007] According to the present disclosure, it is possible to provide an adhesive tape that combines ease of peeling with resistance to peeling in the thickness direction, a bonded body in which the adhesive tape is easily peeled off and which is capable of sufficiently maintaining adhesion between adherends, and a method for dismantling the bonded body for easily dismantling the bonded body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail, but the present invention is not limited to the present embodiment.

[0009] [Adhesive tape] The pressure-sensitive adhesive tape of the present embodiment comprises a first adhesive layer, a first base layer, a foam layer and a third adhesive layer in this order, the first base layer having a breaking strength of 1.0 to 100.0 MPa, a breaking elongation of 400 to 1500%, a 25% compressive strength of the foam of the foam layer being 40 to 160 kPa, and a tensile strength of the foam being 3. to 15.0 MPa. The pressure-sensitive adhesive tape of the present embodiment preferably comprises a second adhesive layer between the first base layer and the foam layer. The pressure-sensitive adhesive tape of the present embodiment preferably comprises a fourth adhesive layer between the second adhesive layer and the foam layer. The pressure-sensitive adhesive tape of the present embodiment more preferably comprises a second base layer between the second adhesive layer and the fourth adhesive layer. According to the pressure-sensitive adhesive tape of this embodiment, it is possible to achieve both facilitation of the peeling operation and peel resistance in the thickness direction. Specifically, in the pressure-sensitive adhesive tape according to this embodiment, the breaking strength of the first base material layer is 1.0 to 100.0 MPa, and the breaking elongation of the first base material layer is 400 to 1500%, so that when the pressure-sensitive adhesive tape is peeled off between parts in a product to be reworked or recycled (hereinafter, the object to which the pressure-sensitive adhesive tape is adhered is also referred to as the first adherend and the second adherend), the first base material layer is sufficiently elongated, and the first base material layer can be peeled off (pulled out) from between the first adherend and the second adherend together with at least the first adhesive layer (preferably the first adhesive layer and the second adhesive layer, which is an optional component) without being torn off. As a result, the first adherend and the second adherend can be easily separated and dismantled, and the pressure-sensitive adhesive tape can be easily peeled off. In addition, since the 25% compressive strength of the foam in the foam layer is 40 to 160 kPa and the tensile strength of the foam is 3.0 to 15.0 MPa, the adhesive tape is endowed with appropriate elasticity, and even if the parts (adherends) are slightly distorted, the parts (first adherend, second adherend) can continue to be adhered together (has resistance to peeling in the thickness direction of the tape). Hereinafter, a first embodiment, a second embodiment, a third embodiment and a fourth embodiment of the pressure-sensitive adhesive tape of the present embodiment will be described.

[0010] Adhesive Tape of First Embodiment The adhesive tape of the first embodiment according to this embodiment comprises, in order, a first adhesive layer, a first base layer, a foam layer and a third adhesive layer, and the first base layer has a breaking strength of 1.0 to 100.0 MPa and a breaking elongation of 400 to 1500%, the foam of the foam layer has a 25% compressive strength of 40 to 160 kPa and a tensile strength of 3.0 to 15.0 MPa.

[0011] <First base layer> In a first embodiment, the pressure-sensitive adhesive tape includes a first base layer between a first adhesive layer forming one adhesive surface of the pressure-sensitive adhesive tape and a third adhesive layer forming the other adhesive surface of the pressure-sensitive adhesive tape, the first base layer having a breaking strength of 1.0 to 100.0 MPa and a breaking elongation of 400 to 1500%.

[0012] In the first embodiment, the first base layer is not particularly limited as long as it has the above-mentioned properties, and can be appropriately selected from among known materials that can be used in pressure-sensitive adhesive tapes. It is preferable that the first base layer contains the following first base material, and may further contain other components as necessary. The first substrate layer may have a single-layer structure, or a multi-layer structure of two, three or more layers.

[0013] In the first embodiment, the first base layer has a breaking strength of 1.0 to 100.0 MPa, preferably 5 to 95 MPa, more preferably 15 to 92 MPa, and even more preferably 25.0 to 90.0 MPa. When the breaking strength is 1.0 MPa or more, when the adhesive tape is peeled off to separate and dismantle the first adherend and the second adherend, the first base layer is sufficiently elongated even when pulled, and at least the first base layer can be peeled off (pulled out) from between the first adherend and the second adherend without tearing. This allows the first adherend and the second adherend to be easily separated and dismantled. In addition, when the breaking strength is 100.0 MPa or less, it is possible to prevent the stress applied to the worker when pulling the adhesive tape from becoming too large. The breaking strength of the first base material layer refers to the stress value measured when the first base material layer is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement atmosphere conditions of 23°C and 50% RH, until it breaks. The breaking strength can be adjusted by appropriately selecting the material and by applying stretching during the manufacturing process of the first base layer.

[0014] In the first embodiment, the first base layer has a breaking elongation of 400 to 1500%, preferably 400 to 1400%, more preferably 500 to 1300%, and even more preferably 600 to 1200%. By having a breaking elongation (also referred to as breaking elongation) of 400% or more, even if the adhesive tape is firmly attached to the adherend, the stress when peeling off the adhesive tape is not too large. In addition, by having a breaking elongation of 1500% or less, the stretching distance when peeling off the adhesive tape is not too long, making it possible to work in a small space. The breaking elongation of the first base material layer refers to the tensile elongation percentage measured when the first base material layer was punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement atmosphere conditions of 23°C and 50% RH, until breaking. The breaking elongation can be adjusted by appropriately selecting the material and by applying stretching during the manufacturing process of the first base layer.

[0015] In the first embodiment, the first base layer preferably has a 100% modulus of 1 to 5 MPa, more preferably 1 to 4.5 MPa, and even more preferably 1 to 4 MPa. When the 100% modulus is 1 MPa or more, defects associated with deformation such as slippage when a load is applied to the pressure-sensitive adhesive tape or adherend can be suppressed. Furthermore, when the 100% modulus is 5 MPa or less, an operator can pull the pressure-sensitive adhesive tape from the adherend with a relatively light force in the initial stage of peeling it off. The 100% modulus of the first base material layer refers to the stress value measured when the first base material layer is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement atmosphere conditions of 23°C and 50% RH, and the elongation is 100%. The 100% modulus can be adjusted by appropriately selecting the material and by applying stretching during the manufacturing process of the first base layer.

[0016] In the first embodiment, the first base layer preferably has a rubber hardness of 20 to 90 A, more preferably 30 to 85 A, and further preferably 60 to 85 A. A rubber hardness of 20 A or more can prevent the adhesive tape from tearing when the adhesive tape is stretched and peeled off. In addition, a rubber hardness of 90 A or less makes the first base layer soft, and for example, when an adherend to which the adhesive tape is attached is dropped, the adhesive tape is more likely to absorb the impact, and the adherend can be protected from the impact (the impact resistance of the adhesive tape can be improved). The rubber hardness of the first base layer is Shore A hardness, and refers to a value measured in accordance with JIS K 6253 using a durometer (spring type rubber hardness tester) (model: GS-719G, manufactured by Teclock Corporation). In addition, the rubber hardness can be adjusted by appropriately selecting the material, for example, by changing the molecular weight of the resin, or by changing the monomer unit if a styrene monomer unit is contained.

[0017] The first base layer has a thickness of 10 to 1000 μm, preferably 10 to 300 μm, and more preferably 20 to 200 μm. A thickness of 10 μm or more ensures the strength of the adhesive tape, while a thickness of 1000 μm or less prevents the adhesive tape from being too thick and becoming difficult to pull. In this specification, the "thickness of the first base layer" refers to the average value of the thicknesses measured at any five points in the first base layer using a TH-104 paper / film thickness meter (manufactured by Tester Sangyo Co., Ltd.).

[0018] The ratio of the thickness of the first adhesive layer to the first base layer is not particularly limited and can be appropriately selected according to the purpose, but the ratio of the thickness of the adhesive layer to the thickness of the first base layer, expressed as [thickness of the first adhesive layer / thickness of the first base layer], is preferably 1 / 5 to 5 / 1, more preferably 1 / 3 to 3 / 1, and even more preferably 1 / 2 to 2 / 1. When the ratio of the thickness of the first adhesive layer to the thickness of the first base layer is within a preferred range, the adhesive tape can have excellent adhesion and removability (ease of peeling). On the other hand, when the ratio is greater than 5 / 1, there is a possibility that only the first adhesive layer will remain on the adherend during the re-peeling process of the adhesive tape. In addition, when the ratio is less than 1 / 5, there is a concern that the first adhesive layer will not be able to follow the surface of the adherend when it has an uneven shape, etc., and the adhesive strength will decrease.

[0019] <<Material for first base material>> The stress of the first base layer at 25% elongation is preferably 0.15 MPa to 82 MPa, more preferably 0.15 MPa to 10 MPa, even more preferably 0.15 MPa to 5 MPa, and most preferably 0.15 MPa to 4.5 MPa. When the stress of the first base layer at 25% elongation is 0.15 MPa to 82 MPa, the first base layer can have a suitable adhesive strength, and can be relatively easily peeled off even when peeled off by elongation. On the other hand, when the stress of the first base layer at 25% elongation is less than 0.15 MPa, it is difficult to obtain a non-adhesive force at the interface between the first adhesive layer and the first base layer, and for example, the holding power of the adhesive tape may be impaired. In addition, when the stress of the adhesive tape at 25% elongation exceeds 82 MPa, the force required to elongate the adhesive tape when peeling off the adhesive tape tends to be excessive. The stress of the first base layer at 25% elongation refers to the stress value measured when the adhesive tape is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the lengthwise direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement atmosphere conditions of 23°C and 50% RH, until it is elongated by 25%. The material for the first substrate is not particularly limited as long as it can obtain a first substrate layer having the above-mentioned specific physical properties, but examples thereof include styrene-based resins, which are copolymers containing a block mainly made of styrene-based compound units and a block mainly made of conjugated diene units, and / or hydrogenated products thereof; polyurethane resins such as ester-based polyurethane and ether-based polyurethane; polyolefin resins such as polyethylene and polypropylene; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polystyrene; polycarbonate; polymethylpentene; polysulfone; polyether ether ketone; polyether sulfone; polyether imide; polyimide film; fluorine resin; nylon; acrylic resin, etc. These may be used alone or in combination of two or more types, but it is preferable to use two or more types in combination. Among these, styrene-based resins and polyurethane resins are preferred because suitable breaking strength and breaking elongation can be easily obtained, and styrene-based resins are more preferred. A combination of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer, or a hydrogenated styrene-isoprene butadiene-styrene copolymer is particularly preferred.

[0020] -Styrene-based resin- Since the styrene resin is a resin that exhibits thermoplasticity, it has excellent moldability in extrusion molding, injection molding, etc., and is easy to mold into the first substrate layer. Furthermore, the styrene resin is particularly likely to have excellent breaking elongation among the group of resins generally called thermoplastic resins, and is therefore suitable for use as the first substrate of the pressure-sensitive adhesive sheet.

[0021] Therefore, in the first base material, the proportion of the styrene resin relative to the total resin components is preferably 50% to 100%, more preferably 60% to 100%, even more preferably 65% ​​to 100%, and particularly preferably 70% to 100%. By keeping the proportion of the styrene resin within the above preferred range, a first base layer excellent in breaking elongation and breaking strength can be obtained.

[0022] Here, the styrene resin is a copolymer containing a block mainly made of a styrene compound unit (hereinafter also referred to as polymer block (A)) and a block mainly made of a conjugated diene unit (hereinafter also referred to as polymer block (B)) and / or a hydrogenated product thereof. Examples of the styrene compound include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 1,3-dimethylstyrene, diphenylethylene, 1-vinylnaphthalene, 4-propylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, and 4-(phenylbutyl)styrene. These may be used alone or in combination of two or more. Among them, from the viewpoint of the balance between production cost and physical properties, styrene, α-methylstyrene, and a mixture thereof are preferred, and styrene is more preferred. In addition, the conjugated diene is not limited to the following, but examples thereof include 1,3-butadiene, 2-methyl-1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, and 1,3-hexadiene. Among these, 1,3-butadiene and 2-methyl-1,3-butadiene (isoprene) are preferred from the viewpoint of versatility. These may be used alone or in combination of two or more.

[0023] Specific examples of styrene-based resins include styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, styrene-isoprenebutadiene-styrene copolymers, styrene-butadiene-styrene copolymers, styrene-ethylene-butylene copolymers, styrene-ethylene-butylene-styrene copolymers, styrene-ethylene-propylene copolymers, styrene-ethylene-propylene-styrene copolymers, and hydrogenated products thereof.

[0024] The polymer block (A) is mainly composed of styrene-based compound units. Here, "mainly composed" means that the styrene-based compound units are contained in an amount of 50% by mass or more based on the total mass of the polymer block (A). The content of the styrene-based compound units in the polymer block (A) is more preferably 70% by mass or more, further preferably 90% by mass or more, particularly preferably 95% by mass or more, based on the total mass of the polymer block (A), and may be substantially 100% by mass. However, as long as it does not interfere with the object and effect of the present invention, the polymer block (A) may contain a structural unit derived from an unsaturated monomer other than a styrene-based compound (hereinafter, abbreviated as other unsaturated monomer unit) at a ratio of 10 mass% or less. Examples of the other unsaturated monomer include at least one selected from the group consisting of butadiene, isoprene, 2,3-dimethylbutadiene, 1,3-pentadiene, 1,3-hexadiene, isobutylene, methyl methacrylate, methyl vinyl ether, N-vinylcarbazole, β-pinene, 8,9-p-menthene, dipentene, methylenenorbornene, 2-methylenetetrahydrofuran, etc. When the polymer block (A) contains the other unsaturated monomer unit, the bonding form is not particularly limited and may be either random or tapered.

[0025] The styrene resin may have at least one polymer block (A). When the styrene resin has two or more polymer blocks (A), the polymer blocks (A) may be the same or different. In this specification, "polymer blocks are different" means that at least one of the monomer units constituting the polymer blocks, the weight average molecular weight, the molecular weight distribution, the stereoregularity, and, when a plurality of monomer units are present, the ratio of each monomer unit and the form of copolymerization (random, gradient, block) is different.

[0026] The polymer block (B) is mainly composed of conjugated diene units. Here, "mainly composed" means that the structural unit is contained in an amount of 50 mass% or more based on the total mass of the polymer block (B). The content of the structural unit derived from the conjugated diene in the polymer block (B) is more preferably 70 mass% or more, further preferably 90 mass% or more, particularly preferably 95 mass% or more, based on the total mass of the polymer block (B), and may be substantially 100 mass%.

[0027] The styrene resin is not limited in the bonding form as long as the polymer block (A) and the polymer block (B) are bonded, and may be linear, branched, multi-branched, radial, or a combination of two or more of these. A styrene resin rich in linear structures can provide the first base layer with excellent breaking elongation. On the other hand, a branched or multi-branched structure in which a styrene block is arranged at the molecular end can have a pseudo-crosslinked structure and can provide excellent cohesive strength. For this reason, it is preferable to use a mixture of styrene resins according to the required mechanical properties. Among them, the bonding form between the polymer block (A) and the polymer block (B) is preferably linear, and examples thereof include a diblock copolymer represented by AB, a triblock copolymer represented by ABA, a tetrablock copolymer represented by ABAB, a pentablock copolymer represented by ABABA, and an (AB)nX type copolymer (X represents a coupling agent residue, and n represents an integer of 3 or more), where A represents the polymer block (A) and B represents the polymer block (B). Among them, linear triblock copolymers or diblock copolymers are preferred, and an ABA type triblock copolymer is preferably used. Here, in this specification, when the same type of polymer blocks are linearly bonded via a bifunctional coupling agent or the like, the entirety of the bonded polymer blocks is treated as one polymer block. Accordingly, including the above examples, polymer blocks that should be strictly represented as YXY (X represents a coupling residue) are represented as Y as a whole, except when it is necessary to distinguish them from a single polymer block Y. In this specification, since this type of polymer block containing a coupling agent residue is treated as above, for example, a block copolymer containing a coupling agent residue and that should be strictly represented as ABXBA (X represents a coupling agent residue) is represented as ABA and is treated as an example of a triblock copolymer.

[0028] Furthermore, the styrene-based resin may contain a polymer block (C) consisting of a polymerizable monomer other than the polymer block (A) and the polymer block (B) within the scope of the present invention. In this case, when the polymer block (C) is represented by C, examples of the block copolymer structure include an ABC type triblock copolymer, an ABCA type tetrablock copolymer, and an ABAC type tetrablock copolymer.

[0029] As the styrene resin, it is preferable to use one having 5% to 75% by mass of styrene compound units represented by the following general formula (1) or the like, based on the total mass of the styrene resin, more preferably one having 5% to 50% by mass, even more preferably one having 10% to 45% by mass, and particularly preferably one having 10% to 40% by mass. By using a ratio of styrene compound units to the total mass of the styrene resin within the above-mentioned preferable range, it becomes easier to obtain the breaking elongation and breaking strength in a suitable range. [ka]

[0030] The styrene-based resin may have one or more functional groups, such as a carboxyl group, a hydroxyl group, an acid anhydride group, an amino group, an epoxy group, etc., in the molecular chain and / or at the molecular terminal, or may have no functional groups, as long as the object and effects of the present invention are not impaired.

[0031] Here, when a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer are used in combination as the styrene-based resin, the content of the styrene-isoprene copolymer relative to the total mass of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer is preferably 0% by mass to 80% by mass, more preferably 0% by mass to 70% by mass, even more preferably 0% by mass to 50% by mass, and particularly preferably 0% by mass to 30% by mass. When the content of the styrene-isoprene copolymer is within the above-mentioned preferred range, it is possible to achieve both excellent thermal durability while maintaining excellent breaking elongation and breaking strength.

[0032] The styrene-isoprene copolymer preferably has a weight average molecular weight measured in terms of standard polystyrene using gel permeation chromatography (GPC) in the range of 10,000 to 800,000, more preferably in the range of 30,000 to 500,000, and even more preferably in the range of 50,000 to 300,000. When the weight average molecular weight of the styrene-isoprene copolymer is within the above-mentioned preferred range, it is possible to ensure heat flowability and compatibility when diluted with a solvent, and therefore it is preferable that a first base layer having good workability in the production process and heat durability can be obtained.

[0033] Here, the weight average molecular weight is measured by the GPC method using a GPC apparatus (SC-8020, manufactured by Tosoh Corporation) and is expressed as a standard polystyrene equivalent value. The measurement conditions are as follows. -Measurement conditions- Sample concentration: 0.5% by mass (tetrahydrofuran solution) Sample injection volume: 100μL Eluent: THF (tetrahydrofuran) · Flow rate: 1.0mL / min · Measurement temperature: 40℃ - Column: TSKgel® GMHHR-H(20) x 2 Guard column: TSKgel HXL-H Detector: Differential refractometer Standard polystyrene molecular weight: 10,000 to 20 million (Tosoh Corporation)

[0034] The method for producing the styrene-isoprene copolymer, the styrene-isoprene-styrene copolymer, and the mixture of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. The block copolymer can be obtained by an anionic living polymerization method, and a coupling agent can be added and reacted as necessary. Specifically, the method for producing a styrene-isoprene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods, such as a method in which a styrene block and an isoprene block are sequentially polymerized by an anionic living polymerization method.

[0035] The method for producing a styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. Examples of the method include a method in which a styrene block and an isoprene block are sequentially polymerized by an anionic living polymerization method, and a method in which a block copolymer having a living active end is produced and then reacted with a coupling agent to produce a coupled block copolymer.

[0036] The method for producing the mixture of styrene-isoprene copolymer and styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. For example, a method of mixing the styrene-isoprene copolymer produced by the above method with a styrene-isoprene-styrene copolymer can be mentioned.

[0037] As a method for producing a mixture of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer, it is also possible to produce them as a mixture simultaneously in one polymerization step. In a more specific embodiment, the anionic living polymerization method involves first polymerizing a styrene monomer in a polymerization solvent using an anionic polymerization initiator to form a polystyrene block having a living active end. Secondly, isoprene is polymerized from the living active end of the polystyrene block to obtain a styrene-isoprene diblock copolymer having a living active end. Thirdly, a part of the styrene-isoprene diblock copolymer having a living active end is reacted with a coupling agent to form a coupled styrene-isoprene-styrene block copolymer. Fourthly, the remaining part of the styrene-isoprene diblock copolymer having a living active end is deactivated at its living active end using a polymerization terminator to form a styrene-isoprene diblock copolymer.

[0038] Here, the styrene-based resin is preferably a hydrogenated product of a styrene-isoprene copolymer, a styrene-isoprene-styrene copolymer, a styrene-isoprenebutadiene-styrene copolymer, or a styrene-butadiene-styrene copolymer. More specifically, a hydrogenated copolymer obtained by hydrogenating a block copolymer composed of at least a polymer block (A) mainly composed of a styrene-based compound unit and a polymer block (B) mainly composed of a structural unit derived from isoprene (hereinafter also referred to as an isoprene unit), a structural unit derived from butadiene (hereinafter also referred to as a butadiene unit), or a structural unit derived from a mixture of isoprene and butadiene (hereinafter also referred to as an isoprene and butadiene unit) is preferred.

[0039] When the styrene-based resin is a hydrogenated copolymer in which a block copolymer composed of at least a polymer block (A) and a polymer block (B) mainly composed of isoprene units, butadiene units, or isoprene and butadiene units is hydrogenated, the polymer block (A) and the polymer block (B) described above preferably have the following structures.

[0040] Of the polymer blocks (A) contained in the styrene-based resin, at least one polymer block (A) preferably has a weight average molecular weight of 3,000 to 15,000, more preferably 3,000 to 12,000. When the styrene-based resin has at least one polymer block (A) having a weight average molecular weight within the above range, the mechanical strength of the styrene-based resin containing the styrene-based resin is further improved.

[0041] From the viewpoint of mechanical strength, the total weight average molecular weight of the polymer blocks (A) contained in the styrene-based resin is preferably 3,500 to 15,000, more preferably 4,500 to 15,000, even more preferably 4,500 to 12,000, particularly preferably 5,000 to 11,000, and most preferably 8,000 to 11,000. The "weight average molecular weight" is the weight average molecular weight calculated in terms of standard polystyrene obtained by the above-mentioned gel permeation chromatography (GPC) measurement. The weight average molecular weight of each polymer block (A) of the styrene-based resin can be obtained by measuring a sampled liquid each time the polymerization of each polymer block is completed in the production process. In addition, for example, in the case of a triblock copolymer having an ABA structure, the weight average molecular weight of the second polymer block A can be obtained by determining the weight average molecular weights of the first polymer block A and polymer block B by the above-mentioned method and subtracting them from the weight average molecular weight of the styrene-based resin. In addition, as another method, in the case of a triblock copolymer having an ABA structure, the total weight average molecular weight of the polymer blocks (A) can be calculated by subtracting the weight average molecular weight of the styrene-based resin from the weight average molecular weight of the polymer block (A). 1The weight average molecular weight of the second polymer block A can also be calculated from the total content of polymer block (A) confirmed by H-NMR measurement, and the weight average molecular weight of the deactivated first polymer block A calculated by GPC measurement, and then subtracted to obtain the weight average molecular weight of the second polymer block A.

[0042] The styrene resin preferably has a polymer block (A) content (when a plurality of polymer blocks (A) are present, the total content thereof) of 5 to 75 mass % based on the total amount of the styrene resin, more preferably 5 to 50 mass %, and further preferably 10 to 40 mass %. When the polymer block (A) content is within the above range, the obtained styrene resin has superior flexibility. The content of the polymer block (A) in the styrene-based resin is 1 The value was determined by HNMR spectroscopy.

[0043] The polymer block (B) is mainly composed of isoprene units, butadiene units, or isoprene and butadiene units. As described above, the polymer block (B) is allowed to contain other monomers, and may contain at least one structural unit derived from a conjugated diene compound other than isoprene and butadiene, such as 2,3-dimethylbutadiene, 1,3-pentadiene, 1,3-hexadiene, etc. As described above, the polymer block (B) is mainly composed of isoprene units, butadiene units, or isoprene and butadiene units. However, if the polymer block (B) is mainly composed of butadiene units or isoprene and butadiene units, the mechanical strength (particularly rubber elasticity) of the styrene resin is excellent. Furthermore, it is more preferable that the polymer block (B) is mainly composed of isoprene and butadiene units. The mixing ratio of isoprene and butadiene is not particularly limited, but from the viewpoint of improving various performances, the molar ratio of isoprene / butadiene is preferably 10 / 90 to 90 / 10, more preferably 30 / 70 to 70 / 30, and even more preferably 40 / 60 to 60 / 40. Furthermore, when the polymer block (B) is mainly composed of isoprene and butadiene units, the bonding form thereof is not particularly limited, and may be random, tapered, completely alternating, partially block-like, block, or a combination of two or more of them.

[0044] The bond forms of isoprene and butadiene constituting the polymer block (B) can be 1,2-bonds and 1,4-bonds in the case of butadiene, and 1,2-bonds, 3,4-bonds and 1,4-bonds in the case of isoprene. In the case of styrene-based resins, the total content of 1,2-bonds and 3,4-bonds in the polymer block (B) is preferably 40 mol% or more, more preferably 60 mol% or more, even more preferably 80 mol% or more, still more preferably 85 mol% or more, and most preferably 90 mol% or more. Also, it is preferably 95 mol% or less. In addition, when the polymer block (B) is composed only of butadiene, the above-mentioned "total content of 1,2-bonds and 3,4-bonds" is read as "content of 1,2-bonds". The contents of 1,2-bonds and 3,4-bonds are as follows: 1 This value was calculated by H-NMR measurement. In this specification, when polymer block (B) contains isoprene units, the total amount of 1,2-bonds and 3,4-bonds is referred to as the vinyl bond amount, and when polymer block (B) is composed of butadiene units, the 1,2-bond amount is referred to as the vinyl bond amount in some cases.

[0045] The polymer block (B) may contain structural units derived from other polymerizable monomers other than isoprene units and butadiene units, usually preferably 30% by mass or less, more preferably 10% by mass or less, based on the total mass of the polymer block (B), as long as the purpose and effect of the present invention are not hindered. Examples of the other polymerizable monomers include aromatic vinyl compounds such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, pt-butylstyrene, 2,4-dimethylstyrene, vinylnaphthalene, and vinylanthracene, as well as at least one compound selected from the group consisting of methyl methacrylate, methyl vinyl ether, N-vinylcarbazole, β-pinene, 8,9-p-menthene, dipentene, methylenenorbornene, and 2-methylenetetrahydrofuran. When the polymer block (B) contains structural units derived from other polymer monomers other than isoprene units and butadiene units, the bonding form is not particularly limited and may be either random or tapered.

[0046] The styrene-based resin may have at least one of the polymer blocks (B). When the styrene-based resin has two or more polymer blocks (B), the polymer blocks (B) may be the same or different.

[0047] The hydrogenation rate of the polymer block (B) is preferably 50 mol % or more, more preferably 75 mol % or more, and further preferably 95 mol % or more. The hydrogenation rate is determined by calculating the amount of carbon-carbon double bonds in the structural units derived from the conjugated diene compound in the polymer (B), 1 This value was calculated using H-NMR spectrum, and more detailed conditions are as described in the Examples.

[0048] When the styrene-based resin is the above-mentioned hydrogenated copolymer, the weight average molecular weight of the styrene-based resin is preferably 50,000 to 500,000, more preferably 60,000 to 400,000, further preferably 65,000 to 300,000, and particularly preferably 70,000 to 115,000.

[0049] The fluidity of the styrene resin is preferably a melt flow rate of 0.01 to 300 g / 10 min measured at 230° C. and 21.6 N. When film molding is performed by the T-die method or inflation method, the flow rate is more preferably 0.01 to 100 g / 10 min, and when tube molding or injection molding is performed by the extrusion method, the flow rate is more preferably 0.1 to 100 g / 10 min. Note that all "melt flow rates" in this specification are values ​​measured in accordance with JIS K 7210 (1999).

[0050] In the first embodiment, when the styrene-based resin is the hydrogenated copolymer, the styrene-based resin includes a hydrogenated block copolymer, styrene-ethylene-ethylene / propylene-styrene block copolymer (SEEPS). The styrene-ethylene-ethylene / propylene-styrene block copolymer is a hydrogenated product of a block copolymer formed of styrene-butadiene-isoprene-styrene. As the SEEPS, a commercially available product can be used, and examples thereof include Septon 4033, Septon 4044, Septon 4055, Septon 4077, and Septon 4099 manufactured by Kuraray Co., Ltd.

[0051] The styrene-based resin can be produced by a solution polymerization method, an emulsion polymerization method, a solid-phase polymerization method, or the like. Among them, the solution polymerization method is preferred, and known methods such as ionic polymerization methods such as anionic polymerization and cationic polymerization, and radical polymerization methods can be applied. Among them, the anionic polymerization method is preferred. In the anionic polymerization method, an aromatic vinyl compound and a conjugated diene compound are successively added in the presence of a solvent, an anionic polymerization initiator, and, if necessary, a Lewis base to obtain a block copolymer, a coupling agent is added if necessary to cause a reaction, and then the block copolymer is hydrogenated to obtain a styrene-based resin.

[0052] In the above method, examples of organolithium compounds that can be used as a polymerization initiator include methyllithium, ethyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, pentyllithium, etc. Examples of dilithium compounds that can be used as a polymerization initiator include naphthalenedilithium, dilithiohexylbenzene, etc.

[0053] Examples of the coupling agent include dichloromethane, dibromomethane, dichloroethane, dibromoethane, dibromobenzene, and phenyl benzoate. The amount of these polymerization initiators and coupling agents used is appropriately determined according to the desired weight average molecular weight of the target styrene resin. Usually, initiators such as alkyl lithium compounds and dilithium compounds are preferably used in a ratio of 0.01 to 0.2 parts by mass per 100 parts by mass of the total of monomers such as styrene compounds, butadiene, and isoprene used in polymerization, and when a coupling agent is used, it is preferably used in a ratio of 0.001 to 0.8 parts by mass per 100 parts by mass of the total of monomers.

[0054] The solvent is not particularly limited as long as it does not adversely affect the anionic polymerization reaction, and examples thereof include aliphatic hydrocarbons such as cyclohexane, methylcyclohexane, n-hexane, n-pentane, etc., and aromatic hydrocarbons such as benzene, toluene, xylene, etc. The polymerization reaction is usually carried out at a temperature of 0 to 100°C, preferably 10 to 70°C, for 0.5 to 50 hours, preferably 1 to 30 hours.

[0055] In the above anionic polymerization, the amount of 1,2-bonds and the amount of 3,4-bonds in the unhydrogenated block copolymer can be increased by adding an organic Lewis base, and the amount of 1,2-bonds and the amount of 3,4-bonds can be controlled by the amount of the organic Lewis base added. Examples of the organic Lewis base that can be used include amines such as triethylamine, N,N,N',N'-tetramethylethylenediamine (TMEDA), and N-methylmorpholine; nitrogen-containing heterocyclic aromatic compounds such as pyridine; amides such as dimethylacetamide; ethers such as dimethyl ether, diethyl ether, tetrahydrofuran (THF), and dioxane; glycol ethers such as ethylene glycol dimethyl ether and diethylene glycol dimethyl ether; sulfoxides such as dimethyl sulfoxide; ketones such as acetone and methyl ethyl ketone. These organic Lewis bases can be used alone or in combination of two or more. The amount of the organic Lewis base to be added is determined by the extent to which the vinyl bond amount of the isoprene unit and / or butadiene unit constituting the polymer block (B) is controlled. Therefore, the amount of the Lewis base to be added is not strictly limited, but it is preferable to use it within the range of usually 0.1 to 1,000 mol, preferably 1 to 100 mol, per gram atom of lithium contained in the alkyllithium compound or dilithium compound used as a polymerization initiator.

[0056] After polymerization is performed by the above-mentioned method, an active hydrogen compound such as an alcohol, a carboxylic acid, or water is added to terminate the polymerization reaction, and a hydrogenation reaction (hydrogenation reaction) is performed in an inert organic solvent in the presence of a hydrogenation catalyst. The hydrogenation reaction can be performed under a hydrogen pressure of 0.1 to 20 MPa, preferably 0.5 to 15 MPa, and more preferably 0.5 to 5 MPa, at a reaction temperature of 20 to 250°C, preferably 50 to 180°C, and more preferably 70 to 180°C, for a reaction time of usually 0.1 to 100 hours, and preferably 1 to 50 hours. Examples of the hydrogenation catalyst include Raney nickel; heterogeneous catalysts in which a metal such as Pt, Pd, Ru, Rh, or Ni is supported on a substrate such as carbon, alumina, or diatomaceous earth; Ziegler catalysts comprising a combination of a transition metal compound with an alkylaluminum compound, an alkyllithium compound, or the like; and metallocene catalysts.

[0057] The styrene-based resin thus obtained can be obtained by pouring the polymerization reaction liquid into methanol or the like to coagulate it, followed by drying under heating or reduced pressure, or by pouring the polymerization reaction liquid together with steam into hot water to remove the solvent by azeotropy (so-called steam stripping), followed by drying under heating or reduced pressure.

[0058] -Polyurethane resin- The polyurethane resin is not particularly limited and can be appropriately selected depending on the purpose, but preferably has a softening point of 40° C. or more, and more preferably has a softening point of 50° C. or more. The upper limit of the softening point is preferably 100° C. or less. The softening point refers to a value measured in accordance with JIS K 2207 (ring and ball method) (the same applies to the softening point below).

[0059] As the polyurethane resin, a reaction product of a polyol (b1-1) and a polyisocyanate (b1-2) can be suitably used.

[0060] The polyol (b1-1) is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include polyester polyol, polyether polyol, polycarbonate polyol, and acrylic polyol. These may be used alone or in combination of two or more. Among these, polyester polyol and polyether polyol are preferable as the polyol (b1-1) because they can obtain the mechanical properties of the first base layer. When heat resistance is required in the first base layer, it is preferable to use polyester polyol, and when water resistance or biodegradability is required, it is preferable to use polyether polyol.

[0061] Examples of polyester polyols include polyesters obtained by an esterification reaction between a low molecular weight polyol and a polycarboxylic acid, polyesters obtained by a ring-opening polymerization reaction of a cyclic ester compound such as ε-caprolactone, and copolymer polyesters thereof.

[0062] Examples of low molecular weight polyols that can be used in the production of polyester polyols include aliphatic alkylene glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, and 1,3-butanediol, each of which has a weight average molecular weight of about 50 to 300, and cyclohexanedimethanol.

[0063] Examples of polycarboxylic acids include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid; and anhydrides or esters thereof.

[0064] Examples of polyether polyols include those obtained by addition polymerization of alkylene oxide using one or more compounds having two or more active hydrogen atoms as an initiator.

[0065] As the polycarbonate polyol, for example, one obtained by reacting a carbonate ester and / or phosgene with a low molecular weight polyol described later can be used.

[0066] Examples of carbonate esters include methyl carbonate, dimethyl carbonate, ethyl carbonate, diethyl carbonate, cyclocarbonate, and diphenyl carbonate.

[0067] Examples of low molecular weight polyols that can be used to produce polycarbonate polyols and that can react with carbonate esters and / or phosgene include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propanediol, 1,3-propanediol, dipropylene glycol, tripropylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,5-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 1 ,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,4-cyclohexanedimethanol, hydroquinone, resorcinol, bisphenol A, bisphenol F, 4,4'-biphenol, and the like.

[0068] The polyisocyanate (b1-2) is not particularly limited and can be appropriately selected depending on the purpose, and examples of the polyisocyanate that can be used include alicyclic polyisocyanates, aliphatic polyisocyanates, aromatic polyisocyanates, etc., and examples of the polyisocyanate include alicyclic polyisocyanates, etc. These may be used alone or in combination of two or more kinds.

[0069] Examples of alicyclic polyisocyanates include isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, 2,4-methylcyclohexane diisocyanate, 2,6-methylcyclohexane diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, 2,6-norbornane diisocyanate, dimer acid diisocyanate, bicycloheptane triisocyanate, etc. These may be used alone or in combination of two or more.

[0070] The method for producing the polyurethane resin (b1) by reacting the polyol (b1-1) with the polyisocyanate (b1-2) is not particularly limited and may be appropriately selected from conventionally known production methods. For example, there may be mentioned a method in which the polyol (b1-1) charged in a reaction vessel is heated under normal pressure or reduced pressure conditions to remove moisture, and then the polyisocyanate (b1-2) is supplied all at once or in portions and reacted.

[0071] The reaction between the polyol (b1-1) and the polyisocyanate (b1-2) is preferably carried out in such a manner that the equivalent ratio (NCO / OH equivalent ratio) of the isocyanate group (NCO) in the polyisocyanate (b1-2) to the hydroxyl group (OH) in the polyol (b1-1) is in the range of 1.0 to 20.0, more preferably in the range of 1.1 to 13.0, even more preferably in the range of 1.2 to 5.0, and particularly preferably in the range of 1.5 to 3.0.

[0072] The reaction conditions for the polyol (b1-1) and the polyisocyanate (b1-2) are not particularly limited and can be appropriately selected taking into consideration various conditions such as safety, quality, and cost. The reaction temperature is preferably 70°C to 120°C, and the reaction time is preferably 30 minutes to 5 hours.

[0073] When reacting the polyol (b1-1) with the polyisocyanate (b1-2), a catalyst such as a tertiary amine catalyst or an organometallic catalyst may be used as necessary.

[0074] The reaction may be carried out in a solvent-free environment or in the presence of an organic solvent. The organic solvent is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include ester-based solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; ketone-based solvents such as acetone, methyl ethyl ketone, methyl butyl ketone, and cyclohexanone; ether ester-based solvents such as methyl cellosolve acetate and butyl cellosolve acetate; aromatic hydrocarbon-based solvents such as toluene and xylene; and amide-based solvents such as dimethylformamide and dimethylacetamide. These may be used alone or in combination of two or more. The organic solvent may be removed during the production of the polyurethane resin (b1) or after the production of the polyurethane (b1) by a suitable method such as heating under reduced pressure or drying at normal pressure.

[0075] -Other ingredients- The other components in the first base layer are not particularly limited and can be appropriately selected within a range that does not impair the properties of the adhesive tape, and examples thereof include tackifier resins; polymer components other than the material for the first base; crosslinking agents, antiaging agents, UV absorbers, fillers, polymerization inhibitors, surface conditioners, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, additives such as organic pigments, inorganic pigments, pigment dispersants, silica beads, and organic beads; inorganic fillers such as silicon oxide, aluminum oxide, titanium oxide, zirconia, and antimony pentoxide. These may be used alone or in combination of two or more. The content of other components in the first base layer can be appropriately selected within a range that does not impair the properties of the pressure-sensitive adhesive tape.

[0076] The tackifier resin can be used for the purposes of increasing the adhesion between the adhesive layer of the adhesive tape and the first base layer and increasing the heat resistance.

[0077] The tackifier resin is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the softening point is 80°C or higher, more preferably 90°C or higher, even more preferably 100°C or higher, and particularly preferably 110°C or higher.

[0078] As the tackifier resin, for example, those described in the section "-Rubber-based adhesive resin-" below can be used, and the preferred embodiments are also the same.

[0079] The antiaging agent is not particularly limited and can be appropriately selected from known ones according to the purpose, for example, phenol-based antiaging agents, phosphorus-based antiaging agents (sometimes called "processing stabilizers"), amine-based antiaging agents, imidazole-based antiaging agents, etc. can be mentioned. These may be used alone or in combination of two or more. Among these, phenol-based antiaging agents and phosphorus-based antiaging agents are preferred, and using them in combination is preferred because it can effectively improve the heat resistance stability of the first base material, and as a result, it is possible to obtain an adhesive tape that maintains good initial adhesion and has even better heat durability. In addition, since the phosphorus-based antiaging agent may slightly discolor (yellowing) over time in a high temperature environment, it is preferable to appropriately set the amount used in consideration of the balance between initial adhesion, heat durability, and discoloration prevention.

[0080] As the phenolic antioxidant, a phenolic compound having a steric hindrance group can be generally used, and monophenol type, bisphenol type, and polyphenol type are representative.Specific examples include 2,6-di-t-butyl-4-methylphenol, 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(6-t-butyl-3-methylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), tetrakis-[methylene-3-(3'5'-di-t-butyl-4-hydroxyphenyl)propionate]methane, and n-octadecyl-3-(4'-hydroxy-3'5'-di-t-butylphenyl)propionate.These may be used alone or in combination of two or more.

[0081] The amount of the phenol-based anti-aging agent used is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably used in the range of 0.1 parts by mass to 5 parts by mass per 100 parts by mass of the first substrate material, and using it in the range of 0.5 parts by mass to 3 parts by mass can effectively improve the heat resistance stability of the first substrate material, resulting in an adhesive tape that maintains good initial adhesion and has even better heat durability.

[0082] <Adhesive layer> In a first embodiment, the pressure-sensitive adhesive tape comprises a first pressure-sensitive adhesive layer and a third pressure-sensitive adhesive layer as pressure-sensitive adhesive layers. The first pressure-sensitive adhesive layer and the third pressure-sensitive adhesive layer are pressure-sensitive adhesive layers that form the pressure-sensitive adhesive surface of the pressure-sensitive adhesive tape that adheres to an adherend. The adhesive composition forming each adhesive layer contains an adhesive resin, and may further contain filler particles and other components as necessary in addition to the adhesive resin. The adhesive layers may be made of the same adhesive composition or different adhesive compositions.

[0083] The characteristics of each adhesive layer in the first embodiment will be described below. The stress of the adhesive layer at 25% elongation is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.04 MPa to 0.4 MPa, more preferably 0.05 MPa to 0.1 MPa. When the stress of the adhesive layer at 25% elongation is within the preferred range, the adhesive tape can have a suitable adhesive strength, and can be relatively easily peeled off even when stretched and peeled off. On the other hand, when the stress of the adhesive layer at 25% elongation is less than 0.04 MPa, the adhesive tape may peel off when a load is applied in the shear direction of the adhesive tape while fixing hard adherends to each other, and when it exceeds 0.4 MPa, the force required to stretch the adhesive tape when peeling off the adhesive tape may be excessive. The stress of the adhesive layer at 25% elongation refers to the stress value measured when the adhesive layer is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and pulled in the length direction at a tensile speed of 300 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement conditions of 23°C and 50% RH, and elongated by 25%.

[0084] The breaking strength of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.5 MPa to 2.1 MPa, more preferably 1.0 MPa to 2.1 MPa. When the breaking strength of the adhesive layer is within the above-mentioned preferred range, the adhesive tape can be prevented from tearing even when the adhesive tape is stretched and peeled off, and the load for stretching the adhesive tape is not excessive, so that the peeling operation is easy. On the other hand, when the breaking strength of the adhesive layer is less than 0.5 MPa, adhesive residue may occur due to cohesive failure of the adhesive layer when the adhesive tape is stretched and peeled off, and when it exceeds 2.1 MPa, sufficient adhesiveness may not be obtained. The force required to stretch and deform the adhesive tape also depends on the thickness of the adhesive tape. For example, even when an adhesive tape with a thick thickness and high breaking strength is stretched and peeled off, it may not be stretched sufficiently and cannot be peeled off. The breaking strength of the adhesive layer in an adhesive tape refers to the stress value measured when the adhesive layer is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and pulled in the lengthwise direction at a tensile speed of 300 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement conditions of 23°C and 50% RH, until the tape breaks.

[0085] The breaking elongation of the adhesive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 450% to 1,300%, more preferably 500% to 1,200%, and even more preferably 600% to 1,100%. When the breaking elongation of the adhesive layer is within the above-mentioned preferred range, it is possible to achieve both suitable adhesion and removability (ease of peeling). The breaking elongation of the adhesive layer in an adhesive tape refers to the tensile elongation measured when the adhesive layer is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and pulled in the length direction at a tensile speed of 300 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement conditions of 23°C and 50% RH until breaking.

[0086] The thickness of the adhesive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 5 μm to 150 μm, more preferably 20 μm to 120 μm, even more preferably 30 μm to 110 μm, and particularly preferably 50 μm to 100 μm. The "thickness of the adhesive layer" means the thickness of one adhesive layer in the adhesive tape. The average thickness of each adhesive layer may be the same or different from each other. In this specification, the "thickness of the adhesive layer" refers to the average value of the thicknesses of the adhesive layer at any five points in the adhesive tape measured using a TH-104 Paper / Film Thickness Meter (manufactured by Tester Sangyo Co., Ltd.).

[0087] In the first embodiment, the first adhesive layer has a thickness of preferably 10 to 150 μm, more preferably 20 to 130 μm, and even more preferably 30 to 110 μm, because adhesion to the adherend is easily ensured. The third adhesive layer has a thickness of preferably 10 to 100 μm, and more preferably 30 to 80 μm, because adhesion to the adherend is easily ensured. The second adhesive layer may have a thickness similar to that of the first adhesive layer or the third adhesive layer, or may have a different thickness.

[0088] Here, in the first embodiment, at least the third adhesive layer, preferably the adhesive layers on both sides adjacent to the foam layer (the second and third adhesive layers in the first embodiment, and the third and fourth adhesive layers in the second and third embodiments described below), preferably have a peak value of loss tangent (tan δ) at a frequency of 1 Hz of −30° C. to 0° C., more preferably −20° C. to −5° C. By setting the peak value of the loss tangent of the adhesive layer within this range, it becomes easier to impart good adhesion to an adherend at room temperature. The loss tangent (tan δ) is calculated from the storage modulus (G') and loss modulus (G'') obtained by dynamic viscoelasticity measurement using temperature dispersion using the formula tan δ = G'' / G'. The peak value of the loss tangent (tan δ) at a certain frequency can be obtained from dynamic viscoelasticity measurement using temperature dispersion. The dynamic viscoelastic properties can be adjusted by appropriately selecting the types and ratios of monomers used in the copolymer that constitutes the adhesive resin, the type and amount of polymerization initiator used, the type and amount of crosslinking agent or tackifier resin used, the polymerization method, etc.

[0089] The dynamic viscoelastic properties of the adhesive layer are defined by the loss tangent of the dynamic viscoelastic spectrum at a specific frequency and a specific temperature, or the loss tangent and storage modulus, and further defined by the temperature showing the peak of the loss tangent of the dynamic viscoelastic spectrum at a specific frequency, or the peak value of the loss tangent. In measuring the dynamic viscoelasticity, a viscoelasticity tester (manufactured by Rheometrics, product name: Ares 2KSTD) is used, and a test piece is sandwiched between parallel disks, which are the measuring part of the tester, and the storage modulus (G') and loss modulus (G'') are measured from -50°C to 150°C at a frequency of 1Hz. The test piece is formed into an adhesive layer with a thickness of about 2mm, and is sandwiched between parallel disks for measurement.

[0090] -Filler particles-

[0091] In the first embodiment, the adhesive layer adjacent to the first base layer is preferably a first adhesive layer formed from an adhesive composition containing filler particles having an average particle size of 10 to 40 μm and an adhesive resin. The content of the filler particles in the adhesive composition for forming the first adhesive layer containing the filler particles is preferably 3 to 50 parts by mass per 100 parts by mass of the adhesive resin. Similarly, the second adhesive layer adjacent to the first base layer is preferably formed from an adhesive composition containing filler particles having an average particle size of 10 to 40 μm and an adhesive resin. The content of the filler particles in the second adhesive layer containing the filler particles is preferably 3 to 50 parts by mass per 100 parts by mass of the adhesive resin. The adhesive layer adjacent to the first base layer is preferably at least the first adhesive layer. In addition, as in the adhesive tape of the second embodiment described below, when a second adhesive layer is provided between the first base layer and the foam layer as necessary, the adhesive layer adjacent to the first base layer may be the first adhesive layer and the second adhesive layer described below. Furthermore, in this specification, when simply referred to as an adhesive layer, the adhesive layer includes both the first adhesive layer and the second adhesive layer.

[0092] Since the adhesive layer or the adhesive composition forming the adhesive layer contains the filler particles, when the first base layer is stretched to peel off the adhesive tape from between the first adherend and the second adherend, the adjacent adhesive layer also stretches following the first base layer, and the filler particles are exposed from the adhesive layer. This reduces the adhesion area between the first adhesive layer and the adherend. Therefore, the adhesive tape can be peeled off more easily, making the peeling operation easier. Alternatively, as in the case of the adhesive tape of the second embodiment described later, when a second adhesive layer is provided between the first base layer and the foam layer as required, the adhesion area between the second adhesive layer and the layer adjacent to the second adhesive layer (e.g., the foam layer) is reduced, and therefore the adhesive tape can be peeled off more easily, making the peeling operation even easier.

[0093] The type of filler particles is not particularly limited and can be appropriately selected within a range that does not impair the effects of the present invention, and may be inorganic filler particles or organic filler particles. These may be used alone or in combination of two or more types.

[0094] Specific examples of inorganic filler particles include aluminum hydroxide, magnesium hydroxide, aluminum oxide, silicon oxide, magnesium oxide, zinc oxide, titanium oxide, zirconium oxide, iron oxide, silicon carbide, boron nitride, aluminum nitride, titanium nitride, silicon nitride, titanium boride, carbon, nickel, copper, aluminum, titanium, gold, silver, zirconium hydroxide, basic magnesium carbonate, dolomite, hydrotalcite, calcium hydroxide, barium hydroxide, tin oxide, tin oxide hydrate, borax, zinc borate, zinc metaborate, barium metaborate, zinc carbonate, magnesium-calcium carbonate, calcium carbonate, barium carbonate, Examples of such metals include molybdenum oxide, antimony oxide, red phosphorus, mica, clay, kaolin, talc, zeolite, wollastonite, smectite, silica (quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, ultrafine amorphous silica, etc.), potassium titanate, magnesium sulfate, sepiolite, zonolite, aluminum borate, barium sulfate, barium titanate, zirconia oxide, cerium, tin, indium, carbon, sulfur, cerium, cobalt, molybdenum, strontium, chromium, barium, lead, tin oxide, indium oxide, diamond, magnesium, platinum, zinc, manganese, and stainless steel. Among these, aluminum hydroxide and nickel are preferred. The inorganic filler may be surface-treated, such as by silane coupling treatment or stearic acid treatment, in order to improve dispersibility in the adhesive resin.

[0095] Specific examples of organic filler particles include polystyrene-based fillers, benzoguanamine-based fillers, polyethylene-based fillers, polypropylene-based fillers, silicone-based fillers, urea-formaldehyde-based fillers, styrene / methacrylic acid copolymers, fluorine-based fillers, acrylic-based fillers, polycarbonate-based fillers, polyurethane-based fillers, polyamide-based fillers, epoxy resin-based fillers, and thermosetting resin-based hollow fillers.

[0096] Among the organic filler particles, specifically, examples of the silicone-based filler that can be used include silicone rubber particles obtained by three-dimensionally crosslinking linear organopolysiloxane (see JP-A-63-77942, JP-A-3-93834, and JP-A-04-198324), powdered silicone rubber (see U.S. Pat. No. 3,843,601, JP-A-62-270660, and JP-A-59-96,122), and the like.Furthermore, the surface of the silicone rubber particles obtained by the above method can be modified to have a (R'SiO 3 / 2 ) n Silicone composite particles (see JP-A-7-196815) can also be used that are coated with a silicone resin, which is a cured polyorganosilsesquioxane having a three-dimensional network-like crosslinked structure represented by the formula: (R' represents a substituted or unsubstituted monovalent hydrocarbon group). More specifically, silicone composite particles in which the surfaces of silicone rubber particles are coated with silicone resin are more preferred. As such silicone-based fillers, those commercially available under the above-mentioned trade names, such as Trefil E-500, Trefil E-600, Trefil E-601, and Trefil E-850, are available from Dow Corning Toray Silicones Co., Ltd., and those commercially available under the above-mentioned trade names, such as KMP-600, KMP-601, KMP-602, and KMP-605, are available from Shin-Etsu Chemical Co., Ltd. As another silicone-based filler, an acrylic-modified silicone can be used.

[0097] The adhesive layer in this embodiment contains an adhesive resin and filler particles, and preferably contains an adhesive resin, an acrylic-modified silicone, and microballoons, which are an optional component, as described below. The filler particles present in the adhesive layer in this embodiment, particularly the acrylic-modified silicone, exhibit high affinity for the coexisting adhesive resin, making it difficult to determine the content of the acrylic-modified silicone and the presence or absence of acrylic modification from the adhesive tape. In cases where it is difficult to specify the presence or absence and content of filler particles, particularly acrylic-modified silicone, present in the adhesive layer or adhesive composition in this embodiment, for example, as an alternative to specifying the presence and content of filler particles, particularly acrylic-modified silicone, the frictional force of the outer surface of the adhesive layer in this embodiment may be in the range of 0.1 to 5.0 N. In other words, in this embodiment, a specific means for achieving a frictional force of the outer surface of the adhesive layer in the range of 0.1 to 5.0 N is a mode in which the adhesive layer contains an adhesive resin and an acrylic modified silicone.

[0098] The friction force of the outer surface of the adhesive layer of the adhesive tape of this embodiment is preferably 0.1 to 5.0 N, more preferably 0.3 to 4.0 N, and even more preferably 0.5 to 3.0 N. When the frictional force of the outer surface of the adhesive layer in this embodiment is within the above range, when the adhesive tape is pulled to peel it off from the adherend, the frictional resistance of the adhesive tape on the surface of the adherend decreases, thereby effectively reducing the adhesive force of the adhesive layer to the adherend and making it easier to peel the adhesive tape off. In this embodiment, the outer surface of the adhesive layer refers to the surface that adheres to the adherend, in other words, the outermost surface of the adhesive layer opposite the base layer side among the two opposing surfaces. In the adhesive tape of this embodiment, the frictional force of the outer surface of at least one of the adhesive layers among the multiple adhesive layers may be 0.1 to 5.0 N. Furthermore, the frictional force of both outer surfaces of the two adhesive layers provided on both sides of the base layer may be 0.1 to 5.0 N. As described above, the frictional force of the adhesive layer in this specification refers to the frictional force of the surface of the adhesive layer that comes into contact with the adherend, and the frictional force of the adhesive layer is measured by the test method described in the frictional force measurement explained in the Examples below. More specifically, the frictional force of the outer surface of the adhesive layer in this specification refers to the frictional force against cotton canvas at 23° C., and is preferably 0.1 to 5.0N, more preferably 0.3 to 4.0N, and even more preferably 0.5 to 3.0N. In this specification, the cotton canvas is made of cotton, and is No. 9 cotton canvas [(based on the old JIS L3102) raw yarn twist (warp 10 / 2, weft 10 / 3), density (warp 44-48 threads / inch, weft 33-37 threads / inch), weight 510 g / m 2 )] was used, and the friction force was measured in an atmosphere with a temperature of 23°C and a humidity of 50%.

[0099] In this embodiment, when the acrylic-modified silicone is present in the adhesive layer, the frictional force of the surface of the adhesive layer tends to be low. In addition, when the frictional force of the adhesive layer is low, it has an effect of being easy to slip during 90° peeling, and peeling is facilitated. In this specification, the frictional force of the adhesive layer refers to the frictional force of the surface of the adhesive layer that comes into contact with the adherend (other than the base material layer), and the frictional force of the adhesive layer is measured by the test method described in the frictional force measurement explained in the Examples section below.

[0100] The acrylic-modified silicone may be an emulsion graft polymer of a polyorganosiloxane represented by the following general formula (2), an acrylic acid ester monomer and / or a methacrylic acid ester monomer, and a functional group-containing monomer copolymerizable therewith.

[0101] [ka]

[0102] (In the above general formula (2), R 1 and R 2 each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms; 1 , X 2 , X 3 , X 4 , X 5 , and X 6 each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group; Y 1 and Y 2 are each independently 1or -[O-Si(X 7 )(X 8 )] c -X 9 represents a group represented by the formula: 7 , X 8 , and X 9 each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group; X 1 , X 2 , X 3 , X 4 , X 5 , X 6 , X 7 , X 8 , and X 9 And Y 1 and Y 2 at least two groups in the formula (1) are hydroxyl groups, and a, b, and c each independently represent a positive number satisfying 0≦a≦1,000, 100≦b≦10,000, and 1≦c≦1,000.

[0103] In the general formula (2), R 1 or R 2 The alkyl group having 1 to 20 carbon atoms represented by the formula (I) may be linear or branched, or may be cyclic. Specific examples include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tetradecyl, hexadecyl, octadecyl, cyclopentyl, cyclohexyl, and cycloheptyl. These alkyl groups may be substituted with a halogen atom, an acryloxy group, a methacryloxy group, a carboxy group, an alkoxy group, an alkenyloxy group, an amino group, or an alkyl, alkoxy, or (meth)acryloxy-substituted amino group. R 1 or R 2 Examples of the aryl group having 6 to 20 carbon atoms represented by the formula (R) include a phenyl group, a tolyl group, and a naphthyl group. 1 or R 2 is preferably a methyl group.

[0104] In the general formula (2), X 1 ~X 9 As the alkyl group having 1 to 20 carbon atoms and the aryl group having 6 to 20 carbon atoms represented by the formula: 1 or R 2 Examples of the alkyl group and the aryl group are the same as those exemplified above. X 1 ~X 9 Examples of the alkoxy group having 1 to 20 carbon atoms represented by the formula (I) include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a hexyloxy group, a heptyloxy group, an octyloxy group, a decyloxy group, and a tetradecyloxy group.

[0105] In the general formula (2), a, b, and c are positive numbers of 0≦a≦1,000, 100≦b≦10,000, and 1≦c≦1,000, but a is preferably a positive number of 0 to 200. If a is greater than 1,000, the strength of the resulting film is insufficient. b is preferably a positive number of 1,000 to 5,000. If b is less than 100, the film will have poor flexibility, and if it is greater than 10,000, it will be difficult to form a solid like particles. c is preferably a positive number of 1 to 200. Moreover, the polyorganosiloxane represented by the general formula (2) has at least two, and preferably 2 to 4, hydroxyl groups in one molecule from the viewpoint of crosslinkability, and the hydroxyl groups are preferably present at both ends of the molecular chain.

[0106] Examples of the acrylic acid ester monomer or methacrylic acid ester monomer used in the acrylic-modified silicone include methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, and cyclohexyl methacrylate.

[0107] Examples of the functional group-containing monomer copolymerizable with the acrylic acid ester monomer and / or the methacrylic acid ester monomer include monomers having an unsaturated bond including a carboxyl group, an amide group, a hydroxyl group, a vinyl group, an allyl group, and the like.

[0108] The acrylic modified silicone is preferably obtained by mixing 10 to 100 parts by mass of an acrylic acid ester monomer and / or a methacrylic acid ester monomer, and 0.01 to 20 parts by mass of a functional group-containing monomer copolymerizable therewith, with respect to 100 parts by mass of the polyorganosiloxane represented by the above general formula (2), and subjecting the mixture to emulsion graft polymerization. The conditions for emulsion graft polymerization are not particularly limited, and as the initiator used during polymerization, a known radical initiator that is usually used for acrylic polymers can be used. Also, as the emulsifier, a known anionic surfactant or nonionic surfactant can be used.

[0109] The acrylic-modified silicone usable in the pressure-sensitive adhesive composition of the present embodiment may be in a form containing a polymer in which a part of the polyorganosiloxane is modified by a (meth)acrylic monomer, and is not particularly limited to any of solid, powder, particulate, and solution forms. The shape of the acrylic-modified silicone usable in the pressure-sensitive adhesive composition of the present embodiment is not particularly limited and can be appropriately selected according to the purpose, and may be a regular shape or an irregular shape. Specific examples of acrylic-modified silicone in the form of particles include polygonal, cubic, elliptical, spherical, needle-like, flat, and scale-like shapes, and among these, the particle shape is preferably elliptical, spherical, or polygonal, and more preferably spherical. When the particle shape is elliptical, spherical, polygonal, or the like, the adhesive layer slides well against the adherend when the adhesive tape is stretched, and the adhesive tape can be peeled off more easily and quickly. Particles of these shapes may be used alone or in combination of two or more types. Furthermore, when granular acrylic modified silicone is used, the average particle size of the acrylic modified silicone is preferably 10 to 400 μm, and more preferably 15 to 400 μm. When a granular acrylic modified silicone is used as the acrylic modified silicone of this embodiment, it is granulated and powdered by the following method. That is, spray drying, air flow drying, etc. are included, but a spray dryer is preferable from the viewpoint of productivity. Powdering is preferably performed by hot drying, and processing is preferably performed at 80 to 150°C. Examples of silicone compounds that can be used in this embodiment include commercially available products such as Charine R-170, Charine R-170S, Charine R-770, Charine R-773, and Charine R-200 (all manufactured by Nissin Chemical Industry Co., Ltd.).

[0110] The particle size distribution (D90 / D10) of the filler particles added to the adhesive composition of the present embodiment is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 2.5 to 20, and from the viewpoint of impact resistance, is more preferably 2.5 to 15, and is even more preferably 2.5 to 5. When the particle size distribution (D90 / D10) of the filler particles added to the adhesive composition is within a preferred range, the adhesive tape can be peeled off more easily and quickly, and even if the thickness of the first base material of the adhesive tape is thin, it is difficult to tear, and the impact resistance, shear adhesive strength, and split adhesive strength are excellent. On the other hand, when the particle size distribution (D90 / D10) of the filler particles added to the adhesive composition is less than 2.5, the stretch peelability may be impaired, and when it exceeds 20, the adhesive performance such as impact resistance, shear adhesive strength, and split adhesive strength may be impaired. The particle size distribution (D90 / D10) of the filler particles added to the adhesive composition is obtained by, for example, measuring the particle size of the filler particles using a measuring device (Microtrack) using a laser diffraction scattering method and converting it into a particle size distribution. In addition, in this specification, "filler particles added to the adhesive composition" refers to the filler particles alone when added to the adhesive composition, and is distinguished from the filler particles present in the adhesive layer. More specifically, in this specification, "average particle size" and "number average primary particle size" are distinguished from each other because the measurement methods for both are different. In this specification, "average particle size" refers to the volume average particle size measured by a laser diffraction scattering method for the filler particles alone. On the other hand, in this specification, "number average primary particle size" refers to the number average of the primary particle size calculated from an electron microscope image in an adhesive tape in which one or more types of filler particles and / or microballoons are mixed.

[0111] The average particle size of the filler particles added to the adhesive composition is 5 to 40 μm, preferably 10 to 35 μm, more preferably 10 to 30 μm, and even more preferably 10 to 25 μm. When the average particle size of the filler particles is within the preferred range, the adhesive tape can be peeled off more easily and quickly, and even if the thickness of the first base material of the adhesive tape is thin, the adhesive tape is not easily torn, and has excellent impact resistance, shear adhesive strength, and split adhesive strength. On the other hand, when the average particle size of the filler particles is less than 5 μm, the stretch peelability may be impaired, and when it exceeds 40 μm, adhesive performance such as impact resistance, shear adhesive strength, and split adhesive strength may be impaired. The average particle size of the filler particles refers to the volume average particle size, and can be measured, for example, by using a measuring device (Microtrack) that uses a laser diffraction scattering method. The average particle size includes not only primary particles, but also aggregates such as secondary particles.

[0112] When the silicone rubber particles or silicone composite particles are used as the filler particles to be added to the adhesive composition, the silicone rubber particles or silicone composite particles to be added to the adhesive composition preferably have an average particle size of 5 to 40 μm. If the average particle size is less than 5 μm, the effect of reducing the adhesion area by the filler particles when the adhesive tape is stretched tends to decrease, and if it is more than 40 μm, the adhesive strength of the adhesive tape tends to decrease. When the acrylic-modified silicone is used as the filler particles, the average particle size of the acrylic-modified silicone is preferably 5 to 40 μm. If the average particle size is less than 5 μm, the effect of the filler particles in reducing the adhesion area when the pressure-sensitive adhesive tape is stretched tends to decrease, and if it is more than 40 μm, the adhesive strength of the pressure-sensitive adhesive tape tends to decrease. On the other hand, in this embodiment, the number average primary particle diameter of the filler particles present in the adhesive layer is 3 to 45 μm, preferably 5 to 42 μm, more preferably 8 to 40 μm, even more preferably 9 to 35 μm, and most preferably 10 to 32 μm. In this specification, the "number average primary average particle size of the filler particles" refers to the size of the filler particles present in the adhesive layer, and the number average primary average particle size of the filler particles present in the adhesive layer is measured using the following method. First, the adhesive tape cooled under liquid nitrogen was cut at three random locations using a microtome, and three pieces were used as samples. Then, a photograph was taken of each sample at a magnification of 400 times using a scanning electron microscope, and filler particles, which are solid particles, were selected from the three photographs taken. Then, the cross-sectional area of ​​the solid body calculated by binarization processing (for example, Otsu's binarization processing) using image analysis software was regarded as the area of ​​a circle, and the circle equivalent diameter of each solid body was measured. Then, the total number of solid bodies in the three photographs and the circle equivalent diameter corresponding to each solid body were calculated, and the number average primary average particle size of the filler particles was calculated from the following formula (A).

number

[0113] The ratio of the average particle diameter of the filler particles to the average thickness of the adhesive layer containing the filler particles is not particularly limited and can be appropriately selected depending on the purpose, but the ratio of the average primary particle diameter of the filler particles to the average thickness of the adhesive layer, expressed as [average primary particle diameter of the filler particles / average thickness of the adhesive layer], is preferably 5 / 100 or more, more preferably 5 / 100 to 95 / 100, even more preferably 10 / 100 to 75 / 100, and particularly preferably 20 / 100 to 60 / 100. When the ratio is 5 / 100 or more, the adhesive tape can be peeled off more easily and quickly, and even if the thickness of the first base material of the adhesive tape is thin, it is difficult to tear. In addition, a ratio of 95 / 100 or less is advantageous in that the adhesive performance such as impact resistance, shear adhesive strength, and split adhesive strength is also more excellent.

[0114] The content of the filler particles in the adhesive layer or the adhesive composition for forming the adhesive layer is 3 to 50 parts by mass, preferably 10 to 50 parts by mass, and more preferably 15 to 40 parts by mass, relative to 100 parts by mass of the adhesive resin. When the content of the filler particles is 3 parts by mass or more relative to 100 parts by mass of the adhesive resin, the adhesive tape can be peeled off more easily and quickly. In addition, when the content of the filler particles is 50 parts by mass or less relative to 100 parts by mass of the adhesive resin, it is possible to prevent the adhesive composition from remaining on the adherend, the impact resistance from being deteriorated, and the shear adhesive strength or the split adhesive strength from being weakened. The content of the filler particles in the adhesive layer can be appropriately adjusted when preparing the adhesive composition.

[0115] In addition, when the above-mentioned silicone rubber particles or silicone composite particles are used as filler particles to be added to the adhesive composition, the content of the silicone rubber particles or silicone composite particles to be added to the adhesive composition is preferably 3 to 20 parts by mass per 100 parts by mass of the adhesive resin. Furthermore, when the above-mentioned acrylic-modified silicone is used as the filler particles to be added to the adhesive composition, the content of the acrylic-modified silicone to be added to the adhesive composition is preferably 10 to 50 parts by mass per 100 parts by mass of the adhesive resin.

[0116] The volume ratio of the filler particles to the total volume of the adhesive layer is preferably 4 to 40%, more preferably 5 to 30%, even more preferably 5 to 20%, and most preferably 5 to 15%. When the volume ratio of the filler particles is 4% or more, the adhesive tape can be peeled off more easily and quickly. When the volume ratio of the filler particles is 40% or less, it is possible to prevent the adhesive composition from remaining on the adherend, the impact resistance from being deteriorated, and the shear adhesive strength and split adhesive strength from being weakened. The volume ratio of the filler particles to the adhesive layer can be calculated from the following formulas (1) to (3). Adhesive Resin *1 Mass A (g) / Adhesive resin *1 Density A (g / cm 3 ) = Volume A of adhesive resin * 1 (cm 3 )...Equation (1) Mass of filler particles B (g) / Density of filler particles B (g / cm 3 ) = Volume of filler particles B (cm 3 )...Equation (2) Volume of filler particles B (cm 3 ) / (Adhesive resin *1 Volume A (cm 3 ) + volume of filler particles B (cm 3 )) × 100 = Volume ratio of filler particles (%) Equation (3) In the above formulas (1) and (3), *1 The adhesive resin represented by the formula (I) may contain other components described below. The density is a value measured in accordance with JIS Z 8804.

[0117] -Adhesive resin- The adhesive layer of the present embodiment essentially contains an adhesive resin. The adhesive resin is not particularly limited and can be appropriately selected from known materials, for example, acrylic adhesive resin, rubber adhesive resin, urethane adhesive resin, silicone adhesive resin, or other adhesive resin. These may be used alone or in combination of two or more. Among these, it is preferable that the adhesive resin contains an acrylic adhesive resin.

[0118] --Acrylic adhesive resin-- The acrylic adhesive resin is not particularly limited and can be appropriately selected depending on the purpose. For example, it may contain an acrylic polymer and, if necessary, additives such as a tackifier resin and a crosslinking agent.

[0119] Acrylic polymers can be produced, for example, by polymerizing (meth)acrylate monomers. As the (meth)acrylate monomer, for example, an alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms can be used. Specific examples of alkyl (meth)acrylates having an alkyl group having 1 to 12 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0120] As the alkyl (meth)acrylate having an alkyl group with 1 to 12 carbon atoms, it is preferable to use an alkyl (meth)acrylate having an alkyl group with 4 to 12 carbon atoms, it is more preferable to use an alkyl (meth)acrylate having an alkyl group with 4 to 8 carbon atoms, and it is particularly preferable to use n-butyl acrylate in order to ensure excellent adhesion to the adherend.

[0121] The alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms is preferably used in the range of 80 to 98.5 mass %, and more preferably 90 to 98.5 mass %, based on the total amount of monomers used in the production of the acrylic polymer.

[0122] As the monomers usable in the production of the acrylic polymer, in addition to the above-mentioned ones, highly polar vinyl monomers can be used as necessary. Examples of highly polar vinyl monomers include (meth)acrylic monomers such as (meth)acrylic monomers having a hydroxyl group, (meth)acrylic monomers having a carboxyl group, and (meth)acrylic monomers having an amide group, as well as sulfonic acid group-containing monomers such as vinyl acetate, ethylene oxide-modified succinic acid acrylate, and 2-acrylamido-2-methylpropanesulfonic acid. These may be used alone or in combination of two or more.

[0123] Specific examples of vinyl monomers having a hydroxyl group include (meth)acrylic monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate.

[0124] It is preferable to use a vinyl monomer having a hydroxyl group when an adhesive resin containing an isocyanate-based crosslinking agent is used. Specifically, it is preferable to use 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, or 6-hydroxyhexyl (meth)acrylate as the vinyl monomer having a hydroxyl group.

[0125] The vinyl monomer having a hydroxyl group is preferably used in an amount of 0.01 to 1.0 mass %, more preferably 0.03 to 0.3 mass %, based on the total amount of monomers used in the production of the acrylic polymer.

[0126] Specific examples of vinyl monomers having a carboxyl group include (meth)acrylic monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, (meth)acrylic acid dimer, crotonic acid, and ethylene oxide-modified succinic acid acrylate. Among these, acrylic acid is preferred. Specific examples of vinyl having an amide group include (meth)acrylic monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, acrylamide, and N,N-dimethylacrylamide.

[0127] The highly polar vinyl monomer is preferably used in the range of 1.5% by mass to 20% by mass, more preferably 1.5% by mass to 10% by mass, and even more preferably 2% by mass to 8% by mass, relative to the total amount of monomers used in the production of the acrylic polymer, since this allows for the formation of an adhesive layer that is well balanced in terms of cohesive strength, holding power, and adhesiveness.

[0128] The method for producing the acrylic polymer is not particularly limited and may be appropriately selected from known methods depending on the purpose, and examples thereof include a method in which a monomer is polymerized by a polymerization method such as a solution polymerization method, a bulk polymerization method, a suspension polymerization method, an emulsion polymerization method, etc. Among these, it is preferable to produce the acrylic polymer by the solution polymerization method or the bulk polymerization method.

[0129] During polymerization, if necessary, a peroxide-based thermal polymerization initiator such as benzoyl peroxide or lauroyl peroxide, an azo thermal polymerization initiator such as azobisisobutylnitrile, an acetophenone-based photopolymerization initiator, a benzoin ether-based photopolymerization initiator, a benzyl ketal-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a benzoin-based photopolymerization initiator, a benzophenone-based photopolymerization initiator, or the like can be used. In the present embodiment, the acrylic polymer may be a homopolymer or a multicomponent copolymer (a di- to hepta-component copolymer), or may be a mixture thereof.

[0130] The weight-average molecular weight of the acrylic polymer obtained by the above method is preferably 300,000 to 3,000,000, and more preferably 500,000 to 2,500,000, as measured using gel permeation chromatography (GPC) and converted into standard polystyrene.

[0131] Here, the weight average molecular weight of the acrylic polymer is measured by the GPC method using a GPC apparatus (HLC-8329GPC, manufactured by Tosoh Corporation) and is a value converted into standard polystyrene. The measurement conditions are as follows. [Measurement conditions] Sample concentration: 0.5% by mass (tetrahydrofuran (THF) solution) Sample injection volume: 100μL · Eluent: THF · Flow rate: 1.0mL / min · Measurement temperature: 40℃ - Column: TSKgel GMHHR-H(20) x 2 Guard column: TSKgel HXL-H Detector: Differential refractometer Standard polystyrene molecular weight: 10,000 to 20 million (Tosoh Corporation)

[0132] In this embodiment, the acrylic polymer is preferably a triblock copolymer represented by the following general formula (I) or a diblock copolymer represented by the below-described general formula (V). A preferred embodiment of the acrylic polymer in this embodiment will be described below.

[0133] <Triblock copolymer> The adhesive layer of the adhesive tape of the present embodiment is a compound represented by the following general formula (I): [ka] (In the above general formula (I), A, B, and C each independently represent a repeating unit, A and C each independently represent a methacrylic acid alkyl ester monomer unit, B represents an acrylic acid alkyl ester monomer unit, p, q, and r each independently represent the degree of polymerization of each monomer unit, and A and C may be methacrylic acid alkyl ester monomer units having the same or different chemical structures. In the above general formula (I), * represents a bond to another atom.)

[0134] In the above general formula (I), A and C represent repeating units different from B, and represent methacrylic acid alkyl ester monomer units. A and C are each independent and may be the same methacrylic acid alkyl ester monomer units or methacrylic acid alkyl ester monomer units having different chemical structures. In this specification, the term "methacrylic acid alkyl ester monomer unit" refers to a structural unit derived from a methacrylic acid alkyl ester monomer when a methacrylic acid alkyl ester monomer is (co)polymerized or graft polymerized, that is, a repeating unit derived from a methacrylic acid ester monomer. In the present invention, the methacrylic acid alkyl ester monomer unit is represented by the following general formula (II): [ka] (In the above general formula (II), R 3 represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R4 and the substituent R 4 represents a halogen atom, an amino group, or a cyano group.

[0135] In the above general formula (II), R 3 From the viewpoint of removability and high load retention, R is more preferably an alkyl group having 1 to 12 carbon atoms, and even more preferably an alkyl group having 1 to 4 carbon atoms. 1 The alkyl group having 1 to 12 carbon atoms may be linear, branched, or cyclic, and from the viewpoint of adhesive strength, linear or branched is preferable, and linear is more preferable. Examples of the alkyl group having 1 to 12 carbon atoms include linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, t-butyl, n-pentyl, isopentyl, hexyl, octyl, nonyl, decyl, undecyl, and dodecyl, as well as cyclic alkyl groups such as cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, and dicyclopentanyl. Examples of the alkyl group having 1 to 4 carbon atoms include linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, and t-butyl, as well as cyclic alkyl groups such as cyclobutyl. As the alkyl group having 1 to 4 carbon atoms, from the viewpoints of removability and high load retention, a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a t-butyl group are preferable, and a methyl group is more preferable.

[0136] Preferred R in the above general formula (II) 3 is any one of an alkyl group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, or a cyclobutyl group, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 2 It may be substituted with (a halogen atom, an amino group, a cyano group).

[0137] In this embodiment, for example, the methacrylic acid alkyl ester monomer is not particularly limited and includes methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, t-butyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, pentadecyl methacrylate, cyclohexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, 2-hexyldecyl methacrylate, etc. Among these, methyl methacrylate is preferred from the viewpoints of high load retention and dismantling ability.

[0138] In the above general formula (I), B represents a repeating unit different from A and C, and represents an acrylic acid alkyl ester monomer unit. In this specification, the term "acrylic acid alkyl ester monomer unit" refers to a structural unit derived from an acrylic acid alkyl ester monomer when an acrylic acid alkyl ester monomer is (co)polymerized or graft polymerized, i.e., a repeating unit derived from an acrylic acid ester monomer. In the present invention, the acrylic acid alkyl ester monomer unit is represented by the following general formula (III): [ka] (In the above general formula (III), R 5 represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 6 and the substituent R 4 represents a halogen atom, an amino group, or a cyano group.

[0139] In the above general formula (III), R 5 From the viewpoint of adhesiveness, an alkyl group having 1 to 12 carbon atoms is more preferable, and an alkyl group having 4 to 8 carbon atoms is even more preferable. The alkyl group may be linear, branched, or cyclic, and from the viewpoint of adhesiveness, a linear or branched alkyl group is preferable.

[0140] In addition, in the above general formula (III), examples of the alkyl group having 1 to 12 carbon atoms are the same as the examples of the alkyl group having 1 to 12 carbon atoms in the above general formula (I).

[0141] Preferred R in the above general formula (III) 5 is an alkyl group selected from the group consisting of n-butyl, isobutyl, t-butyl, n-pentyl, isopentyl, hexyl, octyl, cyclohexyl, cycloheptyl, and cyclooctyl, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 6 It may be substituted with (a halogen atom, an amino group, a cyano group).

[0142] In this embodiment, examples of the acrylic acid alkyl ester monomer include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, t-butyl acrylate, amyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, etc. Among these, from the viewpoint of achieving both adhesive strength and removability, n-butyl acrylate, 2-ethylhexyl acrylate, and copolymers thereof are preferred.

[0143] In the above general formula (I), p, q, and r each independently represent the degree of polymerization of each monomer unit. The values ​​of p, q, and r relate to the molecular weight, etc. p / (p+q+r) is preferably 0.02 to 0.40, and more preferably 0.05 to 0.37. q / (p+q+r) is preferably 0.20 to 0.95, and more preferably 0.25 to 0.90. r / (p+q+r) is preferably 0.02 to 0.40, and more preferably 0.05 to 0.37.

[0144] In this embodiment, the triblock copolymer has the following general formula (IV): [ka] (In the above general formula (IV), R 3 and R 7 each independently represents an alkyl group having 1 to 4 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 4 may be substituted with, and the substituent R 4 represents a halogen atom, an amino group, or a cyano group, R 5 represents an alkyl group having 4 to 8 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 6 may be substituted with, and the substituent R 6 represents a halogen atom, an amino group, or a cyano group, and p, q, and r each independently represent the degree of polymerization of each monomer unit.

[0145] In the above general formula (IV), R 1 is R in the above general formula (II). 3 In the above general formula (IV), R 5 is R in the above general formula (III). 5 In the above general formula (IV), R 7 is R in the above general formula (II). 3 In the above general formula (IV), p, q, and r can be the same as p, q, and r in the above general formula (I). 3 and R 7 may be the same or different.

[0146] In this embodiment, when the triblock copolymer is represented by the above general formula (IV), R 3 is preferably selected from the group consisting of linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, and t-butyl, and a cyclobutyl group; R 5is preferably selected from the group consisting of methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, t-butyl, n-pentyl, isopentyl, hexyl, octyl, nonyl, decyl, or undecyl; R 7 is preferably selected from the group consisting of linear or branched alkyl groups, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, and the like, and a cyclobutyl group, and it is preferable that p / (p+q+r) is 0.02 to 0.40, q / (p+q+r) is 0.20 to 0.95, and r / (p+q+r) is 0.02 to 0.40.

[0147] In the triblock copolymer of the present invention, it is preferable that A and C in the general formula (I) are the same. Specifically, when the triblock copolymer has a repeating unit represented by the above general formula (IV), R 1 and R 5 and are the same group, p / (p+q+r) is 0.02 to 0.40, q / (p+q+r) is 0.20 to 0.95, and r / (p+q+r) is 0.02 to 0.40. In a triblock copolymer having a repeating unit represented by the above general formula (I), when A and C are the same (ABA type triblock copolymer), a higher elastic modulus can be ensured, and therefore it is easier to ensure adhesive strength with excellent high load retention, removability over time, and storage stability.

[0148] --Molecular weight-- The triblock copolymer preferably has a weight average molecular weight Mw of 50,000 to 300,000, and a number average molecular weight Mn of 50,000 to 300,000. More preferably, the triblock copolymer has a weight average molecular weight Mw of 100,000 to 250,000, and a number average molecular weight Mn of 100,000 to 250,000, and even more preferably, the triblock copolymer has a weight average molecular weight Mw of 130,000 to 230,000, and a number average molecular weight Mn of 130,000 to 230,000. It is preferable that the weight average molecular weight Mw of the triblock copolymer is within the above range from the viewpoints of adhesion, removability and high load retention, and it is preferable that the number average molecular weight Mn of the triblock copolymer is within the above range from the viewpoints of adhesion, removability and high load retention. Here, the weight average molecular weight Mw and number average molecular weight Mn of the triblock polymer are measured by the GPC method using a GPC apparatus (HLC-8329GPC, manufactured by Tosoh Corporation) and are values ​​converted into standard polystyrene. The measurement conditions are as follows: -Measurement conditions- Sample concentration: 0.5% by mass (tetrahydrofuran (THF) solution) Sample injection volume: 100μL · Eluent: THF · Flow rate: 1.0mL / min · Measurement temperature: 40℃ - Column: TSKgel GMHHR-H(20) x 2 Guard column: TSKgel HXL-H Detector: Differential refractometer Standard polystyrene molecular weight: 10,000 to 20 million (Tosoh Corporation)

[0149] --stereoregularity-- The triblock copolymer and / or a partial structure (e.g., a block) of the triblock copolymer preferably has stereoregularity (tacticity). Specifically, the triblock copolymer and / or a partial structure (e.g., a block) of the triblock copolymer may have any of isotactic, syndiotactic, and atactic stereoregularity, or may have a plurality of blocks having any of these stereoregularities.

[0150] A preferred embodiment of the triblock copolymer is represented by the formula (I) "-(A) p The syndiotacticity of the polymer block in the -" portion preferably exhibits a ratio of rr triads of 65% or more, and more preferably the ratio of rr triads is 75 to 95%. A preferred embodiment of the triblock copolymer is represented by the formula (I) "-(C) r The syndiotacticity of the polymer block in the -" portion preferably exhibits a ratio of rr triads of 65% or more, and more preferably the ratio of rr triads is 75 to 95%. A preferred embodiment of the triblock copolymer is represented by the formula (I) "-(B) q The polymer block of the "-" portion preferably exhibits atacticity.

[0151] The triblock copolymer has a ratio of rr triads of 65% or more "-(A) p When the composition contains a polymer block of the -" portion, the effect of providing good removability and holding power at high temperatures is achieved.

[0152] Generally, the syndiotacticity of a polymer is expressed by the ratio of a chain (triad) consisting of three monomer units that is rr. In this specification, it is calculated by NMR measurement of the polymer. Specifically, 13 The signal peaks that represent the arrangement of triads in C-NMR vary depending on the conditions such as the type of polymer, the measurement solvent, and the measurement temperature, so it is necessary to identify and quantify the signals according to the respective measurement conditions. In this specification, the samples dissolved in deuterated chloroform are measured at 50°C.

[0153] Preferred forms of the triblock copolymer include polymethyl methacrylate block-polyn-butyl acrylate block-polymethyl methacrylate, polyethyl methacrylate block-polyn-butyl acrylate block-polyethyl methacrylate, polypropyl methacrylate block-polyn-butyl acrylate block-polypropyl methacrylate, polymethyl methacrylate block-polyt-butyl acrylate block-polymethyl methacrylate, polymethyl methacrylate block-polypropyl acrylate block-polymethyl methacrylate, and the like.

[0154] The triblock copolymer has an overall molecular weight distribution, in terms of the ratio of weight average molecular weight / number average molecular weight, preferably in the range of 1.0 to 2.3, and more preferably in the range of 1.00 to 1.50.

[0155] In the present embodiment, when A and C in the general formula (I) are different repeating units, the "-(A) p Total weight of polymer blocks of "-" part (relevant "-(A)" p The total weight of the polymer blocks of "-" is referred to as a.) and "-(B) q Total weight of polymer blocks of "-" part (said "-(B) q The total weight of the polymer blocks in the -" portion is referred to as b. From the viewpoint of adhesive properties, the mass ratio of a / b is preferably within the range of 2 / 98 to 67 / 33, and more preferably within the range of 5 / 95 to 60 / 40.

[0156] In the present embodiment, when A and C in the general formula (I) are different repeating units, the "-(C)" contained in the molecule of the triblock copolymer r Total weight of polymer blocks of "-" part (relevant "-(C)" r The total weight of the polymer blocks of "-" is referred to as c. q The ratio of the "-" portion to the total weight of the polymer blocks, c / b, is preferably within the range of 2 / 98 to 67 / 33, and more preferably within the range of 5 / 95 to 60 / 40, from the viewpoint of adhesive properties.

[0157] In the present embodiment, when A and C in the general formula (I) are the same repeating unit, the "-(A)" contained in the molecule of the triblock copolymer p The polymer block of the -" portion and the -(C) r - Total weight of polymer blocks in "-(A)" p The polymer block of the -" portion and the -(C) r The total weight of the polymer blocks of "-" is referred to as d.) and "-(B) qFrom the viewpoint of adhesive properties, the ratio of the "-" portion to the total weight of the polymer blocks (referred to as b) is preferably within the range of 5 / 95 to 80 / 20, and more preferably within the range of 10 / 90 to 75 / 25, in terms of the mass ratio d / b.

[0158] The triblock copolymer may be modified, if necessary, with a functional group such as a hydroxyl group, a carboxyl group, an acid anhydride group, an amino group, or a trimethoxysilyl group in the molecular side chain or at the molecular main chain terminal, as long as the effect of the present invention is not impaired.

[0159] --Method of manufacturing triblock copolymer-- The method for producing the triblock copolymer is not particularly limited and can be appropriately selected from conventionally known production methods, for example, a method for sequentially polymerizing a block copolymer by an anionic living polymerization method, a cationic living polymerization method, etc. In addition, when the triblock copolymer has stereoregularity (for example, syndiotacticity), a known method using an organometallic complex may be used.

[0160] As an example of a method for producing the triblock copolymer, the triblock copolymer can be produced by a technique comprising sequentially polymerizing a methacrylic acid alkyl ester monomer as a main component and a monomer mainly composed of an acrylic acid alkyl ester monomer and / or a methacrylic acid alkyl ester monomer as a main component in an inert polymerization solvent using a polymerization initiator so as to obtain a desired block bonding order.

[0161] In the present embodiment, one aspect of the method for producing the triblock copolymer is to first polymerize a methacrylic acid alkyl ester monomer in a polymerization solvent using a polymerization initiator by an anionic living polymerization method to obtain a polymethacrylic acid alkyl ester block having a living active end ("-(A)" in general formula (I) pSecondly, an alkyl methacrylate-alkyl acrylate diblock copolymer having a living active end (corresponding to the "-(A)" portion in general formula (I)) is formed by polymerizing an alkyl acrylate monomer from the living active end of the polyalkyl methacrylate. p -(B) q Thirdly, a part of the alkyl methacrylate-alkyl acrylate diblock copolymer having a living active end is reacted with a coupling agent to obtain a coupled alkyl methacrylate-alkyl acrylate-alkyl methacrylate triblock copolymer (corresponding to the "-(A)" part of general formula (I)). p -(B) q -(C) r ― In this case, the polymerization is terminated by reacting with a polymerization terminator such as alcohol, if necessary.

[0162] Examples of the polymerization initiator include organolithium compounds and organometallic compounds such as organolithium compounds and organometallic complexes. Examples of the organolithium compound include alkyllithium such as t-butyllithium, and compounds obtained by reacting alkyllithium with 1,1-diphenylethylene, diphenylmethane, etc. Furthermore, these organolithium compounds may be used in combination with inorganic salts such as lithium chloride, lithium salts of alkoxides such as lithium 2-(2-methoxyethoxy)ethoxide, and organoaluminum compounds such as diisobutyl(2,6-di-t-butyl-4-methylphenoxy)aluminum. The above-mentioned organometallic complexes include rare earth metal complexes having a pentamethylcyclopentadienyl group as a ligand, such as bis(pentamethylcyclopentadienyl)samarium methyltetrahydrofuranate, bis(pentamethylcyclopentadienyl)yttrium methyltetrahydrofuranate, etc. Furthermore, these organometallic complexes may be used in combination with alkylaluminums such as trimethylaluminum.

[0163] Examples of the polymerization solvent that can be used include hydrocarbon solvents such as benzene, toluene, and xylene; halogenated hydrocarbon solvents such as chloroform, methylene chloride, and carbon tetrachloride; and ether solvents such as tetrahydrofuran and diethyl ether. A suitable example of the triblock copolymer according to this embodiment is a polymer containing 90 to 99 mass % of n-butyl acrylate monomer units.

[0164] <Other adhesive resins> The adhesive layer of the adhesive tape of this embodiment preferably contains a triblock copolymer having a repeating unit represented by the general formula (I) as an adhesive resin. If necessary, the adhesive layer may further contain a diblock copolymer, an acrylic adhesive resin, a rubber-based adhesive resin, other adhesive resins, etc. as an adhesive resin other than the triblock copolymer. Also, the adhesive layer may contain a diblock copolymer, an acrylic adhesive resin, a rubber-based adhesive resin, other adhesive resins, etc. instead of the triblock copolymer. In addition, in the adhesive layer of the adhesive tape of this embodiment, the triblock copolymer preferably accounts for 50 to 100 mass % of the entire adhesive resin, and more preferably 70 to 100 mass % of the triblock copolymer. When the content of the triblock copolymer in the adhesive resin used in the adhesive layer is within the above range, it is easy to achieve both adhesiveness, dismantling ability, and high load retaining strength.

[0165] --Diblock copolymer-- The adhesive layer of the adhesive tape of the present embodiment is a compound represented by the following general formula (V): [ka] (In the above general formula (V), D and E each independently represent a repeating unit, D represents a methacrylic acid alkyl ester monomer unit, E represents an acrylic acid alkyl ester monomer unit, and s and t each independently represent the degree of polymerization of each monomer unit. In the above general formula (V), * represents a bond to another atom.) In the adhesive layer of the adhesive tape of this embodiment, the diblock copolymer preferably accounts for 0 to 40 mass %, and more preferably 0 to 20 mass %, of the entire adhesive resin. When the content of the diblock copolymer in the adhesive resin used in the adhesive layer is within the above range, it is easy to achieve both adhesiveness, dismantling ability, and high load retaining strength. In addition, in the present embodiment, when a triblock copolymer and a diblock copolymer are used in combination as the adhesive resin, it becomes easier to ensure high elastic modulus and initial adhesion, and therefore it becomes easier to ensure high load retention, removability over time, and initial adhesion. In particular, when the adhesive tape is pulled, the filler such as acrylic modified silicone in the adhesive layer can be maintained in a state exposed to the surface for a long period of time, and this, combined with the effect of the filler, produces an excellent synergistic effect. The methacrylic acid alkyl ester monomer unit and the acrylic acid alkyl ester monomer unit in the above general formula (V) can have the same form as the methacrylic acid alkyl ester monomer unit and the acrylic acid alkyl ester monomer unit in the above general formula (I). The diblock copolymer has the following general formula (VI): [ka] (In the above general formula (VI), R 8 represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 9 and the substituent R 9 represents a halogen atom, an amino group, or a cyano group; R 10 represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 11and the substituent R 11 represents a halogen atom, an amino group, or a cyano group, and s and t each independently represent the degree of polymerization of each monomer unit.

[0166] In the above general formula (VI), R 8 is R in the above general formula (II). 3 In the above general formula (VI), R 10 is R in the above general formula (III). 5 In the above general formula (VI), s and t can have the same configuration as p and q in the above general formula (I).

[0167] In this embodiment, the diblock copolymer preferably has a weight average molecular weight Mw of 50,000 to 300,000 and a number average molecular weight Mn of 50,000 to 300,000. The weight average molecular weight can be measured using the method for measuring the weight average molecular weight of the triblock copolymer in the present invention.

[0168] In the above general formula (VI), s and t each independently represent the degree of polymerization of each monomer unit. The values ​​of s and t relate to the molecular weight, etc. s / (s+t) is preferably 0.01 to 0.99, more preferably 0.1 to 0.9. t / (s+t) is preferably 0.01 to 0.99, more preferably 0.1 to 0.9.

[0169] In the present embodiment, when a diblock copolymer and a triblock copolymer are used in combination, the content of the diblock copolymer is not particularly limited and can be appropriately selected according to the purpose. In the present embodiment, the diblock copolymer is preferably contained in an amount of 0 to 100 parts by mass, more preferably 1 to 50 parts by mass, and even more preferably 10 to 50 parts by mass, per 100 parts by mass of the triblock copolymer. When the content of the tackifier resin in the adhesive layer is within the above range, adhesion to the adherend is easily ensured.

[0170] The acrylic adhesive resin preferably contains a tackifier resin in order to improve adhesion to the adherend and surface adhesive strength. The tackifier resin contained in the acrylic adhesive resin is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the softening point is 30°C to 180°C, and more preferably 70°C to 140°C in order to form an adhesive layer with high adhesive performance. When a (meth)acrylate-based tackifier resin is used, it is preferable that the glass transition temperature is 30°C to 200°C, and more preferably 50°C to 160°C.

[0171] Specific examples of the tackifier resin contained in the acrylic adhesive resin include rosin-based tackifier resin, polymerized rosin-based tackifier resin, polymerized rosin ester-based tackifier resin, rosin phenol-based tackifier resin, stabilized rosin ester-based tackifier resin, disproportionated rosin ester-based tackifier resin, hydrogenated rosin ester-based tackifier resin, terpene-based tackifier resin, terpene phenol-based tackifier resin, petroleum resin-based tackifier resin, (meth)acrylate-based tackifier resin, etc. These may be used alone or in combination of two or more. Among these, the tackifier resin is preferably polymerized rosin ester-based tackifier resin, rosin phenol-based tackifier resin, disproportionated rosin ester-based tackifier resin, hydrogenated rosin ester-based tackifier resin, terpene phenol-based resin, or (meth)acrylate-based resin.

[0172] The amount of tackifier resin used is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable to use it in the range of 5 parts by mass to 65 parts by mass per 100 parts by mass of the acrylic polymer, and it is more preferable to use it in the range of 8 parts by mass to 55 parts by mass, as this makes it easier to ensure adhesion to the adherend. In addition, at least in the third adhesive layer, preferably in the adhesive layers on both sides adjacent to the foam layer (the third adhesive layer in the first embodiment, and the second adhesive layer, the third adhesive layer and the fourth adhesive layer in the second, third and fourth embodiments described below), it is further preferable to use a tackifier resin in an amount in the range of 5 parts by mass to 40 parts by mass per 100 parts by mass of the acrylic polymer.

[0173] It is preferable to use an acrylic adhesive resin that contains a crosslinking agent in order to further improve the cohesive strength of the adhesive layer.

[0174] The crosslinking agent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, metal chelate-based crosslinking agents, and aziridine-based crosslinking agents. These may be used alone or in combination of two or more. Among these, the crosslinking agent is preferably a type that is mixed after the production of the acrylic polymer and promotes a crosslinking reaction, and it is more preferable to use an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent that is highly reactive with the acrylic polymer.

[0175] Examples of isocyanate crosslinking agents include tolylene diisocyanate, triphenylmethane isocyanate, naphthylene-1,5-diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and trimethylolpropane-modified tolylene diisocyanate. These may be used alone or in combination of two or more. Among these, trifunctional polyisocyanate compounds such as tolylene diisocyanate and its trimethylolpropane adduct, and triphenylmethane isocyanate are particularly preferred.

[0176] As an index of the degree of crosslinking, the gel fraction value obtained by measuring the insoluble portion after immersing the adhesive layer in toluene for 24 hours is used. The gel fraction of the adhesive layer of this embodiment is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10% by mass to 70% by mass, more preferably 25% by mass to 65% by mass, and even more preferably 35% by mass to 60% by mass in order to obtain an adhesive layer having both good cohesiveness and adhesiveness.

[0177] The gel fraction refers to a value measured by the following method. A pressure-sensitive adhesive composition containing a pressure-sensitive adhesive resin and, if necessary, additives is applied to a release sheet so that the thickness after drying is 50 μm, and the adhesive composition is dried at 100° C. for 3 minutes and aged at 40° C. for 2 days, and cut into a 50 mm square to be used as a sample. Next, the mass (G1) of the sample before immersion in toluene is measured in advance, and the toluene-insoluble portion of the sample after immersion in a toluene solution at 23° C. for 24 hours is separated by filtering with a 300 mesh wire net, and the mass (G2) of the residue after drying at 110° C. for 1 hour is measured, and the gel fraction is calculated according to the following formula (4). The mass (G3) of the conductive fine particles in the sample is calculated from the mass (G1) of the sample and the composition of the pressure-sensitive adhesive composition. Gel fraction (mass%) = (G2-G3) / (G1-G3) × 100 Formula (4)

[0178] --Rubber-based adhesive resin-- The rubber-based adhesive resin usable in the adhesive layer of the present embodiment is not particularly limited, and examples thereof include rubber materials that can be generally used as adhesive resins (e.g., synthetic rubber-based adhesive resins or natural rubber-based adhesive resins, etc.). The rubber material may contain additives such as tackifier resins as necessary.

[0179] Specific examples of the rubber material include block copolymers of aromatic vinyl compounds and conjugated diene compounds. As the block copolymer, styrene-based resins such as styrene-isoprene copolymer, styrene-isoprene-styrene copolymer, styrene-isoprenebutadiene-styrene copolymer, styrene-butadiene-styrene copolymer, styrene-ethylene-butylene copolymer, styrene-ethylene-propylene copolymer, and hydrogenated products thereof are preferred. The rubber material may be used alone or in combination of two or more. Among these, it is more preferred to use two or more styrene-based resins in combination, since it can impart excellent adhesive properties and holding power to the adhesive tape. In particular, it is preferred to use a mixture of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer.

[0180] The styrene resin may be, for example, a resin having a single structure such as a linear structure, a branched structure, or a multi-branched structure, or may be a mixture of resins having different structures. When the styrene resin having a large amount of linear structure is used in the adhesive layer, the adhesive tape has excellent adhesive performance. On the other hand, a resin having a branched or multi-branched structure and having a styrene block at the molecular end can form a pseudo-crosslinked structure, and therefore exhibits excellent cohesive force, and can impart high holding power to the adhesive layer. For this reason, it is preferable to mix and use the styrene resin used as the adhesive resin according to the required characteristics. The styrene resin preferably contains the structural unit represented by the following general formula (3) in a range of 10% by mass to 80% by mass, more preferably 12% by mass to 60% by mass, even more preferably 15% by mass to 40% by mass, and particularly preferably 17% by mass to 35% by mass, based on the total mass of the styrene resin, which allows the resin to exhibit excellent adhesiveness and heat resistance. [ka]

[0181] When a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer are used in combination as the styrene-based resin used in the adhesive resin of this embodiment, the content of the styrene-isoprene copolymer relative to the total mass of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer is preferably 0% by mass to 80% by mass, more preferably 0% by mass to 77% by mass, even more preferably 0% by mass to 75% by mass, and particularly preferably 0% by mass to 70% by mass. When the content of the styrene-isoprene copolymer is within the above-mentioned preferred range, an adhesive tape that combines excellent adhesive performance and heat durability can be provided.

[0182] The weight average molecular weight (Mw) of the styrene-isoprene copolymer is preferably in the range of 10,000 to 800,000, more preferably in the range of 30,000 to 500,000, and even more preferably in the range of 50,000 to 300,000. The weight average molecular weight is a value measured using a gel permeation chromatograph (GPC) in terms of standard polystyrene. When the weight average molecular weight of the styrene-isoprene copolymer is within the above range, it is possible to ensure heat flowability or compatibility when diluted with a solvent, which is preferable in that an adhesive tape having heat durability can be obtained while ensuring good workability in the production process.

[0183] The weight average molecular weight (Mw) of the styrene-isoprene copolymer by GPC is measured using a GPC apparatus (SC-8020, manufactured by Tosoh Corporation) and is a value converted into standard polystyrene. The measurement conditions are as follows: -Measurement conditions- Sample concentration: 0.5% by mass (THF (tetrahydrofuran) solution) Sample injection volume: 100μL Eluent: THF · Flow rate: 1.0mL / min · Measurement temperature: 40℃ - Column: TSKgel® GMHHR-H(20) x 2 Guard column: TSKgel HXL-H Detector: Differential refractometer Standard polystyrene molecular weight: 10,000 to 20 million (Tosoh Corporation)

[0184] The method for producing the styrene resin used in the pressure-sensitive adhesive resin of the present embodiment is not particularly limited and can be appropriately selected from known production methods. For example, after preparing a block copolymer by an anionic living polymerization method, a coupling agent is added as necessary and reacted to produce the target styrene resin. The method for producing a styrene-isoprene copolymer, which is a preferred example of the styrene-based resin, is not particularly limited and may be appropriately selected from known production methods, such as a method for sequentially polymerizing a styrene block and an isoprene block by an anionic living polymerization method.

[0185] Furthermore, the method for producing a styrene-isoprene-styrene copolymer, which is a preferred example of the styrene-based resin, is not particularly limited and can be appropriately selected from known production methods, such as a method of sequentially polymerizing a styrene block and an isoprene block by an anionic living polymerization method, or a method of producing a block copolymer having a living active end, and then reacting it with a coupling agent to produce a coupled block copolymer.

[0186] The method for producing the mixture of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from known production methods. For example, the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer produced by the above method can be mixed by a known mixing means.

[0187] Furthermore, in another method for producing the mixture of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer, they may be produced simultaneously as a mixture in one polymerization step. A more specific example of a method for producing the mixture of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer includes the following first to fourth steps using an anionic living polymerization method. The first step is a step of polymerizing a styrene monomer in a polymerization solvent using an anionic polymerization initiator to form a polystyrene block having a living active terminal. The second step is a step of polymerizing isoprene from the living active end of the polystyrene block to obtain a styrene-isoprene diblock copolymer having a living active end. The third step is a step of reacting a part of the styrene-isoprene diblock copolymer having a living active end with a coupling agent to form a coupled styrene-isoprene-styrene block copolymer. The fourth step is a step of deactivating the living active ends of the remaining styrene-isoprene diblock copolymer using a polymerization terminator to form a styrene-isoprene diblock copolymer.

[0188] The tackifier resin used in combination with the rubber-based adhesive resin is not particularly limited and can be appropriately selected depending on the purpose. For example, it is preferable to use a tackifier resin having a softening point of 80° C. or higher. This makes it possible to provide an adhesive tape that has both excellent initial adhesion and heat durability.

[0189] The tackifier resin used in combination with the rubber-based adhesive resin is preferably a resin that is solid at room temperature (23°C). Specific examples of the tackifier resin include petroleum resin, polymerized rosin resin, terpene resin, rosin resin, terpene-phenol resin, styrene resin, coumarone-indene resin, xylene resin, or phenol resin. Examples of the petroleum resin include C5-based petroleum resin, C9-based petroleum resin, C5 / C9-based petroleum resin, and alicyclic petroleum resin. These resins may be used alone or in combination of two or more. Among these, the tackifier resin used in combination with the rubber-based adhesive resin is preferably a combination of C5-based petroleum resin and polymerized rosin resin, from the viewpoint of achieving both better initial adhesion and heat durability. The petroleum resin is highly compatible with the styrene monomer unit represented by the general formula (3) constituting the styrene-based resin, and therefore can further improve the initial adhesive strength and heat durability of the pressure-sensitive adhesive tape.

[0190] Examples of the C5 petroleum resin include the Escorez series (Escorez 1202, Escorez 1304, or Escorez 1401) manufactured by ExxonMobil Corporation, Wingtac 95 manufactured by The Goodyear Tire & Rubber Company, the Quinton series (Quinton K100, Quinton R100, or Quinton F100) manufactured by Zeon Corporation, and PicoTac 95 or PicoPair 100 manufactured by Rika Hercules Corporation.

[0191] Examples of the C9-based petroleum resins include the Nippon Oil Neopolymer series manufactured by JX Nippon Oil & Energy Corporation (Nippon Oil Neopolymer L-90, Nippon Oil Neopolymer 120, Nippon Oil Neopolymer 130, Nippon Oil Neopolymer 140, Nippon Oil Neopolymer 150, Nippon Oil Neopolymer 170S, Nippon Oil Neopolymer 160, Nippon Oil Neopolymer E-100, Nippon Oil Neopolymer E-130, Nippon Oil Neopolymer 130S, or Nippon Oil Neopolymer S), and Petokol (registered trademark) manufactured by Tosoh Corporation.

[0192] The C5 / C9 petroleum resin may be a copolymer of a C5 petroleum resin and a C9 petroleum resin. Specific examples of the C5 / C9 petroleum resin include Escoretz 2101 manufactured by Exxon Mobil Corporation, Quinton G115 manufactured by Zeon Corporation, and Hercotac 1149 manufactured by Rika Hercules Corporation.

[0193] The alicyclic petroleum resin can be obtained by hydrogenating a C9 petroleum resin, and examples thereof include Escoretz 5300 manufactured by Exxon Mobil Corporation, Alcon P-100 manufactured by Arakawa Chemical Industries Co., Ltd., and Regalite R101 manufactured by Rika Hercules Co., Ltd.

[0194] The amount of the tackifier resin used in combination with the rubber-based adhesive resin is not particularly limited and can be appropriately selected depending on the purpose. The tackifier resin is preferably used in the range of 0% to 100% by mass, more preferably in the range of 0% to 70% by mass, even more preferably in the range of 0% to 50% by mass, and particularly preferably in the range of 0% to 30% by mass, relative to the total amount (100% by mass) of the components constituting the rubber-based adhesive resin. When the tackifier resin is used within the preferred range, the adhesion at the interface between the adhesive layer and the base layer is improved, and the adhesive tape is easily able to have both excellent breaking elongation and heat durability.

[0195] The amount of the tackifier resin having a softening point of 80° C. or higher used is not particularly limited and can be appropriately selected depending on the purpose. For example, the tackifier resin having a softening point of 80° C. or higher is preferably used in the range of 3% by mass to 100% by mass, more preferably in the range of 5% by mass to 80% by mass, relative to the total amount of the styrene-based resin. When emphasis is placed on the viewpoint of providing a pressure-sensitive adhesive tape that combines even more excellent adhesiveness and excellent heat durability, it is particularly preferable to use the tackifier resin in the range of 5% by mass to 80% by mass.

[0196] Furthermore, for the purpose of obtaining application property or initial adhesion in a constant temperature environment, a tackifier resin having a softening point of 80° C. or higher may be used in combination with a tackifier resin having a softening point of −5° C. or lower. The tackifier resin having a softening point of −5° C. or lower is not particularly limited and can be appropriately selected from known tackifier resins depending on the purpose. For example, it is preferable to use a tackifier resin that is liquid at room temperature (20° C. to 27° C.).

[0197] Specific examples of tackifier resins having a softening point of -5°C or less include process oils, and liquid rubbers such as polyester and polybutene. These liquid rubbers may be used alone or in combination of two or more. From the viewpoint of exerting even better initial adhesion, it is preferable to use polybutene as the tackifier resin having a softening point of -5°C or less.

[0198] The tackifier resin having a softening point of -5°C or lower preferably occupies a range of 0 to 40% by mass, and more preferably 0 to 30% by mass, relative to the total amount (100% by mass) of the tackifier resin.

[0199] Furthermore, the tackifier resin having a softening point of -5°C or less is preferably used in a range of 0% by mass to 40% by mass relative to the total amount (100% by mass) of the styrene-based resin used in the adhesive resin, and more preferably in a range of 0% by mass to 30% by mass when emphasis is placed on improving the initial adhesive strength, having good adhesiveness, and exhibiting sufficient heat durability.

[0200] The mass ratio of the tackifier resin having a softening point of 80° C. or higher to the tackifier resin having a softening point of −5° C. or lower is not particularly limited and can be appropriately selected depending on the purpose. The mass ratio of the tackifier resin having a softening point of 80° C. or higher to the tackifier resin having a softening point of −5° C. or lower, expressed as [mass of the tackifier resin having a softening point of 80° C. or higher / mass of the tackifier resin having a softening point of −5° C. or lower], is preferably used in the range of 5 to 50, and more preferably in the range of 10 to 30 when emphasis is placed on the viewpoint of obtaining a pressure-sensitive adhesive tape that combines excellent initial adhesion and excellent holding power.

[0201] The mass ratio of the styrene resin to the tackifier resin used in combination with the rubber-based adhesive resin is not particularly limited and can be appropriately selected according to the purpose. For example, the mass ratio of the styrene resin to the tackifier resin, expressed as [styrene resin / tackifier resin used in combination with the rubber-based adhesive resin], is preferably used in the range of 0.5 to 10.0, and when the viewpoint of improving the initial adhesive strength and obtaining excellent heat durability is emphasized, it is more preferably used in the range of 0.6 to 9.0. In addition, the mass ratio [styrene resin / tackifier resin used in combination with the rubber-based adhesive resin] is preferably larger than 1, for example, in order to prevent peeling caused by the repulsive force of the adhesive tape when it is attached to a curved surface of an adherend (repulsion resistance).

[0202] -Other ingredients- Other components contained in the adhesive layer of the present embodiment are not particularly limited and can be appropriately selected within a range that does not impair the properties of the adhesive tape. For example, polymer components other than the adhesive resin, crosslinking agents, antiaging agents, ultraviolet absorbers, fillers, polymerization inhibitors, surface conditioners, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, plasticizers, softeners, flame retardants, metal deactivators, silica beads, organic beads and other additives; silicon oxide, aluminum oxide, titanium oxide, zirconia, antimony pentoxide and other inorganic fillers. These other components may be used alone or in combination of two or more. The content of other components in the adhesive layer can be appropriately selected within a range that does not impair the properties of the adhesive tape.

[0203] -Other adhesive resins- In this embodiment, in addition to the above-mentioned adhesive resins, mixed adhesive resins such as acrylic mixed adhesives, rubber mixed adhesives, urethane mixed adhesives, adhesive compositions, adhesives, or adhesive resins, which will be described below, may be used as the adhesive resin. (Acrylic mixed adhesive) The mixed pressure-sensitive adhesive may be an acrylic mixed pressure-sensitive adhesive containing an acrylic polymer as a base resin from the viewpoints of adhesive properties (e.g., shear adhesive strength), molecular design, stability over time, etc. In this specification, the term "base resin" refers to the main component of the resin components contained in the mixed pressure-sensitive adhesive (e.g., a component contained in an amount of more than 50 mass%).

[0204] (Acrylic polymer) The acrylic polymer is preferably a polymer of a monomer raw material that contains, for example, an alkyl (meth)acrylate as a main monomer and may further contain a subcomponent monomer copolymerizable with the main monomer, where the main monomer refers to a component that accounts for more than 50% by mass of the total monomer components in the monomer raw material.

[0205] In this embodiment, as the alkyl(meth)acrylate, for example, a compound represented by the following general formula (4) can be suitably used. [ka] (R in the above formula (4) 13 represents a hydrogen atom or a methyl group. 14 is a chain alkyl group having 1 to 20 carbon atoms (hereinafter, this range of carbon atoms may be expressed as "C1-20"). From the viewpoint of the storage elastic modulus of the adhesive resin, R in the above general formula (4) 14is preferably an alkyl (meth)acrylate in which R is a chain alkyl group of C1-14 (e.g., C2-10, more preferably, C4-8), 13 is a hydrogen atom and R 14 More preferred is an alkyl acrylate in which R is a C4-8 chain alkyl group. 14 The alkyl (meth)acrylate having a C1-20 chain alkyl group may be used alone or in combination of two or more. Preferred alkyl (meth)acrylates include n-butyl acrylate and 2-ethylhexyl acrylate. From the viewpoints of adhesive properties and prevention of adhesive residue, n-butyl acrylate is more preferred.

[0206] The blending ratio of the main monomer in the total monomer components is preferably 70% by mass or more (e.g., 85% by mass or more, more preferably 90% by mass or more). The upper limit of the blending ratio of the main monomer is not particularly limited, but is preferably 99.5% by mass or less (e.g., 99% by mass or less).

[0207] The monomer of the minor component having copolymerizability with the alkyl (meth)acrylate, which is the monomer of the main component, is useful for introducing a crosslinking point into the acrylic polymer or for increasing the cohesive strength of the acrylic polymer. As the monomer of the minor component, for example, one or more of functional group-containing monomers such as a carboxyl group-containing monomer, a hydroxyl group-containing monomer, an acid anhydride group-containing monomer, an amide group-containing monomer, an amino group-containing monomer, a keto group-containing monomer, a monomer having a nitrogen atom-containing ring, an alkoxysilyl group-containing monomer, an imide group-containing monomer, and an epoxy group-containing monomer can be used. For example, from the viewpoint of improving the cohesive strength, an acrylic polymer in which a carboxyl group-containing monomer and / or a hydroxyl group-containing monomer is copolymerized as the monomer of the minor component is preferred. Examples of suitable examples of the carboxyl group-containing monomer include acrylic acid and methacrylic acid. Examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, as well as unsaturated alcohols. Among these, hydroxyalkyl (meth)acrylates are preferred, with 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate being more preferred.

[0208] The amount of the monomer of the subcomponent is not particularly limited, and may be appropriately selected so as to realize the desired cohesive force. In general, from the viewpoint of achieving a good balance between adhesive force and cohesive force, the amount of the monomer of the subcomponent is suitably 0.5% by mass or more, preferably 1% by mass or more, of the total monomer components forming the acrylic polymer. The amount of the monomer of the subcomponent is suitably 30% by mass or less, preferably 10% by mass or less (e.g., 5% by mass or less) of the total monomer components. When a hydroxyl group-containing monomer is copolymerized in the acrylic polymer, the content of the hydroxyl group-containing monomer is preferably in the range of about 0.001 to 10% by mass (e.g., 0.01 to 5% by mass, preferably 0.05 to 2% by mass) of the total monomer components used in the synthesis of the acrylic polymer. This allows the realization of a pressure-sensitive adhesive resin with a higher level of balance between adhesive force and cohesive force.

[0209] The acrylic polymer of the present disclosure may be copolymerized with monomers (other monomers) other than those mentioned above, within a range that does not significantly impair the effects of the present invention. The other monomers can be used for the purpose of, for example, adjusting the glass transition temperature of the acrylic polymer, adjusting the adhesive performance (for example, peelability), and the like. For example, as monomers that can improve the cohesive force of the adhesive resin, there can be mentioned sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, cyano group-containing monomers, vinyl esters, aromatic vinyl compounds, and the like. The other monomers may be used alone or in combination of two or more. Among them, vinyl esters are preferred examples. Specific examples of the vinyl esters include vinyl acetate, vinyl propionate, vinyl laurate, and the like. Among them, vinyl acetate is preferred. The content of the other monomers is preferably about 30% by mass or less (for example, 0.01 to 30% by mass, more preferably 0.1 to 10% by mass) of the total monomer components used in the synthesis of the acrylic polymer.

[0210] The copolymer composition of the acrylic polymer is preferably designed so that the glass transition temperature (Tg) of the polymer is −15° C. or lower (e.g., −70° C. or higher and −15° C. or lower), more preferably −25° C. or lower (e.g., −60° C. or higher and −25° C. or lower), and even more preferably −40° C. or lower (e.g., −60° C. or higher and −40° C. or lower). It is preferable to set the Tg of the acrylic polymer to the above-mentioned upper limit or lower from the viewpoint of the impact resistance of the pressure-sensitive adhesive tape, etc.

[0211] The Tg of an acrylic polymer can be adjusted by appropriately changing the monomer composition (i.e., the type and amount ratio of the monomers used in the synthesis of the polymer). Here, the Tg of an acrylic polymer refers to a value calculated from the Fox formula shown below based on the Tg of the homopolymer of each monomer constituting the polymer and the mass fraction of the monomer (copolymerization ratio based on mass). The Fox formula, as shown below, is a relational expression between the Tg of a copolymer and the glass transition temperature Tgj of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer. 1 / Tg=Σ(Mj / Tgj) (In the above Fox formula, Tg represents the glass transition temperature (K) of the copolymer, Mj represents the mass fraction (copolymerization ratio on a mass basis) of monomer j in the copolymer, and Tgj represents the glass transition temperature (K) of a homopolymer of monomer j.) As the Tg of the homopolymer, a value described in a conventionally known literature or data is used.

[0212] In this embodiment, the following values ​​are specifically used as the Tg of the homopolymer. 2-Ethylhexyl acrylate 203.15K Butyl acrylate 218.15K Vinyl acetate 305.15K Acrylic acid 379.15K Methacrylic acid 501.15K 2-Hydroxyethyl acrylate 258.15K For the Tg of homopolymers other than those described above, the values ​​described in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989) are used. When the Tg value of the homopolymer to be used is not described in the Polymer Handbook, the value obtained by the measurement method described in, for example, JP-A-2007-51271 is used.

[0213] The method for producing the acrylic polymer is not particularly limited. As the production method, a method generally known as a polymerization method for acrylic polymers, such as a solution polymerization method, an emulsion polymerization method, a bulk polymerization method, or a suspension polymerization method, can be appropriately adopted. For example, the acrylic polymer is preferably produced by a solution polymerization method. As a monomer supply method when carrying out the solution polymerization method, a lump-sum charging method in which all monomer raw materials are supplied at once, a continuous supply (dropping) method, or a divided supply (dropping) method can be appropriately adopted. Furthermore, the polymerization temperature can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, and the like. For example, the polymerization temperature can be about 20°C to 170°C (for example, 40°C to 140°C). In addition, photopolymerization (for example, carried out in the presence of a photopolymerization initiator) carried out by irradiating light such as UV, or active energy ray irradiation polymerization carried out by irradiating active energy rays such as β rays or γ rays may be used.

[0214] The solvent (polymerization solvent) used in the solution polymerization can be appropriately selected from known organic solvents. For example, aromatic compounds (e.g., aromatic hydrocarbons) such as toluene, and aliphatic or alicyclic hydrocarbons such as ethyl acetate are preferably used.

[0215] The polymerization initiator used for polymerization can be appropriately selected from known polymerization initiators depending on the type of polymerization method. For example, one or more azo-based polymerization initiators such as 2,2'-azobisisobutyronitrile can be preferably used. Other examples of the polymerization initiator include peroxide-based initiators such as benzoyl peroxide and hydrogen peroxide; persulfates such as potassium persulfate; substituted ethane-based initiators such as phenyl-substituted ethane; and aromatic carbonyl compounds. Still other examples of the polymerization initiator include redox-based polymerization initiators obtained by combining a peroxide with a reducing agent. The above polymerization initiators may be used alone or in combination of two or more. The amount of the polymerization initiator used may be a normal amount, and may be selected from the range of about 0.005 to 1 part by mass (for example, 0.01 to 1 part by mass) relative to 100 parts by mass of the total monomer components.

[0216] The weight average molecular weight (Mw) of the base resin (preferably an acrylic polymer) in the present disclosure is not particularly limited, but is, for example, 10 × 10 4 Over 500 x 10 4 From the viewpoint of achieving a high level of balance between cohesive strength and adhesive strength, the Mw of the base resin (preferably an acrylic polymer) is preferably 10×10 4 ~150×10 4 , more preferably 20×10 4 ~110×10 4 (For example, 20×10 4 ~75×10 4 ), and more preferably 35×10 4 ~90×10 4 (For example, 35×10 4 ~65×10 4 ) range. Here, the measured value of Mw refers to a value calculated as standard polystyrene by gel permeation chromatography (GPC). As the GPC device, for example, "HLC-8320GPC" (column: TSKgelGMH-H(S), manufactured by Tosoh Corporation) can be used. The same applies to the examples described later.

[0217] (Rubber-based mixed adhesive) The adhesive resin in this embodiment may be a rubber-based mixed adhesive. A preferred embodiment of the rubber-based mixed adhesive contains a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound as a base resin. The monovinyl-substituted aromatic compound refers to a compound in which a functional group having one vinyl group is bonded to an aromatic ring. An example of the aromatic ring is a benzene ring (which may be a benzene ring substituted with a functional group (e.g., an alkyl group) that does not have a vinyl group). Specific examples of the monovinyl-substituted aromatic compound include styrene, α-methylstyrene, vinyltoluene, and vinylxylene. Specific examples of the conjugated diene compound include 1,3-butadiene and isoprene. Such block copolymers may be used alone or in combination of two or more types as the base resin.

[0218] In the block copolymer, the X block (also referred to as the hard segment or hard block) has a copolymerization ratio of the monovinyl-substituted aromatic compound (two or more kinds may be used in combination) of preferably 70% by mass or more, more preferably 90% by mass or more, and particularly preferably 100% by mass. In the block copolymer, the Y block (also referred to as the soft segment or soft block) has a copolymerization ratio of the conjugated diene compound (two or more kinds may be used in combination) of preferably 70% by mass or more, more preferably 90% by mass or more, and is substantially 100% by mass. By using such a block copolymer, a pressure-sensitive adhesive tape with higher performance can be realized.

[0219] The block copolymer is preferably a diblock polymer, a triblock polymer, a radial body, a mixture thereof, or the like. In the triblock polymer and the radial polymer, it is preferable that an X block (e.g., a styrene block) is arranged at the end of the polymer chain. The X blocks arranged at the end of the polymer chain are likely to gather together to form a domain, which forms a pseudo-crosslinked structure and improves the cohesiveness of the adhesive resin. From the viewpoint of adhesive strength (peel strength) to an adherend and repulsion resistance, the block copolymer of the present disclosure has a diblock polymer ratio of, for example, preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 65% ​​by mass or more, and particularly preferably 70% by mass or more. From the viewpoint of resistance to continuously applied stress, a diblock polymer ratio of 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less can be used. For example, it is preferable to use a block copolymer having a diblock polymer ratio of 60 to 85% by mass.

[0220] (styrene block copolymer) In a preferred embodiment of the pressure-sensitive adhesive resin of the present disclosure, the mixed pressure-sensitive adhesive is preferably a styrene-based block copolymer. As the styrene-based block copolymer, for example, the base resin preferably contains at least one of a styrene-isoprene block copolymer and a styrene-butadiene block copolymer. Of the styrene-based block copolymers contained in the pressure-sensitive adhesive resin, a form in which the proportion of the styrene-isoprene block copolymer is 70% by mass or more, a form in which the proportion of the styrene-butadiene block copolymer is 70% by mass or more, or a form in which the total proportion of the styrene-isoprene block copolymer and the styrene-butadiene block copolymer is 70% by mass or more is preferred. It is preferred that the styrene-based block copolymer is almost entirely (for example, 95 to 100% by mass) of the styrene-based block copolymer. It is preferred that the styrene-based block copolymer is almost entirely (for example, 95 to 100% by mass) of the styrene-based block copolymer. This composition makes it possible to suitably realize a pressure-sensitive adhesive tape that is excellent in repulsion resistance and well-balanced with other adhesive properties.

[0221] The styrene-based block copolymer is preferably in the form of a diblock polymer, a triblock polymer, a radial polymer, a mixture thereof, or the like. In the triblock polymer and the radial polymer, it is preferable that the styrene block is arranged at the end of the polymer chain. This is because the styrene blocks arranged at the end of the polymer chain are likely to gather together to form a styrene domain, which forms a pseudo crosslinked structure and improves the cohesion of the adhesive resin. In the styrene-based block copolymer, the upper and lower limits of the diblock polymer ratio can be the values ​​of the block copolymers mentioned above.

[0222] The styrene content of the styrene block copolymer is preferably 5 to 40% by mass based on the entirety of the styrene block copolymer. From the viewpoint of repulsion resistance and holding power, the styrene content in the styrene block copolymer is preferably 10% by mass or more, more preferably more than 10% by mass, and even more preferably 12% by mass or more. From the viewpoint of adhesive power to an adherend, a styrene block copolymer having a styrene content of 35% by mass or less (e.g., 30% by mass or less, more preferably 25% by mass or less, for example, less than 20% by mass) is preferred. For example, a styrene block copolymer having a styrene content of 12% by mass or more and less than 20% by mass is particularly preferred.

[0223] (Urethane-based mixed adhesive) The adhesive resin can be composed of a urethane-based mixed adhesive. Here, the urethane-based mixed adhesive refers to an adhesive containing a urethane-based polymer as a base resin. The urethane-based mixed adhesive is, for example, made of a urethane-based resin containing a urethane-based polymer obtained by reacting a polyol with a polyisocyanate compound as a base resin. The urethane-based polymer is not particularly limited, but an appropriate one can be adopted from various urethane-based polymers (ether-based polyurethane, ester-based polyurethane, carbonate-based polyurethane, etc.) that can function as an adhesive resin. Examples of polyols include polyether polyol, polyester polyol, polycarbonate polyol, polycaprolactone polyol, etc. Examples of polyisocyanate compounds include diphenylmethane diisocyanate, tolylene diisocyanate, hexamethylene diisocyanate, etc.

[0224] (Adhesive composition) The adhesive resin in this embodiment may be an adhesive formed from an aqueous adhesive composition, a solvent-based adhesive composition, a hot melt-type adhesive composition, or an active energy ray curable adhesive composition. The aqueous adhesive composition refers to an adhesive composition in a form containing an adhesive (adhesive layer forming component) in a solvent (aqueous solvent) mainly composed of water, and includes, for example, a composition called an aqueous dispersion type adhesive composition (a composition in which at least a part of the adhesive is dispersed in water). In addition, the solvent-based adhesive composition refers to an adhesive composition in a form containing an adhesive in an organic solvent. The present disclosure is preferably implemented in an embodiment having an adhesive formed from a solvent-based adhesive composition, from the viewpoint of emphasizing the suitable realization of adhesive properties such as shear adhesive strength.

[0225] (Acrylic Oligomer) The pressure-sensitive adhesive composition of the present disclosure may contain an acrylic oligomer. By using an acrylic oligomer, it is possible to improve the impact resistance and repulsion resistance in a well-balanced manner. In addition, when the pressure-sensitive adhesive composition is cured by irradiation with active energy rays (e.g., UV irradiation), the acrylic oligomer has the advantage that it is less likely to cause curing inhibition (e.g., polymerization inhibition of unreacted monomers) than tackifier resins such as rosin-based resins and terpene-based resins. The acrylic oligomer is a polymer containing an acrylic monomer as its constituent monomer component, and is defined as a polymer having a smaller Mw than the above-mentioned acrylic polymer.

[0226] The proportion of the acrylic monomer in the total monomer components constituting the acrylic oligomer is, for example, more than 50% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more. In a preferred embodiment, the acrylic oligomer has a monomer composition consisting essentially of acrylic monomers.

[0227] As the monomer components constituting the acrylic oligomer, the chain alkyl (meth)acrylates, functional group-containing monomers, and other monomers exemplified as the monomers usable for the acrylic polymer can be used. The above-mentioned constituent monomers may also include alicyclic hydrocarbon group-containing (meth)acrylates. As the monomer components constituting the acrylic oligomer, one or more of the various monomers exemplified above can be used.

[0228] The chain alkyl (meth)acrylate may be any of the following in the formula (II): 3 Preferably used is an alkyl(meth)acrylate having 1 to 12 carbon atoms (for example, more preferably C1-8). Suitable examples include methyl methacrylate, ethyl acrylate, n-butyl acrylate, isobutyl methacrylate, t-butyl acrylate, and 2-ethylhexyl acrylate. Of these, methyl methacrylate is more preferred.

[0229] Suitable examples of the functional group-containing monomer include monomers having a nitrogen atom-containing ring (e.g., a nitrogen atom-containing heterocycle), such as N-vinyl-2-pyrrolidone and N-acryloylmorpholine; amino group-containing monomers, such as N,N-dimethylaminoethyl (meth)acrylate; amide group-containing monomers, such as N,N-diethyl (meth)acrylamide; carboxy group-containing monomers, such as acrylic acid and methyl methacrylate; and hydroxy group-containing monomers, such as ethylhexyl acrylate.

[0230] The alicyclic hydrocarbon group-containing (meth)acrylate may be, for example, one or more (meth)acrylates containing an alicyclic hydrocarbon group having a carbon number in the range of 4 to 20. The number of carbon atoms constituting the alicyclic hydrocarbon group is preferably 5 or more (e.g., 6 or more, more preferably 8 or more) and preferably 16 or less (e.g., 12 or less, more preferably 10 or less). Examples of the alicyclic hydrocarbon group-containing (meth)acrylate include cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate. Among them, dicyclopentanyl methacrylate is more preferable.

[0231] The proportion of the alicyclic hydrocarbon group-containing (meth)acrylate in all monomer components constituting the acrylic oligomer (i.e., copolymerization proportion) is preferably about 30 to 90 mass % (e.g., 50 to 80 mass %, more preferably 55 to 70 mass %) from the viewpoint of adhesion or cohesion.

[0232] A preferred embodiment of the acrylic oligomer contains a chain alkyl (meth)acrylate and / or an alicyclic hydrocarbon group-containing (meth)acrylate as a monomer component constituting the acrylic oligomer. In this embodiment, the proportion of the chain alkyl group-containing and alicyclic hydrocarbon group-containing (meth)acrylic acid ester in the total monomer components constituting the acrylic oligomer is preferably about 80 mass% or more (for example, 90 to 100 mass%, more preferably 95 to 100 mass%). More preferably, the monomer components constituting the acrylic oligomer are substantially composed of a chain alkyl (meth)acrylate and / or an alicyclic hydrocarbon group-containing (meth)acrylate.

[0233] When the acrylic oligomer is a copolymer of a monomer mixture containing a chain alkyl (meth)acrylate and an alicyclic hydrocarbon group-containing (meth)acrylate, the composition ratio of the chain alkyl (meth)acrylate and the alicyclic hydrocarbon group-containing (meth)acrylate is not particularly limited. In a preferred embodiment, the mass ratio (M Ch ) and the mass ratio of the alicyclic hydrocarbon group-containing (meth)acrylate (M Ali ) and the mass ratio (M Ch :M Ali ) is 1:9 to 9:1, preferably 2:8 to 7:3 (for example, 3:7 to 6:4, more preferably 3:7 to 5:5).

[0234] The composition of the monomer components constituting the acrylic oligomer (i.e., polymerization composition) is not particularly limited, and the Tg of the acrylic oligomer can be set to 10°C or more and 300°C or less. Here, the Tg of the acrylic oligomer refers to a value calculated based on the composition of the monomer components constituting the acrylic oligomer in the same manner as the Tg based on the monomer composition. From the viewpoint of initial adhesiveness, the Tg of the acrylic oligomer is preferably 180°C or less (e.g., 160°C or less). Moreover, from the viewpoint of cohesiveness of the adhesive resin, the Tg is preferably 60°C or more (e.g., 100°C or more, more preferably 120°C or more).

[0235] The weight average molecular weight (Mw) of the acrylic oligomer is not particularly limited, but is, for example, 0.1×10 4 ~3×10 4 From the viewpoint of improving adhesive properties (e.g., adhesive strength or repulsion resistance), the Mw of the acrylic oligomer is about 1.5×10 4 Less than or equal to 1×10 is preferred 4 Less than 0.8×10 is preferable. 4 Less than (e.g. 0.6×10 4 From the viewpoint of the cohesiveness of the adhesive resin, the Mw is more preferably 0.2×10 4 or more (e.g. 0.3×10 4The molecular weight of the acrylic oligomer can be adjusted by using a chain transfer agent during polymerization, if necessary.

[0236] The acrylic oligomer can be formed by polymerizing its constituent monomer components. The polymerization method or polymerization mode of the acrylic oligomer is not particularly limited, and various known polymerization methods (e.g., solution polymerization, emulsion polymerization, bulk polymerization, photopolymerization, radiation polymerization, etc.) can be adopted. The type and amount of polymerization initiator (e.g., azo polymerization initiator such as AIBN) that can be used as necessary are also generally as described above, so they will not be described here.

[0237] The content of the acrylic oligomer in the pressure-sensitive adhesive composition of the present disclosure is preferably, for example, 0.5 parts by mass or more relative to 100 parts by mass of the acrylic polymer. From the viewpoint of better exerting the effect of the acrylic oligomer, the content of the acrylic oligomer is preferably 1 part by mass or more (for example, 1.5 parts by mass or more, more preferably 2 parts by mass or more). In addition, from the viewpoint of the curability of the pressure-sensitive adhesive composition or the compatibility with the acrylic polymer, the content of the acrylic oligomer is preferably less than 50 parts by mass (for example, less than 10 parts by mass), and more preferably less than 8 parts by mass (for example, less than 7 parts by mass, more preferably 5 parts by mass or less). Even with such a small amount of addition, the use of the acrylic oligomer can achieve improvement in impact resistance and repulsion resistance.

[0238] (tackifier) The adhesive resin or adhesive composition of the present disclosure may be a composition containing a tackifier. The tackifier is not particularly limited. As the tackifier, for example, various tackifier resins such as rosin-based tackifier resins, terpene-based tackifier resins, hydrocarbon-based tackifier resins, epoxy-based tackifier resins, polyamide-based tackifier resins, elastomer-based tackifier resins, phenol-based tackifier resins, or ketone-based tackifier resins can be used. The above tackifier resins may be used alone or in combination of two or more.

[0239] Specific examples of rosin-based tackifying resins include unmodified rosins such as gum rosin, wood rosin, and tall rosin (raw rosin (main component is a tricyclic diterpenoid isomer having 20 carbon atoms, called resin acid)); modified rosins obtained by modifying these unmodified rosins through hydrogenation, disproportionation, polymerization, etc. (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc.; the same applies below); and various other rosin derivatives. Specific examples of the rosin derivative include rosin esters such as compounds obtained by esterifying unmodified rosin with alcohols (i.e., esterified products of rosin) and compounds obtained by esterifying modified rosin with alcohols (i.e., esterified products of modified rosin); unsaturated fatty acid modified rosins obtained by modifying unmodified rosin or modified rosin with unsaturated fatty acid; unsaturated fatty acid modified rosin esters obtained by modifying rosin esters with unsaturated fatty acid; rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin, unsaturated fatty acid modified rosins, or unsaturated fatty acid modified rosin esters; metal salts of rosins (particularly rosin esters) such as unmodified rosin, modified rosin, and various rosin derivatives; rosin phenolic resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) with an acid catalyst and thermally polymerizing the mixture; and the like. When an acrylic polymer is used as the base resin, it is preferable to use a rosin-based tackifier resin. From the viewpoint of improving adhesive properties such as adhesive strength, it is more preferable to use two or more kinds of the above rosin-based tackifier resins that are different in type, properties (eg, softening point), etc. in combination.

[0240] Specific examples of the terpene-based tackifier resin include terpene resins such as α-pinene polymer, β-pinene polymer, and dipentene polymer; modified terpene resins obtained by modifying these terpene resins (phenol-modified, aromatic-modified, hydrogen-modified, hydrocarbon-modified, etc.); and the like. Specific examples of the modified terpene resin include terpene-modified phenolic resin, styrene-modified terpene resin, aromatic-modified terpene resin, and hydrogen-modified terpene resin. When an acrylic polymer is used as the base resin, it is preferable to use a terpene-based tackifier resin, such as a terpene-modified phenolic resin. In particular, from the viewpoint of improving adhesive properties such as adhesive strength, it is more preferable to use one or more of the above terpene-based tackifier resins (such as terpene-modified phenolic resins) that are different in type, characteristics (such as softening point) in combination.

[0241] Specific examples of hydrocarbon-based tackifying resins include various hydrocarbon resins such as aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic / aromatic petroleum resins (styrene-olefin copolymers, etc.), aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone-indene resins.

[0242] In the present disclosure, the tackifier resin preferably has a softening point (softening temperature) of about 70° C. or higher (preferably about 100° C. or higher, more preferably about 110° C. or higher). By using a pressure-sensitive adhesive resin or a pressure-sensitive adhesive composition containing a tackifier resin having various softening points as described above, a pressure-sensitive adhesive tape with better adhesive strength can be realized. Among the tackifier resins exemplified above, terpene-based tackifier resins (e.g., terpene-modified phenolic resins) and rosin-based tackifier resins (e.g., esterified products of polymerized rosin) having the above softening points can be preferably used. The upper limit of the softening point of the tackifier resin is not particularly limited, and can be, for example, about 200° C. or lower (e.g., about 180° C. or lower).

[0243] In the present embodiment, the amount of the tackifier used is not particularly limited and can be appropriately adjusted according to the desired adhesive performance (adhesive strength, etc.) The amount of the tackifier used is, for example, preferably about 10 to 100 parts by mass, more preferably 20 to 80 parts by mass, and even more preferably 30 to 60 parts by mass, based on the solid content, per 100 parts by mass of the acrylic polymer.

[0244] When the adhesive resin is composed of a rubber-based mixed adhesive, the rubber-based mixed adhesive preferably contains a high-softening point resin having a softening point of 120°C or more as a tackifier resin. The adhesive tape containing the high-softening point resin is preferable from the viewpoint of repulsion resistance or holding power. In a preferred embodiment, the high-softening point resin may contain a tackifier resin having a softening point of preferably 125°C or more, more preferably 130°C or more, even more preferably 135°C or more, and particularly preferably 140°C or more. In addition, from the viewpoint of adhesive strength to an adherend, the softening point of the high-softening point resin is usually preferably 200°C or less, more preferably 180°C or less, even more preferably 170°C or less, and particularly preferably 160°C or less.

[0245] Specific examples of the high softening point resin include terpene phenol resin, polymerized rosin, and esterified polymerized rosin. These high softening point resins may be used alone or in combination of two or more. A preferred embodiment is one in which the high softening point resin contains one or more terpene phenol resins. For example, a terpene phenol resin having a softening point of 120°C or more and 200°C or less (e.g., 120°C or more and 180°C or less, e.g., 125°C or more and 170°C or less) can be used as the high softening point resin.

[0246] The terpene phenol resin preferably has a softening point of 120° C. or higher and a hydroxyl value (OH value) of 40 mgKOH / g or higher (for example, 40 to 200 mgKOH / g, more preferably 40 to 160 mgKOH / g). When the terpene phenol resin has a hydroxyl value within the above range, a pressure-sensitive adhesive tape with higher performance can be realized. The hydroxyl value in this specification is measured by the potentiometric titration method specified in JIS K 0070:1992. As a more specific measurement method, the method described in JP 2014-55235 A can be used.

[0247] In the present disclosure, for example, the rubber-based mixed adhesive is preferably a mixed adhesive in which a high softening point resin (h1) having a hydroxyl value of 40 mgKOH / g or more and less than 80 mgKOH / g is mixed with a high softening point resin (h2) having a hydroxyl value of 80 mgKOH / g or more (e.g., 80 to 160 mgKOH / g, e.g., 80 to 140 mgKOH / g). In this case, the amount of the high softening point resin (h1) and the high softening point resin (h2) used is, for example, preferably in a mass ratio (h1:h2) range of 1:5 to 5:1, more preferably in a range of 1:3 to 3:1 (e.g., 1:2 to 2:1). An embodiment in which both the high softening point resin (h1) and the high softening point resin (h2) are terpene phenol resins is preferable.

[0248] In the present embodiment, from the viewpoint of repulsion resistance, holding power, etc., the lower limit of the content of the high softening point resin is preferably 20 parts by mass or more, 30 parts by mass or more (e.g., 35 parts by mass or more) relative to 100 parts by mass of the base resin. Also, from the viewpoint of adhesive strength, low-temperature characteristics, etc., the upper limit of the content of the high softening point resin is preferably 100 parts by mass or less, 80 parts by mass or less, 70 parts by mass or less, 60 parts by mass or less, 50 parts by mass or less) relative to 100 parts by mass of the base resin.

[0249] In the present disclosure, the rubber-based mixed adhesive may contain a low-softening point resin having a softening point of less than 120° C. instead of or in addition to the high-softening point resin. The rubber-based mixed adhesive may contain a high-softening point resin having a softening point of 120° C. or higher and a low-softening point resin having a softening point of less than 120° C.

[0250] The low softening point resin is preferably a resin having a softening point of, for example, 40° C. or higher (e.g., 60° C. or higher). When emphasis is placed on repulsion resistance or holding power, a low softening point resin having a softening point of 80° C. or higher (more preferably 100° C. or higher) and lower than 120° C. is preferred. Alternatively, a low softening point resin having a softening point of 110° C. or higher and lower than 120° C. may be used.

[0251] In this embodiment, the rubber-based mixed adhesive preferably contains at least one of a petroleum resin and a terpene resin (e.g., an unmodified terpene resin) as the low softening point resin. For example, a composition in which the main component of the low softening point resin (i.e., a component that occupies more than 50% by mass of the low softening point resin) is a petroleum resin, a terpene resin, a mixture of a petroleum resin and a terpene resin, or the like is preferred. When attaching importance to adhesive strength and compatibility, the main component of the low softening point resin is preferably a terpene resin (e.g., a β-pinene polymer). Substantially the entire amount (e.g., 95% by mass or more) of the low softening point resin may be composed of a terpene resin.

[0252] The low softening point resin is preferably a tackifier resin having a hydroxyl value of 0 or more and less than 80 mgKOH / g. The tackifier resin having a hydroxyl value of 0 or more and less than 80 mgKOH / g may be any of the above-mentioned various tackifier resins having a hydroxyl value within the above range, and may be used alone or in appropriate combination of two or more. The low softening point resin is preferably, for example, a terpene phenol resin, a petroleum resin (e.g., C5 petroleum resin), a terpene resin (e.g., β-pinene polymer), a rosin resin (e.g., polymerized rosin), a rosin derivative resin (e.g., an ester of the polymerized rosin), or the like having a hydroxyl value of 0 or more and less than 80 mgKOH / g.

[0253] When attaching importance to the adhesive strength to the adherend, the content of the low softening point resin is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of the base resin. When attaching importance to the repulsion resistance, the content of the low softening point resin is preferably 120 parts by mass or less, more preferably 90 parts by mass or less, even more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 50 parts by mass or less, and particularly preferably 40 parts by mass or less.

[0254] When the tackifier resin is a mixture containing a low softening point resin and a high softening point resin, the mass ratio of the low softening point resin: the high softening point resin is preferably 1:5 to 3:1, more preferably 1:5 to 2:1. In the present disclosure, the rubber-based mixed adhesive preferably contains more high softening point resin than low softening point resin as the tackifier resin, and for example, the mass ratio of the low softening point resin: the high softening point resin is preferably 1:1.2 to 1:5. This can realize a pressure-sensitive adhesive tape with higher performance.

[0255] In the present disclosure, the content of the tackifier resin relative to 100 parts by mass of the base resin (e.g., a rubber-based polymer) is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 40 parts by mass or more, and particularly preferably 50 parts by mass or more. In addition, when emphasis is placed on low-temperature properties (e.g., adhesive strength and impact resistance under low-temperature conditions), the content of the tackifier resin relative to 100 parts by mass of the base resin is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, even more preferably 100 parts by mass or less, and particularly preferably 80 parts by mass.

[0256] (Other added ingredients) In the present disclosure, the pressure-sensitive adhesive composition may contain a crosslinking agent as necessary. The type of crosslinking agent is not particularly limited and can be appropriately selected from known crosslinking agents. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, and metal chelate-based crosslinking agents. The crosslinking agent may be used alone or in combination of two or more. Among them, from the viewpoint of improving the cohesive force, the crosslinking agent is preferably an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent. The amount of the crosslinking agent used is not particularly limited and can be selected, for example, from the range of about 10 parts by mass or less (for example, about 0.005 to 10 parts by mass, preferably about 0.01 to 5 parts by mass) relative to 100 parts by mass of the base resin (for example, an acrylic polymer).

[0257] The pressure-sensitive adhesive composition may contain various known fillers that may be contained in the pressure-sensitive adhesive or pressure-sensitive adhesive resin. As the filler, various particulate or fibrous materials may be used. Examples of materials constituting the particulate material include metals such as copper, nickel, aluminum, chromium, iron, and stainless steel; metal oxides such as alumina, zirconia, and zinc oxide; carbides such as silicon carbide, boron carbide, and nitrogen carbide; nitrides such as aluminum nitride, silicon nitride, and boron nitride; inorganic materials such as calcium carbide, calcium carbonate, aluminum hydroxide, glass, and silica; polymers such as polystyrene, acrylic resins (e.g., polymethyl methacrylate), phenolic resins, benzoguanamine resins, urea resins, silicone resins, polyesters, polyurethanes, polyethylene, polypropylene, polyamides (e.g., nylon, etc.), polyimides, and polyvinylidene chloride; and the like. In addition, natural raw material particles such as volcanic sirasu, clay, and sand may be used as the particulate material. Furthermore, the pressure-sensitive adhesive composition may contain a particulate material having a hollow structure as the filler, that is, microballoons (e.g., hollow particles made of inorganic or organic materials) described below. Examples of microballoons used in the pressure-sensitive adhesive composition include glass balloons (e.g., hollow glass balloons), hollow balloons made of metal oxides (e.g., hollow alumina balloons), and hollow balloons made of porcelain (e.g., hollow ceramic balloons). As the fibrous material, various synthetic fiber materials or natural fiber materials can be used. These may be used alone or in combination of two or more. The amount of the filler to be added is not particularly limited and can be appropriately selected based on the purpose and use of the addition or technical common sense.

[0258] The above-mentioned adhesive composition may contain various general additives such as a leveling agent, a crosslinking assistant, a plasticizer, a softener, a colorant (dye, pigment), an antistatic agent, an antiaging agent, an ultraviolet absorber, an antioxidant, or a light stabilizer, if necessary. In addition, for example, an adhesive strength regulator such as a silicone oligomer may be added to the adhesive composition (e.g., an acrylic adhesive composition). As for such various additives, known ones can be used by a conventional method.

[0259] -Adhesive- In this embodiment, an adhesive based on a vinyl aromatic block copolymer and an adhesive resin may be used as the adhesive resin. The adhesive is preferably a block copolymer formed from at least two blocks selected from the group consisting of a polystyrene block formed mainly from vinyl aromatics (X block), preferably styrene, a diene polymer block formed mainly by polymerization of a 1,3-diene compound (Y block), such as isoprene or butadiene, and a copolymer block polymerized from both isoprene and butadiene. The block copolymer may also be partially or completely hydrogenated in the diene block. Similarly, block copolymers of vinyl aromatics and isobutylene can also be used in the adhesive. The preferred adhesive is a block copolymer and has polystyrene endblocks.

[0260] The block copolymer obtained from the X block and the Y block may contain a Y block which may be the same or different from each other. The block copolymer may have a linear XYX structure. Radial block copolymers as well as star-shaped and linear multiblock copolymers may also be used in the present embodiment. XY-block copolymers may also be used as adhesives. Any of these copolymers may be used alone or in combination of two or more kinds.

[0261] Instead of the polystyrene block, a polymer block based on another aromatic-containing homopolymer or copolymer (preferably a copolymer polymerized from a C8-C12 aromatic compound) (e.g., a polymer block polymerized from an aromatic compound having a glass transition temperature of more than 75° C.) can also be used as the X block, for example, an aromatic block polymerized from α-methylstyrene. Furthermore, the same or different A-blocks can also be contained.

[0262] In this embodiment, the X blocks are also referred to as "hard blocks". The Y blocks are also referred to as "soft blocks". This reflects the selection of polymer blocks with corresponding glass transition temperatures (X blocks at least 25°C, in particular at least 50°C, and Y blocks at most 25°C, in particular at most -25°C).

[0263] In this embodiment, the block copolymer has a polyvinyl aromatic moiety content of 10% to 35% by weight, preferably 20% to 32% by weight.

[0264] More preferably, the lower limit of the content of the vinyl aromatic block copolymer, in particular the styrene block copolymer, is at least 20 mass%, preferably at least 30 mass%, and particularly preferably at least 35 mass%, in total, relative to the total amount (100 mass%) of the adhesive.

[0265] If the proportion of vinyl aromatic block copolymer is too low, the result will be an adhesive with relatively low cohesive strength.

[0266] The upper limit of the content of the vinyl aromatic block copolymer, particularly the styrene block copolymer, is 80% by weight or less, preferably 65% ​​by weight or less, and particularly preferably 60% by weight or less, based on the total amount of the adhesive (100% by weight). If the content of the vinyl aromatic block copolymer is too high, the adhesive will have little tack.

[0267] Block copolymers with soft and hard blocks that differ greatly in their glass transition temperatures generally form domain structures at room temperature, which tend to provide cohesive strength through physical crosslinking of the adhesive. Also, unmodified block copolymers of styrene blocks and diene / butylene / isobutylene / ethylene / propylene blocks generally only maintain shear stability up to 85°C or up to 100°C, at which point the hard blocks begin to soften, depending on the composition.

[0268] The adhesive may be based on selected styrene block copolymers. Pressure sensitive adhesion of the polymer blend may be achieved by the addition of an elastomeric phase of a miscible adhesive resin. Blend components that may be added to the adhesive include antioxidants, processing aids, colorants, optical brighteners, stabilizers, endblock reinforcing resins, and optionally other polymers, preferably of elastomeric nature. The types and amounts of these mixed components can be selected as necessary.

[0269] In order to obtain the desired cohesive properties, the adhesive may also comprise, in addition to the at least one vinyl aromatic block copolymer, at least one adhesive resin, which is preferably compatible with the elastomeric block of the block copolymer, Particularly preferably, at least 75% by weight of the total adhesive resin is a hydrocarbon resin or a terpene resin, or a mixture thereof.

[0270] The adhesive agent may be a non-polar hydrocarbon resin. The non-polar hydrocarbon resin may be, for example, a hydrogenated or non-hydrogenated polymer of dicyclopentadiene, a non-hydrogenated, partially, selectively or completely hydrogenated hydrocarbon resin based on C5-, C5 / C9- or C9-monomer streams, or a polyterpene resin based on α-pinene and / or β-pinene and / or δ-limonene. The adhesive resins mentioned above may be used alone or as a mixture of two or more kinds. In that case, they may be used as solid or liquid resins at room temperature. The hydrogenated or non-hydrogenated rosin-based resins are utilized in the adhesive to a maximum extent of 25% based on the total amount of resin, so that the adhesive is not excessively polar.

[0271] As further additives, the following components (a) to (h) may generally be used: Component (a): A plasticizer, such as a softening oil, or a low molecular weight liquid polymer, such as a low molecular weight polybutene. Component (b): A primary antioxidant such as, for example, a sterically hindered phenol. Component (c): A secondary antioxidant such as, for example, a phosphite or a thioether. Component (d): Process stabilizers such as C-radical scavengers Component (e): Photoprotective agents such as UV-absorbers or sterically hindered amines. Component (f): Processing aid Component (g): End block reinforcing resin, Component (h): optionally other polymers with elastomeric properties, suitably available elastomers, in particular unsaturated polydienes, such as natural or synthetic polyisoprene or polybutadiene, based on pure hydrocarbons, substantially chemically saturated elastomers (e.g. saturated ethylene-propylene copolymers, α-olefin copolymers, polyisobutylene, butyl rubber, ethylene-propylene rubber), as well as chemically functionalized hydrocarbons (e.g. halogenated acrylate-containing allyl polyolefins or vinyl ether-containing polyolefins).

[0272] The adhesive may be colored, if necessary, with a colorant or pigment, and the color of the adhesive may be white, black, or a chromatic color.

[0273] In this embodiment, the adhesive resin may be an adhesive resin containing at least one polyvinyl aromatic-polydiene block copolymer-based elastomer (i), at least one tackifying resin (ii), and an optionally added softening resin (iii), and optionally added other additives (iv).

[0274] The elastomer (i) is preferably composed of at least 90% by mass of a polyvinyl aromatics-polydiene block copolymer, particularly a polyvinyl aromatics-polybutadiene block copolymer. The proportion of polyvinyl aromatics in the polyvinyl aromatics-polydiene block copolymer is 12 to 35% by mass, preferably 20 to 32% by mass. The blending ratio of the elastomer (i) to the total amount (100% by mass) of the adhesive resin is preferably 40 to 55% by mass, more preferably 45 to 55% by mass. The adhesive resin (ii) is preferably composed of a hydrocarbon resin that is essentially compatible with the polydiene block and essentially incompatible with the polyvinyl aromatic block, preferably at least 90% by mass, more preferably at least 95% by mass, and the mixing ratio of the adhesive resin (ii) to the total amount of the adhesive resin (100% by mass) is preferably at least 40% by mass, more preferably 40 to 60% by mass. Furthermore, the amount of the softening resin (iii) is 0 mass % to a maximum of 5 mass % relative to the total amount (100 mass %) of the adhesive resin. The adhesive resin may contain microballoons (for example, microballoons described below). When the adhesive resin contains microballoons, the proportion of the microballoons relative to the total amount (100 mass%) of the adhesive resin is preferably at least 0.5 mass%, more preferably 0.5 to 2.5 mass%, and even more preferably 1.0 to 2.0 mass%. Furthermore, when an adhesive resin is used in the adhesive layer, the thickness of the adhesive layer is preferably 20 to 75 μm, and more preferably 25 to 65 μm.

[0275] The adhesive resin in this embodiment comprises a pressure-sensitive adhesive based on an elastomer (i) (e.g., at least one polyvinyl aromatic-polydiene block copolymer) and at least one tackifying resin (ii).

[0276] The above elastomer (i) is XY, XYX, (XY) n , (XY)n Z or (XYX) n It is preferred that the block copolymer be at least one polyvinyl aromatics-polydiene block copolymer in the form of a block copolymer having the Z structure. In addition, XY, XYX, (XY) n , (XY) n Z or (XYX) n In Z, X's each independently represent a polymer block formed by polymerization of at least one vinyl aromatic compound, Y's each independently represent a polymer block formed by polymerization of a conjugated diene having 4 to 18 carbon atoms, or a partially hydrogenated derivative of such a polymer in the polydiene block, Z represents the remainder of a coupling agent or a polymerization initiator, and n represents an integer of 2 or more.

[0277] The adhesive resin is preferably composed of synthetic rubber, and it is particularly preferred that all synthetic rubbers constituting the adhesive resin are block copolymers having the above-mentioned structure, so that the adhesive resin may comprise a mixture of different block copolymers having the above-mentioned structure.

[0278] In other words, the block copolymer (vinyl aromatic block copolymer) contains one or more rubber-like blocks Y (also called soft blocks) and one or more glass-like blocks X (also called hard blocks). Particularly preferably, at least one synthetic rubber constituting the adhesive resin is a block copolymer having the structure XY, XYX, (XY)2Z, (XY)3Z or (XY)4Z, where X, Y and Z in these formulas have the above-mentioned meanings. A particularly preferred form of the adhesive resin is a block copolymer in which all synthetic rubbers constituting the adhesive resin have the structure XY, XYX, (XY)2Z, (XY)3Z or (XY)4Z, where X, Y and Z have the above-mentioned meanings. In particular, the synthetic rubber of the adhesive resin is preferably a mixture of block copolymers having the structure XY, XYX, (XY)2Z, (XY)3Z or (XY)4Z, and more preferably contains at least a diblock copolymer (excluding the above general formula (V)) XY, and / or a triblock copolymer (excluding the above general formula (I)) XYZ or (XY)2X.

[0279] Further, diblock and triblock copolymers (excluding the above general formulas (I) and (V)), and (XY) n -or (XY) n Advantageously, the mixture is made up of Z block copolymers, where n is 3 or greater.

[0280] Furthermore, diblock copolymers (excluding the above general formula (V)) and radial multiblock copolymers (XY) n or (XY) n Advantageously, the mixture consists of Z, n being 3 or greater.

[0281] The adhesive resin of this embodiment is preferably a pressure-sensitive adhesive based on block copolymers, which comprises a polymer block X (X block) mainly formed from vinyl aromatics, preferably styrene, and a polymer block Y (Y block) mainly formed by polymerization of 1,3-dienes, such as butadiene and isoprene, or a copolymer of both, in particular butadiene. In this case, these products may be partially hydrogenated in the diene block. As regards the partially hydrogenated derivatives, block copolymers in which the vinyl groups possibly present, i.e. the repeating units present in a side chain in an unsaturated state, such as 1,2-polybutadiene, 1,2-polyisoprene or 3,4-polyisoprene, are present in a hydrogenated state. Preferably, the block copolymer of the adhesive resin has polystyrene endblocks.

[0282] The block copolymer resulting from the X block and the Y block may contain the same or different Y blocks. The block copolymer may have a linear XYX structure. Radial block copolymers, as well as star and linear multiblock copolymers, may also be used. As another component, a diblock copolymer of XYZ may be present. All of the above polymers may be used alone or in mixture with each other.

[0283] Instead of the preferred polystyrene blocks, the vinyl aromatics may also utilize other aromatics-containing homo- and copolymer-based polymer blocks (preferably C8-C12 aromatics) having a glass transition temperature above 75° C., such as α-methylstyrene-containing aromatics blocks. Additionally, identical or different X blocks may also be included.

[0284] The vinyl aromatics for the construction of the X block preferably include styrene, α-methylstyrene and / or other styrene derivatives. Thus, the X block may exist as a homopolymer or copolymer. A particularly preferred X block is polystyrene.

[0285] Preferred conjugated dienes as monomers for the construction of the soft block Y are preferably selected from the group consisting of butadiene, isoprene, ethylbutadiene, phenylbutadiene, piperylene, pentadiene, hexadiene, ethylhexadiene, and dimethylbutadiene, and any mixtures of these monomers. The soft block Y may also be present as a homopolymer or copolymer.

[0286] The conjugated dienes used as monomers for the soft block Y are particularly preferably selected from butadiene and isoprene. For example, the soft block Y is a polymer made of polyisoprene, polybutadiene or partially hydrogenated derivatives of both polymers, such as in particular polybutylenebutadiene; or a mixture of butadiene and isoprene. Very particularly preferably, the block B is polybutadiene.

[0287] The "hard block X" and "soft block Y" reflect the selection of blocks according to their glass transition temperatures (the glass transition temperature of the hard block X is 25° C. or higher, more preferably 50° C., while the glass transition temperature of the soft block Y is preferably 25° C. or lower, more preferably −25° C. or lower).

[0288] In this embodiment, the lower limit of the proportion of the vinyl aromatic block copolymer, particularly the styrene block copolymer, is at least 40 mass %, preferably at least 45 mass %, in total, relative to the total amount (100 mass %) of the adhesive resin. The lower the proportion of vinyl aromatic block copolymer, the smaller the adhesive resin's cohesive strength, which results in easier peeling. In addition, the glass transition temperature of the elastomer phase increases, lowering impact resistance. In addition, there is a higher risk of residues remaining on the adhesive substrate when debonding.

[0289] On the other hand, the upper limit for the proportion of vinyl aromatic block copolymers, in particular styrene block copolymers, is preferably a maximum of 55% by weight in total, based on the total amount of adhesive resin, whereas a higher proportion of vinyl aromatic block copolymers results in the pressure-sensitive adhesive no longer being sufficiently pressure-sensitive.

[0290] In this embodiment, the proportion of the vinyl aromatic block copolymer, particularly the styrene block copolymer, is at least 40 mass % in total, more preferably 45 to 55 mass %, relative to the total amount (100 mass %) of the adhesive resin.

[0291] In addition to at least one vinyl aromatic block copolymer, the adhesive resin may also contain at least one tackifying resin (ii) to enhance adhesion to a desired level, said tackifying resin (ii) being preferably compatible with the elastomeric block of the block copolymer.

[0292] By "tackifying resin" is meant, consistent with the general understanding of those skilled in the art, an oligomeric or polymeric resin that enhances the adhesive properties (tack, inherent tack) of an adhesive when compared to an otherwise identical adhesive, but not including tackifier resins.

[0293] In this embodiment, the tackifying resin is selected in a proportion of 90% by weight or more, preferably 95% by weight or more (based on the total resin proportion) of resins having a DACP (diacetone alcohol cloud point) of more than +5°C, preferably more than +10°C and less than +65°C (if polyisoprene block copolymer is present in the elastomer), preferably less than +50°C (if polyisoprene block copolymer is not present in the elastomer). In addition, at least one resin has, in particular, a MMAP (mixed methylcyclohexane aniline point) of at least +50°C, preferably at least +60°C, and at most +100°C (if polyisoprene block copolymer is present in the elastomer), preferably at most +90°C (if polyisoprene block copolymer is not present in the elastomer). At least one tackifying resin has a softening point (ring and ball) of 70°C or more, preferably 100°C or more and up to 150°C.

[0294] The tackifiers used in conjunction with the adhesive resins mentioned above are preferably non-polar hydrocarbon resins, such as hydrogenated and non-hydrogenated polymers of dicyclopentadiene, non-hydrogenated or partially, selectively or completely hydrogenated hydrocarbon resins based on C5-, C5 / C9- or C9-monomer streams, polyterpene resins based on α-pinene and / or β-pinene and / or δ-limonene. The aforementioned tackifying resins can be used alone or in mixtures. Optionally, hydrogenated or non-hydrogenated tackifying resins, which also contain oxygen, can be used, preferably in a proportion of up to 10%, based on the total amount of resin in the adhesive resin.

[0295] It is particularly preferred that the adhesive resin of this embodiment is at least 75% by mass (based on the total resin proportion) of a hydrocarbon resin or a terpene resin or a mixture thereof. The adhesive resin preferably contains 40 to 60% by mass of at least one adhesive resin based on the total amount (100 mass) of the adhesive resin.

[0296] In this embodiment, the blending ratio of the (viscous) liquid softening resin (iii) at room temperature is up to 5% by mass relative to the total amount (100% by mass) of the adhesive resin. However, it is not necessary to blend the (viscous) liquid softening resin (iii) at room temperature. For example, the use of low-viscosity softening agents such as mineral oil and vegetable oil can be significantly avoided. When using the softening resin (iii), a viscous softening resin having a melt viscosity of at least 25 Pa*s, particularly at least 50 Pa*s, at 25°C and 1 Hz and a softening temperature of <25°C is preferred. The melt viscosity is determined according to Test VI.

[0297] The adhesive resin may contain other additives (iv) as necessary. For example, the above-mentioned components (b) to (h) may be used as the other additives (iv). The component (b) is preferably blended in an amount of 0.2 to 1 mass % relative to 100 mass % of the total amount of the adhesive resin. Examples of component (c) include secondary antioxidants such as phosphites, thioesters, or thioethers, and the component (c) is preferably blended in an amount of 0.2 to 1 mass % relative to 100 mass % of the total amount of the adhesive resin. The component (d) is preferably blended in an amount of 0.2 to 1 mass % relative to the total amount (100 mass %) of the adhesive resin. The component (e) is preferably blended in an amount of 0.2 to 1 mass % relative to the total amount (100 mass) of the adhesive resin. The component (f) is preferably blended in an amount of 0.2 to 1 mass % relative to the total amount (100 mass %) of the adhesive resin. The component (g) is preferably blended in an amount of 0.2 to 10 mass % relative to the total amount (100 mass %) of the adhesive resin. Component (h): optionally further polymers, preferably of elastomeric nature, preferably in a proportion of 0.2 to 10% by weight, based on the total amount (100% by weight) of the adhesive resin; correspondingly usable elastomers include, inter alia, purely hydrocarbon-based elastomers, for example unsaturated polydienes, such as natural or synthetic polyisoprene or polybutadiene, chemically substantially saturated elastomers, for example saturated ethylene-propylene copolymers, α-olefin copolymers, polyisobutylene, butyl rubber, ethylene-propylene rubber, as well as chemically functionalized hydrocarbons, for example halogen-containing, acrylate-containing, allyl-containing or vinyl ether-containing polyolefins.

[0298] The type and amount of the above-mentioned other additives can be selected as required. When additive (iv) is used and is migratory, the same type of additive as (iv) can be used. The adhesive resin may not contain a part of the above-mentioned other additives, preferably not all of them.

[0299] In this embodiment, the adhesive resin may further include additives other than the other additives mentioned above. The additives may be, but are not limited to, crystalline or amorphous oxides, hydroxides, carbonates, nitrides, halides, carbides or mixed oxide- / hydroxide- / halide compounds of aluminum, silicon, zirconium, titanium, tin, zinc, iron or alkaline (earth) metals. The additives may be aluminium, such as aluminum oxides, boehmite, bayerite, gibbsite, diaspore and the like. Particularly preferred examples are layered silicates, such as bentonite, montmorillonite, hydrotalcite, hectorite, kaolinite, boehmite, mica, vermiculite or mixtures thereof. Carbon black or other modifications of carbon, such as carbon nanotubes, may also be used as additives.

[0300] The adhesive resin may be colored with a dye or pigment if necessary, and the color of the adhesive resin may be, for example, white, black, or a chromatic color.

[0301] When it is important to adjust the thermal shear strength of the adhesive resin, silica, more preferably precipitated silica surface-modified with dimethyldichlorosilane, may be added.

[0302] The adhesive layer of the present embodiment may contain microballoons. The microballoons in the adhesive layer have a number average primary particle size of 10 to 60 μm. Meanwhile, the microballoons used as a raw material for preparing the adhesive composition have an average particle size of 10 to 50 μm. When microballoons having a predetermined number-average primary particle size are present in the adhesive layer, a large number of cavities or shear yields occur near the microballoons dispersed in the matrix, absorbing the energy at the time of impact, which is thought to improve impact resistance. However, if the filling rate of the microballoons in the adhesive layer is increased with emphasis on the required impact resistance, the elastic modulus is improved and the cutting processability is improved, but the relative amount of the adhesive resin decreases and the adhesive performance is reduced. This tendency is particularly noticeable when an adhesive tape having an adhesive layer and a base layer is used, because poor anchoring of the adhesive layer to the base layer occurs. However, when the above-mentioned filler particles and microballoons are added in combination to the adhesive layer, high adhesive strength can be maintained while ensuring impact resistance. Although the reason is unclear, it is thought that when filler particles and microballoons of different particle sizes and materials are mixed, the aggregation of the fillers or balloons is suppressed, resulting in a good dispersion state of the adhesive layer.

[0303] The microballoons in this embodiment are hollow bodies, and the average particle size (=outer diameter) of the hollow bodies alone is 10 to 50 μm. The microballoons may contain volatile hydrocarbons such as butane and isobutane, if necessary. The average particle size (=outer diameter) of the hollow bodies (single body) of 10 to 50 μm here refers to the average particle size of the microballoons after they are expanded. When the microballoons in this embodiment are added to the adhesive composition, it is preferable to use expanded microballoons obtained by previously expanding unexpanded microballoons by heat treatment or the like. In addition, when forming a precursor of an adhesive layer (such as a coating film of a resin composition for an adhesive layer) or an adhesive layer using unexpanded microballoons, the microballoons may be expanded. Examples of the unexpanded microballoons include microballoons made of a thermoplastic resin that are not expanded.

[0304] Similarly, the number average primary particle diameter of the microballoons present in the adhesive layer also represents the outer diameter of the microballoons after expansion. In this embodiment, the microballoons contained in the adhesive layer may be hollow bodies having a number average primary particle diameter of 10 to 60 μm, and are preferably expanded microballoons.

[0305] In this embodiment, the average particle size of the expanded microballoons added to the pressure-sensitive adhesive composition is preferably 10 to 50 μm, more preferably 15 to 50 μm, and even more preferably 18 to 45 μm. When the average particle size of the microballoons is within the preferred range, the pressure-sensitive adhesive tape can be peeled off more easily and quickly, is less likely to tear even when the base material of the pressure-sensitive adhesive tape is thin, and has excellent impact resistance, shear adhesive strength, and cleavage adhesive strength. On the other hand, when the average particle size of the microballoons is less than 10 μm, the desired impact resistance cannot be obtained, and when it exceeds 50 μm, adhesive performance such as shear adhesive strength and cleavage adhesive strength may be impaired. In this specification, the "average particle size of microballoons" refers to the size of the microballoons alone before they are added to the pressure-sensitive adhesive composition, and refers to the volume average particle size measured by a measuring device (Microtrac) using a laser diffraction scattering method. The average particle size of the microballoons was measured under the measurement conditions described in the Examples section below.

[0306] In this specification, the "number average primary average particle size of microballoons" refers to the size of a single microballoon particle present in the adhesive layer, and the number average primary average particle size of microballoons present in the adhesive layer is measured using the following method. First, the adhesive tape cooled under liquid nitrogen was cut at three random locations using a microtome, and the three pieces were used as samples. Then, a photograph was taken of each sample at a magnification of 400 times using a scanning electron microscope, and from the three photographs taken, the hollow particles were selected as microballoons and the solid particles were selected as filler particles. Then, the cross-sectional areas of the hollow and solid bodies calculated by binarization processing (for example, Otsu's binarization processing) using image analysis software were regarded as the area of ​​a circle, and the circle equivalent diameters of the hollow and solid bodies were measured. Then, the total number of hollow and solid bodies in the three photographs and the corresponding circle equivalent diameters were calculated, and the number average primary average particle size of the hollow microballoons was calculated from the following formula (B).

number

[0307] In this embodiment, the external shape of the microballoons is not particularly limited and can be appropriately selected depending on the purpose. Examples of the external shape of the microballoons include spherical, elliptical, polygonal, cubic, rod-like, needle-like, flat, scaly, and amorphous.

[0308] The microballoons in this embodiment have a structure sealed by a surface layer, which is an outer shell. Either microballoons using an organic material (e.g., thermoplastic resin) for the outer shell or microballoons using an inorganic material (e.g., borosilicate glass, silica, carbon, ceramic, etc.) for the outer shell can be used, but organic microballoons are preferred. When organic microballoons are used, the outer shell becomes soft, especially when heat is applied to the microballoons. At the same time, the liquid foaming gas or the like enclosed inside the hollow body changes to its gaseous state. At this time, the microballoons expand irreversibly and expand three-dimensionally. The expansion ends when the internal pressure and the external pressure become equal. Since the outer shell is maintained, a closed-cell foam can be obtained.

[0309] In this embodiment, the microballoons contained in the adhesive layer are preferably expanded microballoons. In addition, in this embodiment, in the adhesive composition forming the adhesive layer, unexpanded microballoons are used to form the adhesive layer. Examples of the unexpanded microballoons include unexpanded microballoons made of a thermoplastic resin. In this embodiment, the microballoons preferably have a surface layer, which is an outer shell, made of the first resin. More specifically, the preferred microballoons in this embodiment are hollow particles having a surface layer containing the first resin.

[0310] The first resin is preferably a thermoplastic resin, and is preferably an acrylonitrile resin, specifically, vinylidene chloride / acrylonitrile copolymer, methyl methacrylate / acrylonitrile copolymer, methacrylonitrile / acrylonitrile copolymer, etc. Specific examples of the microballoons include the Dualite (registered trademark) series manufactured by Dualite Corporation, the Expancel series manufactured by Akzo Nobel, the Matsumoto Microsphere (registered trademark) series manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., hollow glass particles (silica balloons, alumina balloons, etc.), hollow ceramic particles, etc.

[0311] In this embodiment, it is preferable that the surface of the microballoons is partially or entirely coated with an inorganic material (e.g., inorganic fine particles). The inorganic material is preferably at least one or more inorganic powders selected from the group consisting of calcium carbonate, surface-treated calcium carbonate, titanium oxide, silicon oxide, talc, clay, and carbon black. Coating the surface of the microballoons with an inorganic material is preferable from the viewpoint of improving productivity, dispersibility, and impact resistance. In addition, the inorganic material may be surface-treated with a titanate-based coupling agent or an aluminate-based coupling agent, if necessary. The microballoons used in this embodiment are hollow particles having a surface layer containing a first resin, and preferably have an inorganic material attached to the surface of the surface layer. In this embodiment, it is also preferable that calcium carbonate is attached to a part or the whole of the microballoon surface. This further improves the impact resistance effect.

[0312] In this embodiment, the ratio of the number average primary particle size of the microballoons to the average thickness of the adhesive layer is not particularly limited and can be appropriately selected depending on the purpose. The ratio of the number average primary particle size of the microballoons to the thickness of the adhesive layer, expressed as [number average primary particle size of the microballoons / average thickness of the adhesive layer], is preferably in the range of 0.1 to 1.0, more preferably 0.2 to 0.9, even more preferably 0.2 to 0.8, and particularly preferably 0.3 to 0.7. When the ratio is 0.1 or more, suitable impact resistance is easily obtained, and when the ratio is 1.0 or less, it is advantageous in that the adhesive properties such as shear adhesive strength and split adhesive strength are also more excellent.

[0313] The content of the microballoons in the adhesive layer is 1 to 30 parts by mass, preferably 2 to 25 parts by mass, more preferably 3 to 23 parts by mass, and even more preferably 4 to 20 parts by mass, relative to 100 parts by mass of the adhesive resin. By having the content of the microballoons be 1 part by mass or more relative to 100 parts by mass of the adhesive resin, it is possible to achieve both impact resistance and cuttability, or to ensure ease of peeling. In addition, by having the content of the microballoons be 50 parts by mass or less relative to 100 parts by mass of the adhesive resin, it is possible to prevent the adhesive layer from remaining on the adherend, the impact resistance from decreasing, and the shear adhesive strength or split adhesive strength from decreasing. The content of the microballoons in the adhesive layer can be appropriately adjusted when preparing the adhesive composition.

[0314] The volume ratio of the microballoons to the total volume of the adhesive layer is preferably 3 to 40 volume%, more preferably 5 to 35 volume%, even more preferably 8 to 30 volume%, and most preferably 10 to 30 volume%. When the volume ratio of the microballoons is 3 volume% or more, the adhesive tape can be peeled off more easily and quickly. When the volume ratio of the microballoons is 40 volume% or less, the adhesive layer can be prevented from remaining on the adherend, the impact resistance can be reduced, and the shear adhesive strength or split adhesive strength can be prevented.

[0315] In this specification, the volume ratio of the microballoons to the adhesive layer can be calculated from the following formulas (4) to (6). Adhesive Resin *1 Mass A (g) / Adhesive resin *1 Density A (g / cm 3 ) = Adhesive resin *1 Volume A (cm 3 )...Equation (4) Mass of microballoon B (g) / Density of microballoon B (g / cm 3 ) = Volume of microballoon B (cm 3 )...Equation (5) Microballoon volume B (cm3 ) / (Adhesive resin *1 Volume A (cm 3 ) + volume of microballoon B (cm 3 )) × 100 = Volume fraction of microballoons (volume%) Equation (6) In the above formulas (4) and (6), the adhesive resin represented by *1 may contain other components described below. The density is a value measured in accordance with JIS Z 8804.

[0316] <Foam layer> In the first embodiment, the pressure-sensitive adhesive tape includes a foam layer, and the foam of the foam layer has a 25% compressive strength of 40 to 160 kPa and a tensile strength of 3.0 to 15.0 MPa, which gives the pressure-sensitive adhesive tape appropriate elasticity and allows the tape to continue adhering each part (first adherend, second adherend) even if the parts (adherends) are slightly distorted (the tape has resistance to peeling in the thickness direction).

[0317] In the first embodiment, the foam of the foam layer has a 25% compression strength of 40 to 160 kPa, preferably 50 to 140 kPa, more preferably 60 to 130 kPa. By using a foam having a 25% compression strength in this range, it has excellent adhesion to the adherend, and in particular, it has excellent adhesion by suitably following the adherend having an uneven shape or a rough surface. In addition, since a foam with this compression strength has an appropriate cushioning property, the pressure during attachment is concentrated at the joint and the air present at the adhesive interface is easily pushed out, so that even when rigid bodies are joined together, excellent adhesion can be achieved without generating gaps through which water can enter.

[0318] The foam of the foam layer preferably has a closed-cell structure. This allows, for example, a first adherend and a second adherend bonded together using an adhesive tape to more reliably block the space through the adhesive tape, improving airtightness and effectively preventing water from seeping in from the cut surface of the foam. The shape of the bubbles forming the closed-cell structure is not particularly limited, but closed bubbles having an average bubble diameter longer in the flow direction, width direction, or both directions than the average bubble diameter in the thickness direction of the foam are preferred because they have appropriate cushioning properties.

[0319] The average bubble diameter in the thickness direction of the foam is preferably 1 to 100 μm, more preferably 10 to 50 μm, and the average bubble diameter in the flow direction and width direction of the foam is preferably 1.2 to 700 μm, more preferably 10 to 500 μm, and even more preferably 50 to 300 μm. By setting the average bubble diameter within this range, closed bubbles are easily formed even when the width of the pressure-sensitive adhesive tape is narrowed, and the path of water penetration from the cross section of the foam can be suitably blocked.

[0320] The ratio of the average cell diameter is not particularly limited, but the ratio of the average cell diameter in the flow direction of the foam to the average cell diameter in the thickness direction of the foam (average cell diameter in the flow direction / average cell diameter in the thickness direction) is preferably 1.2 to 15, more preferably 3 to 8. The ratio of the average cell diameter in the width direction of the foam to the average cell diameter in the thickness direction of the foam (average cell diameter in the width direction / average cell diameter in the thickness direction) is preferably 1.2 to 15, more preferably 3 to 8. It is more preferable that both the flow direction and the width direction are within the above ratio range. When the ratio is 1.2 or more, flexibility in the thickness direction is easily ensured, and the tracking ability is improved. When the ratio is 15 times or less, the flexibility and tensile strength of the foam are less likely to vary between the flow direction and the width direction.

[0321] Furthermore, the ratio of the average cell diameter in the machine direction to the width direction is preferably 0.25 to 4 times, and more preferably 0.33 to 3 times, when the machine direction is taken as 1. When the ratio is within the above range, the flexibility and tensile strength of the foam are less likely to vary between the machine direction and the width direction.

[0322] The average bubble diameter in the width direction and flow direction of a foam is measured as follows. First, the foam is cut into 1 cm pieces in both the width direction and flow direction. Next, the central part of the cut surface of the foam is magnified 50 times with a scanning electron microscope (SEM), and the cross section of the foam in the width direction or flow direction is photographed so that the cut surface of the foam fits in the photograph over the entire length of the foam thickness direction. In the obtained photograph, all the bubble diameters present on the cut surface with an actual length of 2 mm before enlargement in the flow direction or width direction are measured, and the average bubble diameter is calculated from the average value.

[0323] The average bubble diameter in the thickness direction of a foam is measured as follows. First, the thickness of the foam is measured by photographing it with an SEM. Next, an SEM photograph is taken under the same conditions as for measuring the average bubble diameter in the flow direction of the foam. Next, in the photograph obtained, the number of bubbles in the thickness direction present at any point of the foam is visually counted, and the average bubble diameter in the thickness direction is calculated using the following formula. Average bubble diameter in thickness direction (μm) = foam thickness (μm) / number of bubbles This is measured at any three points, and the average value is taken as the average bubble diameter in the thickness direction.

[0324] The foam structure of the foam is preferably adjusted to have an expansion ratio of 2 to 6.5 times, more preferably 3 to 5.5 times, since it is easy to adjust the compressive strength and tensile strength within the above ranges and realize excellent adhesion to the adherend. In this specification, the expansion ratio refers to the specific gravity of the resin constituting the foam divided by the specific gravity of the foam.

[0325] For the 25% compression strength, cut a sample into 50 mm square pieces and stack them together until the thickness is about 10 mm. The sample is sandwiched between plates with a larger surface area than the sample, and compressed to about 2.5 mm (25% of the original thickness) at a speed of 10 mm / min at 23°C. The compression is stopped, and the strength is measured after 20 seconds.

[0326] The compressive strength and tensile strength of the foam can be adjusted appropriately depending on the material and foam structure of the foam used. The type of foam is not particularly limited as long as it has the above compressive strength and tensile strength, but polyolefin foams and polyurethane foams made of polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, etc., rubber foams made of acrylic rubber and other elastomers, etc. can be used, and polyolefin foams are preferably used because they are easy to prepare thin foams that are excellent in conformity to the unevenness of the adherend surface and in shock absorption.

[0327] The thickness of the foam may be adjusted as appropriate depending on the mode of use, but is preferably 50 to 1200 μm. For fixing components of electronic devices, particularly small, thin portable electronic devices, a thin tape is required, so the thickness of the foam is more preferably 50 to 300 μm, even more preferably 50 to 250 μm, and most preferably 75 to 150 μm.

[0328] The foam has a tensile strength of 3.0 to 15.0 MPa, preferably 4.0 to 13.0 MPa, and more preferably 5.0 to 12.0 MPa. The elongation at break is 100 to 1000%, and preferably 300 to 700%. A foam having a tensile strength and elongation at break within the above ranges can suppress deterioration in processability of the pressure-sensitive adhesive tape, tearing, and deterioration in application workability, even if the foam is a flexible foam.

[0329] The tensile strength mentioned above is the maximum strength measured using a Tensilon tensile testing machine on a sample with a gauge length of 2 cm and a width of 1 cm, at a tensile speed of 300 mm / min in an environment of 23°C and 50% RH.

[0330] Examples of such foams include crosslinked polyolefin resin foams obtained by irradiating an expandable polyolefin resin sheet formed using a polyolefin resin with an electron beam to crosslink the resin and foam the sheet, etc. Although conventionally known polyolefin resins can be used, those containing 40% by mass or more of a polyethylene resin obtained using a metallocene compound containing a tetravalent transition metal are preferred.

[0331] In order to improve adhesion to the adhesive layer or other layers, the foam may be subjected to surface treatment such as corona treatment, flame treatment, plasma treatment, hot air treatment, ozone / ultraviolet treatment, application of an adhesion enhancing treatment agent, etc. The surface treatment is performed so that the wetting index measured by a wetting agent is 36 mN / m or more, preferably 40 mN / m, to obtain good adhesion to the adhesive.

[0332] <Other layers> The adhesive tape of the first embodiment is not particularly limited, and other layers may be provided as appropriate depending on the purpose. Examples of such layers include a primer layer, an antistatic layer, a flame-retardant layer, a decorative layer, a conductive layer, a heat-conductive layer, and a release layer.

[0333] <Adhesive tape shape, characteristics, etc.> The shape and dimensions of the adhesive tape of the first embodiment are not particularly limited, and examples thereof include adhesive tapes having a shape and dimensions suitable for attachment to a specified adherend (e.g., adhesive tapes in a state after punching processing) and long sheet-like adhesive tapes (e.g., adhesive tapes before being processed into a specific shape). Furthermore, the adhesive tape of the first embodiment can be provided with an optional gripping area that is made non-adhesive, for example, for application to an adherend or for peeling from an adherend, by covering the adhesive layer on the surface side of the adhesive tape with a non-adhesive film or the like, or by leaving the adhesive layer on the surface side unformed (by peeling it off or not forming it during production).

[0334] The thickness of the adhesive tape is not particularly limited and can be selected appropriately depending on the thickness of the adhesive layer and the first base layer, but is preferably 85 μm to 2400 μm, more preferably 130 μm to 840 μm, even more preferably 150 μm to 570 μm, and particularly preferably 180 μm to 500 μm. In this specification, the "thickness of the adhesive tape" refers to the average value of the thicknesses measured at any five points on the adhesive tape using a TH-104 paper / film thickness meter (manufactured by Tester Sangyo Co., Ltd.).

[0335] The pressure-sensitive adhesive tape also has excellent impact resistance. Impact resistance can be confirmed, for example, by the method described in the "Evaluation of Impact Resistance" section of the Examples section below. In the evaluation of impact resistance, the height of the impact point at which peeling or destruction of the pressure-sensitive adhesive tape occurs can be appropriately selected within a range that does not impair the effects of the present invention, but is preferably 30 cm or more, more preferably 40 cm or more, even more preferably 50 cm or more, and particularly preferably 60 cm or more. If the height is less than 30 cm, there is a tendency that sufficient impact resistance cannot be obtained.

[0336] The 180° peel adhesive strength of the pressure-sensitive adhesive tape is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10 N / 20 mm to 50 N / 20 mm, more preferably 15 N / 20 mm to 45 N / 20 mm, and even more preferably 18 N / 20 mm to 40 N / 20 mm. When the 180° peel adhesive strength is within the above-mentioned preferred range, the pressure-sensitive adhesive tape has a moderate adhesive strength without peeling or slipping from the adherend, and can be easily peeled off when stretched and peeled off again. The 180° peel adhesive strength of an adhesive tape refers to the value measured in accordance with JIS Z 0237.

[0337] <Method of manufacturing adhesive tape> In the first embodiment, the method for producing the adhesive tape is not particularly limited and can be appropriately selected from known methods. The method for producing the adhesive tape of the first embodiment preferably includes an adhesive layer forming step, a first base layer forming step, a foam layer forming step, and a lamination step, and further includes other layer forming steps as necessary. In addition, the adhesive tape can also be produced by a multi-layer simultaneous formation step in which the adhesive layer forming step and the first base layer forming step are performed simultaneously.

[0338] The adhesive layer forming step is not particularly limited as long as each adhesive layer can be formed, and can be appropriately selected depending on the purpose, and examples thereof include a method of forming an adhesive layer on the surface of a release sheet by a heat press method, a casting method by extrusion molding, a uniaxial stretching method, a sequential secondary stretching method, a simultaneous biaxial stretching method, an inflation method, a tube method, a calendar method, a solution method, etc. Among these, the casting method by extrusion molding and the solution method are preferred. The release sheet is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include paper such as kraft paper, glassine paper, and wood-free paper; resin films such as polyethylene, polypropylene (biaxially oriented polypropylene (OPP), uniaxially oriented polypropylene (CPP)), and polyethylene terephthalate (PET); laminated paper in which the above-mentioned paper and resin film are laminated together; and the above-mentioned paper that has been subjected to a sealing treatment with clay, polyvinyl alcohol, or the like and then subjected to a release treatment with silicone resin or the like on one or both sides. These may be used alone or in combination of two or more types.

[0339] The first base layer forming step is not particularly limited as long as the first base layer can be formed, and can be appropriately selected according to the purpose, and examples thereof include a heat press method, a casting method by extrusion molding, a uniaxial stretching method, a sequential secondary stretching method, a simultaneous biaxial stretching method, an inflation method, a tube method, a calendar method, and a solution method. These methods may be used alone or in combination of two or more. Among these, the casting method by extrusion molding, the inflation method, the tube method, the calendar method, and the solution method are preferred in terms of imparting suitable flexibility and extensibility to the first base layer. The first base layer may be surface-treated in order to further improve adhesion to the adhesive layer. The surface treatment method is not particularly limited and can be appropriately selected from known methods as long as it does not impair the properties of the adhesive tape. Examples of the surface treatment method include sandblasting, surface polishing / rubbing, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet irradiation treatment, and oxidation treatment.

[0340] In the foam layer forming step, as long as the foam layer can be formed, there is no particular restriction, and it can be appropriately selected according to the purpose. Specifically, in the foam layer forming step, for example, the raw material for forming the foam is supplied so as to be coated on a release sheet. Then, when a raw material that is to be foamed after coating is used, for example, another release sheet is supplied from above the surface of the raw material to be cast. Then, in this laminated state, the raw material is passed through a roll coater or the like to adjust the thickness while foaming it. It is not important whether or not the release sheet supplied from above is used, but if the release sheet is used, it is easy to adjust the thickness of the foam before curing, and a skin layer can be formed on the surface of the foam obtained after heat treatment. In addition, when using a raw material that has been foamed before application (for example, an emulsion composition, etc.), the raw material is applied onto release paper using a known means such as a doctor knife or doctor roll, and adjusted to the desired thickness. Through these steps, a laminate can be obtained in which a release sheet is laminated on at least one side of the uncured foam layer. The laminate is then heated by a heat treatment device, whereby it can be cured and dried to form a foam layer.

[0341] In addition, when a crosslinked polyolefin resin foam is used as the foam, a polyolefin resin and a thermal decomposition type foaming agent are fed to an extruder and melt-kneaded to obtain a raw material, which is then extruded from the extruder into a sheet to form a foamable polyolefin resin sheet. The sheet is then irradiated with an electron beam to crosslink the resin, and then foamed, stretched, and thinned to obtain a foam. Although a conventionally known polyolefin resin can be used, it is preferable to use a polyolefin resin containing 40% by mass or more of a polyethylene resin obtained using a metallocene compound containing a tetravalent transition metal. In addition, after the foam is foamed, the foam sheet may be sliced ​​in the thickness direction, stretched with a hot roll, and then skinned to produce the foam.

[0342] The lamination step is a step of laminating the first base layer, each adhesive layer, and foam layer. The method of laminating the first base layer, each adhesive layer, and foam layer is not particularly limited and can be appropriately selected from known methods, for example, a method of pressing and laminating the adhesive layer, the first base layer, and the foam layer in a state of adhering to the release sheet formed in the adhesive layer forming step. Specifically, the first adhesive layer and the first base layer are laminated, and the third adhesive layer and the foam layer are laminated. Next, the laminate on the first base layer side and the laminate on the foam layer side are laminated so as to sandwich the foam layer therebetween, thereby obtaining the adhesive tape of the first embodiment.

[0343] Adhesive Tape of Second Embodiment The adhesive tape of the second embodiment according to this embodiment comprises, in order, a first adhesive layer, a first base layer, a second adhesive layer, a foam layer and a third adhesive layer, and the first base layer has a breaking strength of 1.0 to 100.0 MPa, a breaking elongation of 400 to 1500%, a 25% compressive strength of the foam of the foam layer of 40 to 160 kPa, and a tensile strength of 3.0 to 15.0 MPa. The adhesive tape of the second embodiment is different from the adhesive tape of the first embodiment in that it includes a second adhesive layer between the first base layer and the foam layer. In this embodiment, the second adhesive layer is a layer that enables the first base layer side portion and the foam layer side portion of the adhesive tape to be joined together. When peeling off the adhesive tape of the second embodiment, it is preferable that the second adhesive layer extends following the first base layer, which allows the second adhesive layer to reduce residues remaining on the adherend.

[0344] Hereinafter, the adhesive tape of the second embodiment will be described in terms of the constituent features that differ from those of the adhesive tape of the first embodiment described above, and a description of the same constituent features will be omitted. In the third embodiment, similarly to the first and second embodiments, the adhesive layer adjacent to the first base layer, specifically the first adhesive layer, preferably the first adhesive layer and the second adhesive layer, preferably contain a predetermined amount of filler particles as described above. In the third embodiment, the adhesive layer adjacent to the first base layer, particularly the first adhesive layer, contains filler particles, so that the adhesive tape can be peeled off more easily, and the peeling operation can be facilitated. In addition, the second adhesive layer also contains filler particles, so that the adhesive strength can be easily reduced when peeling off the adhesive tape from between the first adherend and the second adherend, even between the second adhesive layer and the fourth adhesive layer described later, and the adhesive tape can be peeled off even more easily.

[0345] The adhesive composition forming the second adhesive layer may contain the same adhesive resin as the adhesive resin described in the first embodiment above, and may further contain filler particles and other components as necessary in addition to the adhesive resin, as in the first embodiment above. The second adhesive layer may be the same adhesive composition as the first adhesive layer or the third adhesive layer, or may be a different adhesive composition. The second adhesive layer may have the same range of properties and thickness as the first adhesive layer or the third adhesive layer.

[0346] In the second embodiment, similarly to the first embodiment, the adhesive layer adjacent to the first base layer, specifically the first adhesive layer, preferably the first adhesive layer and the second adhesive layer, preferably contain a predetermined amount of filler particles as described above. In the second embodiment, the adhesive layer adjacent to the first base layer, particularly the first adhesive layer, contains filler particles, so that the adhesive tape can be peeled off more easily, and the peeling operation can be facilitated. In addition, the second adhesive layer also contains filler particles, so that the adhesive force can be easily reduced when peeling off the adhesive tape from between the first adherend and the second adherend, and the adhesive tape can be peeled off even more easily.

[0347] <Adhesive tape shape, characteristics, etc.> The adhesive tape of the second embodiment can have the same shape, properties and thickness as the adhesive tape of the first embodiment.

[0348] <Method of manufacturing adhesive tape> In the second embodiment, the method for producing the pressure-sensitive adhesive tape is not particularly limited and can be appropriately selected from among known methods. Specifically, in the adhesive tape of the second embodiment, the first base layer, each adhesive layer, and foam layer can be obtained in the same manner as the adhesive layer forming step, the first base layer forming step, and the foam layer forming step in the manufacturing method of the adhesive tape of the first embodiment. In addition, in the adhesive tape of the second embodiment, the adhesive layer, the first base layer, and the foam layer in a state where they are attached to the release sheet are pressed and laminated to obtain the adhesive tape. Specifically, the first adhesive layer and the second adhesive layer in a state where they are attached to the release sheet are laminated on both sides of the first base layer, and the third adhesive layer in a state where they are attached to the release sheet is laminated on the surface of the foam layer. Then, the laminate on the first base layer side and the laminate on the foam layer side are laminated so as to face each other, thereby obtaining the adhesive tape of the second embodiment.

[0349] Adhesive tape according to a third embodiment The adhesive tape of the third embodiment according to this embodiment comprises, in order, a first adhesive layer, a first base layer, a second adhesive layer, a fourth adhesive layer, a foam layer, and a third adhesive layer, and the first base layer has a breaking strength of 1.0 to 100.0 MPa, a breaking elongation of 400 to 1500%, a 25% compressive strength of the foam of the foam layer of 40 to 160 kPa, and a tensile strength of the foam layer of 3.0 to 15.0 MPa. The adhesive tape of the third embodiment is different from the adhesive tape of the second embodiment in that it includes a fourth adhesive layer between the second adhesive layer and the foam layer, and therefore, compared to the adhesive tape of the second embodiment, the adhesive tape of the third embodiment can facilitate the operation of peeling the adhesive tape from between the first and second adherends. Specifically, when the adhesive tape of the second embodiment is peeled off, the second adhesive layer extends following the first base layer, and at that time, the second adhesive layer may peel off while shredding the foam layer remaining on the adherend as a residue. Therefore, in the adhesive tape of the second embodiment, when the second adhesive layer peels off while shredding the foam layer, the residue including the shredded foam layer must be peeled off from the adherend after dismantling the first adherend and the second adherend. In contrast, in the adhesive tape of the third embodiment, the adhesive strength between adjacent adhesive layers (between the second adhesive layer and the fourth adhesive layer) tends to be lower than the adhesive strength between the adhesive layer and the first substrate or the adhesive strength between the adhesive layer and the foam layer (because the anchor effect is not easily exerted between adhesive layers), so in the adhesive tape of the third embodiment, the presence of the fourth adhesive layer can reduce the second adhesive layer, which peels off together with the first substrate layer, from tearing the foam layer. Therefore, in the adhesive tape of the third embodiment, the foam layer as a residue is not easily torn off, so the residue can be easily removed, making the peeling operation easier.

[0350] Hereinafter, the adhesive tape of the third embodiment will be described in terms of the constituent features that differ from those of the adhesive tape of the first embodiment described above, and a description of the same constituent features will be omitted. <Adhesive layer> The adhesive tape of the third embodiment, compared to the adhesive tape of the first embodiment, includes a second adhesive layer and a fourth adhesive layer between the foam layer and the first base layer. More specifically, the adhesive tape of the third embodiment includes a second adhesive layer disposed on the first base layer side and a fourth adhesive layer disposed on the foam layer side between the first base layer and the foam layer. Also, compared to the adhesive tape of the second embodiment (particularly the adhesive layer), the configuration of the adhesive layer of the third embodiment includes a fourth adhesive layer between the second adhesive layer and the foam layer. The fourth adhesive layer is a layer that, together with the second adhesive layer, enables the part of the adhesive tape on the first base layer side to be joined to the part on the foam layer side. The adhesive composition forming the fourth adhesive layer may contain the same adhesive resin as the adhesive resin described in the first embodiment above, and may further contain filler particles and other components as necessary in addition to the adhesive resin, as in the first embodiment above. The fourth adhesive layer may be the same adhesive composition as the first adhesive layer, the second adhesive layer, and the third adhesive layer, or may be a different adhesive composition. The fourth adhesive layer may have the same range of properties and thickness as the first adhesive layer, the second adhesive layer, and the third adhesive layer.

[0351] In the third embodiment, similarly to the first or second embodiment, the adhesive layer adjacent to the first base layer, specifically the first adhesive layer, preferably the first adhesive layer and the second adhesive layer, preferably contain a predetermined amount of filler particles as described above. In the third embodiment, the adhesive layer adjacent to the first base layer, particularly the first adhesive layer, contains filler particles, so that the adhesive tape can be peeled off more easily, and the peeling operation can be facilitated. In addition, the second adhesive layer also contains filler particles, so that the adhesive strength can be easily reduced between the fourth adhesive layer and the adhesive tape when peeling it off from between the first adherend and the second adherend, and therefore the adhesive tape can be peeled off even more easily.

[0352] <Adhesive tape shape, characteristics, etc.> The adhesive tape of the third embodiment can have the same shape, properties and thickness as the adhesive tape of the first or second embodiment.

[0353] <Method of manufacturing adhesive tape> In the third embodiment, the method for producing the pressure-sensitive adhesive tape is not particularly limited and can be appropriately selected from among known methods. Specifically, in the adhesive tape of the third embodiment, the first base layer, each adhesive layer, and foam layer can be obtained in the same manner as the adhesive layer forming step, the first base layer forming step, and the foam layer forming step in the manufacturing method of the adhesive tape of the first embodiment. In addition, in the adhesive tape of the third embodiment, the adhesive layer, the first base layer, and the foam layer in a state where they are attached to the release sheet are pressed and laminated to obtain the adhesive tape. Specifically, the first adhesive layer and the second adhesive layer in a state where they are attached to the release sheet are laminated on both sides of the first base layer, and the third adhesive layer and the fourth adhesive layer in a state where they are attached to the release sheet are laminated on both sides of the foam layer. Then, the laminate on the first base layer side and the laminate on the foam layer side are laminated so that the second adhesive layer and the fourth adhesive layer face each other, thereby obtaining the adhesive tape of the third embodiment.

[0354] Adhesive tape according to the fourth embodiment The adhesive tape of a fourth embodiment of the present disclosure comprises, in order, a first adhesive layer, a first base layer, a second adhesive layer, a second base layer, a fourth adhesive layer, a foam layer, and a third adhesive layer, and the first base layer has a breaking strength of 1.0 to 100.0 MPa and a breaking elongation of 400 to 1500%, and the foam of the foam layer has a 25% compressive strength of 40 to 160 kPa and a tensile strength of 3.0 to 15.0 MPa. The adhesive tape of the fourth embodiment is different from the adhesive tape of the third embodiment described above in that it includes a second base layer between the second adhesive layer and the fourth adhesive layer. Therefore, the adhesive tape of the third embodiment can be manufactured more easily than the adhesive tape of the second embodiment. Specifically, the adhesive tape of the third embodiment can be obtained by laminating the laminate on the first base layer side and the laminate on the foam layer side so that the second adhesive layer and the fourth adhesive layer face each other, as described above. In contrast, the adhesive tape of the fourth embodiment can be obtained by laminating the laminate on the first base layer side and the laminate on the foam layer side, before laminating the laminate on the first base layer side and the laminate on the foam layer side, by bonding the second base layer onto the surface of the adhesive layer of one of the laminates, and then bonding the other laminate onto the surface of the second base layer. That is, in the adhesive tape of the fourth embodiment, the work of bonding the second adhesive layer and the fourth adhesive layer is not performed in a state where the adhesive layer surfaces of the second adhesive layer and the fourth adhesive layer are exposed, so that the laminate on the first base layer side and the laminate on the foam layer side can be laminated more easily. In addition, according to the adhesive tape of the fourth embodiment, when the first and second adherends bonded by the adhesive tape are dismantled, the first base layer is pulled out and removed together with the first and second adhesive layers from between the adherends, and the interface between the second adhesive layer and the second base layer peels off, so that the stress caused by the conformity of the foam layer is suppressed and the first and second base layers can be easily removed. In addition, there may be a residue of the adhesive tape having the second base layer on its surface between the adherends after dismantling. In this case, since the second base layer on the surface of the residue is non-adhesive, re-adhesion between the adherends can be avoided, and dismantling of the bonded body can be performed more easily.

[0355] Hereinafter, the adhesive tape of the fourth embodiment will be described in terms of the constituent features that differ from those of the adhesive tapes of the first, second and third embodiments described above, and a description of the same constituent features will be omitted. <Second base layer> The adhesive tape of the fourth embodiment is different from the adhesive tape of the third embodiment in that it includes a second base layer between the second adhesive layer and the fourth adhesive layer. The material of the second base layer is not particularly limited, and examples thereof include a resin sheet, a nonwoven fabric, paper, a metal foil, a woven fabric, a rubber sheet, a foam sheet, and a laminate thereof (particularly, a laminate including a resin sheet). Examples of the resin constituting the resin sheet include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), wholly aromatic polyamide (aramid), polyimide (PI), polyvinyl chloride (PVC), polyphenylene sulfide (PPS), fluorine-based resin, polyether ether ketone (PEEK), and the like. Examples of the nonwoven fabric include nonwoven fabric of natural fibers (cellulose-based fibers); nonwoven fabric of synthetic resin fibers such as polypropylene resin fibers, polyethylene resin fibers, and polyester-based resin fibers, and the like. Examples of the metal foil include copper foil, stainless steel foil, and aluminum foil. Examples of the paper include Japanese paper and craft paper. Of the above, the second base layer is preferably a resin sheet from the viewpoint of ease of handling, and more preferably a resin sheet made of polyethylene terephthalate.

[0356] The thickness of the second base layer is not particularly limited, but is, for example, preferably from 2 to 200 μm, more preferably from 5 to 100 μm, even more preferably from 10 to 50 μm, and even more preferably from 10 to 30 μm.

[0357] The second base layer has a breaking elongation of 500% or less, preferably 400% or less, and more preferably 300% or less. By having a breaking elongation of 500% or less, it is possible to easily dismantle the adherends bonded together using the pressure-sensitive adhesive tape.

[0358] <Adhesive tape shape, characteristics, etc.> The adhesive tape of the fourth embodiment can have the same shape, properties and thickness as the adhesive tape of the first, second or third embodiment.

[0359] <Method of manufacturing adhesive tape> In the fourth embodiment, the method for producing the pressure-sensitive adhesive tape is not particularly limited and can be appropriately selected from among known methods. Specifically, in the adhesive tape of the fourth embodiment, the first base layer, each adhesive layer, and foam layer can be obtained in the same manner as the adhesive layer forming step, the first base layer forming step, and the foam layer forming step in the manufacturing method of the adhesive tape of the first embodiment. In addition, in the adhesive tape of the fourth embodiment, the adhesive layer, the first base layer, the second base layer, and the foam layer in a state where they are attached to the release sheet are pressed and laminated to obtain the adhesive tape. Specifically, the first adhesive layer and the second adhesive layer in a state where they are attached to the release sheet are laminated on both sides of the first base layer, and the third adhesive layer and the fourth adhesive layer in a state where they are attached to the release sheet are laminated on both sides of the foam layer. Then, the second base layer is attached to the surface of the second adhesive layer of the laminate on the first base layer side, or to the surface of the fourth adhesive layer of the laminate on the foam layer side. Next, a laminate without a second base layer attached is attached to the surface of the laminate with the second base layer attached so that the second adhesive layer and the fourth adhesive layer face each other with the second base layer in between, and laminated to obtain the adhesive tape of the fourth embodiment.

[0360] <<Applications of adhesive tape>> The adhesive tape of the present embodiment can be suitably used for component fixing or temporary fixing in various industrial fields, such as fixing metal plates constituting relatively large electronic devices, such as flat-screen televisions, home appliances, and office automation equipment, fixing exterior parts to housings, and fixing exterior parts and rigid parts, such as batteries, to relatively small electronic devices, such as portable electronic terminals, cameras, and personal computers, as well as for applications such as labels that display product information.

[0361] [zygote] The bonded structure of this embodiment includes the adhesive tape of the embodiment according to the present invention, a first adherend adhered to the surface of the first adhesive layer of the adhesive tape, and a second adherend adhered to the surface of the third adhesive layer of the adhesive tape. The bonded structure of this embodiment allows the adhesive tape to be easily peeled off, and can adequately maintain adhesion between the adherends in the bonded structure. Here, more specifically, the bonded structure of this embodiment includes a bonded structure using the adhesive tape of the first embodiment (the bonded structure of the first embodiment) or a bonded structure using the adhesive tape of the second embodiment or the adhesive tape of the third embodiment (the bonded structure of the second embodiment), and a bonded structure using the adhesive tape of the fourth embodiment (the bonded structure of the third embodiment).

[0362] <First adherend, second adherend> The first and second adherends are not particularly limited, and may be components constituting products used in various industrial fields such as office automation equipment, IT and home appliances, and automobiles. An example of a combination of the first and second adherends is when one adherend is the housing of the product, and the other adherend is a battery, electronic component, structural component, display element, or other component to be incorporated in the product. The first and second adherends can be fixed or temporarily fixed with an adhesive tape. Alternatively, an example of a combination of the first and second adherends is when one adherend is a display unit that displays a label showing product information, and the other adherend is the label. Furthermore, the specific material forming the surfaces of the first and second adherends can be any material depending on the first and second adherends, and can be made of, for example, resin or metal.

[0363] The first attachment surface of the first adherend to which the adhesive tape is attached, and the second attachment surface of the second adherend to which the adhesive tape is attached can be a smooth flat surface, but the attachment surfaces may also be curved surfaces.

[0364] [Method of dismantling the joined body] The method for dismantling a bonded body of the present embodiment is a method for dismantling the bonded body of the embodiment according to the present invention described above, and includes a step of separating the second adherend from the first adherend. According to the method for dismantling a bonded body of the present embodiment, the bonded body can be easily dismantled. Here, the method for dismantling the joined body of the present embodiment more specifically includes a method for dismantling the joined body of the above-mentioned first embodiment (the method for dismantling the joined body of the first embodiment), a method for dismantling the joined body of the above-mentioned second embodiment (the method for dismantling the joined body of the second embodiment), and a method for dismantling the joined body of the above-mentioned third embodiment (the method for dismantling the joined body of the third embodiment).

[0365] Method for dismantling the joined body according to the first embodiment The method for dismantling a bonded structure of the first embodiment includes a step of stretching at least a first base layer of the adhesive tape to separate the second adherend from the first adherend. The adhesive tape used in the first embodiment includes a first adhesive layer, a first base layer, a foam layer, and a third adhesive layer in this order. In the method for dismantling a bonded body according to the first embodiment, in order to separate (dismantle) the second adherend from the first adherend, specifically, at least the first base layer of the adhesive tape is stretched, so that at least the first adhesive layer (preferably the first adhesive layer) is peeled off (pulled out) from between the first adherend and the second adherend together with the first base layer. This allows the second adherend to be separated (dismantled) from the first adherend. At this time, since the foam layer is not easily stretched like the first base layer, the foam layer and the third adhesive layer may remain attached to the adherend and become residues. In this case, for example, the residues can be removed after the second adherend is separated (dismantled) from the first adherend.

[0366] In the first embodiment, in order to separate (dismantle) the second adherend from the first adherend, layers other than the first base layer of the adhesive tape, for example the foam layer, may also be stretched. However, when the first base layer is stretched, it is difficult for the foam layer to follow suit and stretch, so there is a risk that the foam layer will tear during stretching.

[0367] <<Method of dismantling the joined body according to the second embodiment>> The method for dismantling a bonded body of the second embodiment is the method for dismantling a bonded body of the second embodiment described above, and includes a step of stretching at least the first base layer of the adhesive tape to separate the second adherend from the first adherend. The adhesive tape used in the second or third embodiment includes a first adhesive layer, a first base layer, a second adhesive layer, a foam layer, and a third adhesive layer in this order, and further includes a fourth adhesive layer between the second adhesive layer and the foam layer as necessary. In the method for dismantling a bonded body according to the second embodiment, in order to separate (dismantle) the second adherend from the first adherend, specifically, at least the first base layer of the adhesive tape is stretched, so that at least the first adhesive layer (preferably the first adhesive layer and the second adhesive layer) together with the first base layer is peeled off (pulled out) from between the first adherend and the second adherend. This allows the second adherend to be separated (dismantled) from the first adherend. At this time, since the foam layer is not easily stretched like the first base layer, the foam layer and the third adhesive layer may remain attached to the adherend and become residues. In this case, for example, the residues can be removed after the second adherend is separated (dismantled) from the first adherend.

[0368] In the second embodiment, in order to separate (dismantle) the second adherend from the first adherend, layers other than the first base layer of the adhesive tape, for example the foam layer, may also be stretched. However, when the first base layer is stretched, it is difficult for the foam layer to follow suit and stretch, so there is a risk that the foam layer will tear during stretching. In addition, since the adhesive tape has a second adhesive layer, the adhesive strength between the second adhesive layer and the foam layer is relatively lower than the adhesive strength between the first base material layer and the second adhesive layer, so when the first base material layer is stretched, the second adhesive layer also tends to peel off following the first base material layer. Furthermore, when the adhesive tape has a fourth adhesive layer, the adhesive strength between the second adhesive layer and the fourth adhesive layer is relatively lower than the adhesive strength between the first base material layer and the second adhesive layer and the adhesive strength between the fourth adhesive layer and the foam layer. Therefore, when the first base material layer is stretched, the second adhesive layer also peels off following the first base material layer, and the fourth adhesive layer tends to remain attached to the adherend together with the foam layer.

[0369] <<Method of dismantling the joined body according to the third embodiment>> A method for dismantling a bonded body according to a third embodiment includes the step of separating the second adherend from the first adherend by stretching at least the first base layer of the adhesive tape while leaving the second base layer of the adhesive tape on the surface of the second adherend. The adhesive tape used in the third embodiment includes a first adhesive layer, a first base layer, a second adhesive layer, a second base layer, a fourth adhesive layer, a foam layer, and a third adhesive layer, in that order. In the third embodiment, in order to separate (dismantle) the second adherend from the first adherend, specifically, at least the first base material layer of the adhesive tape is stretched while leaving the second base material layer on the surface of the second adherend, so that at least the first adhesive layer (preferably the first adhesive layer and the second adhesive layer) is peeled off (pulled out) from between the first adherend and the second adherend together with the first base material layer. In the second embodiment, a method for leaving the second base material layer on the surface of the second adherend includes not removing the second base material layer when stretching the first base material layer to remove it from between the first adherend and the second adherend, more specifically, not pulling the second base material layer together with the first base material layer, or not continuing to pull it. In the method for dismantling a bonded body according to the third embodiment, when at least the first adhesive layer is peeled off from between the first and second adherends, the second base layer, the fourth adhesive layer, the foam layer and the third adhesive layer remain attached to the adherends and become residues, and therefore, the residues are removed after the second adherend is separated (dismantled) from the first adherend.

[0370] In the third embodiment, when the first base layer is peeled off together with the first adhesive layer and the second adhesive layer, residue of the adhesive tape having the second base layer on its surface will be present between the first adherend and the second adherend. However, since the second base layer is non-adhesive, re-adhesion between the first adherend and the second adherend can be avoided, making dismantling easier. In the third embodiment, when the adhesive tape uses a substrate that is easily torn off, such as the second substrate layer, when stretching at least the first substrate layer of the adhesive tape, the second substrate layer, etc. (e.g., all layers of the adhesive tape) may be stretched together with the first substrate layer. In this case, the second substrate layer, etc. (e.g., the portion of the adhesive tape including the second substrate layer, the fourth substrate layer, the foam layer, and the third substrate layer) is torn off during the stretching, so that the first substrate layer can be peeled off together with the first substrate layer and the second substrate layer while leaving a residue including the second substrate layer, etc. on the surface of the second adherend.

[0371] Although the embodiments of the present invention have been described above, the pressure-sensitive adhesive tape of the present invention is not limited to the above examples and can be modified as appropriate. EXAMPLES

[0372] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.

[0373] The pressure-sensitive adhesive tapes obtained in the respective Examples and Comparative Examples were measured and evaluated according to the following methods.

[0374] (1) Measurement of the breaking strength and breaking elongation of the base layer Each base layer was punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and the base layer was pulled in the length direction at a tensile speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measurement atmosphere of 23°C and 50% RH, to measure the breaking strength and breaking elongation of the base layer. The results are shown in Table 1 below.

[0375] (2) Measurement of the thickness of the base layer, adhesive layer, and foam layer The thicknesses of the base layer, adhesive layer, and foam layer were measured at five random points using a TH-104 paper / film thickness gauge (manufactured by Tester Sangyo Co., Ltd.) The average values ​​of these measurements were used as the thicknesses of the base layer and adhesive layer.

[0376] (3) Measurement of 25% compressive strength The foam cut into 50 mm squares was stacked until the thickness was about 10 mm, and sandwiched between plates with a larger area than the foam. The foam was compressed to about 2.5 mm (25% of the original thickness) at a speed of 10 mm / min at 23°C, and then stopped. The strength after 20 seconds was measured, and this strength was taken as the 25% compression strength. The strength was also measured using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.).

[0377] (4) Measurement of tensile strength of foam layer The foam of the foam layer was cut into test pieces with a gauge length of 2 cm and a width of 1 cm, and the test pieces were measured using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) at 23°C and 50% RH at a tensile speed of 300 mm / min. The maximum strength among the measured values ​​was recorded as the tensile strength.

[0378] (5) Evaluation of stretch peelability Each adhesive tape was cut to a length of 60 mm and a width of 10 mm. With the length of 10 mm and the width of 10 mm protruding as a grip, a clean, smooth-surfaced aluminum plate (length 150 mm, width 50 mm, thickness 2 mm, alloy number A1050) was attached to one side (third adhesive layer side) of the adhesive tape under conditions of an atmosphere of 23°C and 50% RH. Next, a clean, smooth-surfaced acrylic plate (length 150 mm, width 50 mm, thickness 2 mm, Acrylite L, color tone: colorless, manufactured by Mitsubishi Rayon Co., Ltd.) was attached to the side (first adhesive layer side) of the adhesive tape opposite to the side to which the aluminum plate was attached, and the laminated structure of the aluminum plate, the adhesive tape, and the acrylic plate was pressed by rolling once back and forth with a roller while applying a load of 5 kg to the laminated structure, and then left to stand for 3 days under conditions of an atmosphere of 23°C and 50% RH to prepare a test specimen. Under conditions of an atmospheric temperature of 23°C and 50% RH, the gripping portion of the adhesive tape in the test piece (first adhesive layer, first base layer, second adhesive layer) was stretched horizontally relative to the application surface of the adhesive tape at a tensile speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.). The test was carried out 10 times using the above method, and the removability (stretch removability) was evaluated based on the following evaluation criteria. The results are shown in Tables 1 to 3 below. [Evaluation Criteria] ⊚: The number of times that the sheet could be pulled out from between the acrylic plate and the aluminum plate without at least the first base layer being torn was 9 or more out of 10. ◯: The number of times that the sheet could be pulled out from between the acrylic plate and the aluminum plate without at least the first base layer being torn was 5 to 9 out of 10. ×: The number of times that the sheet could be pulled out from between the acrylic plate and the aluminum plate without at least the first base layer being torn was 4 to 1 out of 10. ×: The number of times that the sheet could be pulled out from between the acrylic plate and the aluminum plate without at least the first base layer being torn was 0 out of 10. In addition, ◎ and ○ indicate that there is no problem with use.

[0379] (6) Evaluation method for conformity in the thickness direction The adhesive tapes obtained in the Examples and Comparative Examples were cut into a frame shape with an outer dimension of 50 mm × 40 mm and a width of 1 mm. The first adhesive layer of the cut adhesive tape was attached to a stainless steel plate 1 (thickness 2 mm, outer dimension 65 mm × 45 mm) with a hole with a diameter of 10 mm in the center. Next, the third adhesive layer of the above adhesive tape was attached to a stainless steel plate 2 (thickness 2 mm, outer dimensions 65 mm x 45 mm) at 23°C and subjected to a pressure of 50 N / cm 2 After applying a pressure of 1000 psi for 5 seconds, the specimen was left in an environment at 23° C. for 24 hours to obtain a bonded assembly. Next, a conformability evaluation sample was prepared to evaluate conformability in the thickness direction of the adhesive tape by using spacers with a thickness of 0.05 mm increments so that the distance between stainless steel plate 1 and stainless steel plate 2 of the bonded body obtained above was +0.00 mm, +0.05 mm, +0.10 mm, +0.15 mm, +0.20 mm, ..., +0.50 mm relative to the thickness of the adhesive tape. The conformability evaluation sample was left for 48 hours in an environment of 23°C and 50% RH, and then an air pressure of 15 kPa was applied for 5 seconds through a hole in the center of stainless steel plate 1 to evaluate the presence or absence of air leakage. ◎: Even when a gap of 1.30 times the thickness of the adhesive tape is provided No air leaks were detected. ○: Even when a gap of 1.25 times the thickness of the adhesive tape is provided No air leaks were detected. △: Even when a gap of 1.20 times the thickness of the adhesive tape is provided No air leaks were detected. ×: Air leakage was observed when a gap of 1.20 times the thickness of the adhesive tape was provided.

[0380] (7) Measurement of friction force The frictional force of the adhesive layer of the adhesive tape (23°C) was measured using a measuring device defined in JIS K7125. The sliding piece was a stainless steel plate (40 cm 2 A canvas was prepared by bonding the felt surface and the cotton canvas #9 facing each other with double-sided tape (DIC #8800CH). The cotton canvas #9 referred to here is No. 9 cotton canvas [(based on the old JIS L3102) with a twist of yarn (warp 10 / 2, weft 10 / 3), density (warp 44-48 threads / inch, weft 33-37 threads / inch), weight 510 g / m 2 )]. Next, the adhesive tape to be used for evaluation was cut to a size of 100 mm wide x 200 mm long, and fixed on a smooth and horizontal test table so that the adhesive layer surface of the adhesive tape to be measured was facing upward. The stress value was measured when the sliding piece slid over the adhesive layer surface of the adhesive tape to be measured. Note that the stress value obtained by this measurement method is in a state where the static friction force is continuously measured because the friction force against the adhesive layer surface is high. For this reason, a graph of the stress value and the moving distance of the sliding piece was created, and the stress value for a moving distance of 50 mm was extracted from the moving distance range where the stress value was relatively stable, and the arithmetic average of the peak values ​​of the extracted stress values ​​was taken as the friction force.

[0381] (8) Measurement of average particle size and number average primary particle size (Measurement of average particle size) The average particle size of the filler particles used in the pressure-sensitive adhesive composition was measured by using a measuring device (Microtrac) that uses a laser diffraction scattering method. (Measurement of number average primary particle size) The adhesive tape cooled under liquid nitrogen was cut at three random locations using a microtome, and the three pieces were used as samples. Then, each sample was photographed at 400 times magnification using a scanning electron microscope, and the solid particles were selected as fillers from the three photographs. Then, the cross-sectional area of ​​the solid bodies calculated by binarization (e.g., Otsu's binarization) using image analysis software was regarded as the area of ​​a circle, and the circle-equivalent diameter of each solid body was measured. Then, the total number of solid bodies in the three photographs and the corresponding circle-equivalent diameter were calculated, and the number-average primary average particle diameter of the filler particles was calculated from the following formula (A).

number

[0382] Next, the materials used in the examples and comparative examples are as follows. <Material for base material> ·Base material (1) (SIS) As the substrate material (1), a SIS resin (Zeon Corporation, Quintac 3620) was used. ·Base material (2) (SEEPS) A nitrogen-purged, dried pressure vessel was charged with 3,000 mL of cyclohexane as a solvent and 9.2 mL of 10.5% by mass sec-butyllithium (cyclohexane solution) as an initiator, and the temperature was raised to 60°C. Then, 100 mL of styrene was added and polymerization was carried out for 60 minutes. Then, 270 mL of isoprene and 350 mL of butadiene were added at the same temperature, and the mixture was reacted for 90 minutes. Then, 100 mL of styrene was added at the same temperature, and the mixture was polymerized for 60 minutes. The polymerization was then terminated with 0.52 mL of methanol, and a polymerization reaction liquid containing a block copolymer was obtained. To this reaction mixture, 29.3 g of palladium carbon (palladium loading: 5% by mass) was added as a hydrogenation catalyst, and the hydrogenation reaction was carried out for 10 hours at a hydrogen pressure of 2 MPa and 150° C. After cooling and releasing the pressure, the palladium carbon was removed by filtration, and the filtrate was concentrated and further dried in vacuum to obtain a substrate material (2). The obtained substrate material (2) had a styrene content of 30 mass %, a weight average molecular weight of 98,000, a molecular weight distribution of 1.03, and a hydrogenation rate of 98%.

[0383] · Substrate materials (3) (urethane) As the substrate material (3), an ester-based polyurethane sheet (Mobyron film MF50T, thickness 50 μm, manufactured by Nisshinbo Textile Inc.) was used.

[0384] ·Base material (4) (PET) As the substrate material (4), a PET film (manufactured by Toray Industries, Inc., Lumirror S10, thickness 12 μm) was used.

[0385] ·Base material (5) (PET) As the substrate material (5), a PET film (manufactured by Toray Industries, Inc., Lumirror S10, thickness 50 μm) was used.

[0386] <Filler particles> Filler particles (1) (silicone-based filler) Silicone composite particles (KMP-601, manufactured by Shin-Etsu Chemical Co., Ltd., average particle size 12 μm) were used as the filler particles (1).

[0387] Filler particles (2) (silicone-based filler) Silicone composite particles (KMP-602, manufactured by Shin-Etsu Chemical Co., Ltd., average particle size 30 μm) were used as the filler particles (2).

[0388] <Adhesive resin> Method for preparing adhesive resin (1) (acrylic) In a reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, 75.94 parts by mass of n-butyl acrylate, 5 parts by mass of 2-ethylhexyl acrylate, 15 parts by mass of cyclohexyl acrylate, 4 parts by mass of acrylic acid, 0.06 parts by mass of 4-hydroxybutyl acrylate, and 200 parts by mass of ethyl acetate were charged, and the mixture was heated to 65°C while blowing in nitrogen under stirring to obtain a mixture (1). Next, 4 parts by mass of a 2,2'-azobisisobutyronitrile solution (solid content 2.5% by mass) previously dissolved in ethyl acetate was added to the mixture (1), and the mixture was held at 65°C for 10 hours under stirring to obtain a mixture (2). Next, the mixture (2) was diluted with 98 parts by mass of ethyl acetate and filtered through a 200-mesh wire net to obtain an acrylic copolymer solution (1) having a weight average molecular weight of 1.6 million (polystyrene equivalent). Next, 100 parts by mass of the acrylic copolymer solution (1) was mixed and stirred with 5 parts by mass of a polymerized rosin ester-based tackifier resin (D-125, Arakawa Chemical Industries, Ltd.) and 15 parts by mass of a petroleum-based tackifier resin (FTR (registered trademark) 6125, manufactured by Mitsui Chemicals, Inc.), and then ethyl acetate was added to obtain an adhesive resin solution (1) containing an adhesive resin (1) with a solid content of 35% by mass.

[0389] Method for preparing adhesive resin (2) (acrylic) In a flask with an internal volume of 1000 ml, the inside of which had been replaced with argon, 500 ml of dry toluene and 80 ml of a solution of 0.75 g of bis(pentamethylcyclopentadienyl)samarium tetrahydrofuranate complex [(C5Me5)2SmMe(THF)] as a polymerization initiator were added to prepare a mixed solution. 12.0 ml of methyl methacrylate (MMA) was added to the mixed solution at 0°C and stirred at 0°C for 30 minutes. Then, 20 ml of the solution was sampled from the system (Sample 1). After the polymerization of MMA, the polymerization reaction system was cooled to -78°C, and 88.0 ml of n-butyl acrylate (nBA) was added as the second monomer and stirred at -78°C for 3 hours. Then, 20 ml of the solution was sampled from the system (Sample 2). After the polymerization of nBA, 12.0 ml of MMA was added to the polymerization system as the third monomer at -78°C and the solution was stirred. After the solution became homogeneous, it was heated to 0°C and stirred for another hour. The polymerization was terminated by adding 50 ml of methanol to the resulting reaction mixture and reacting at room temperature for 2 hours. The reaction solution after the polymerization was terminated was poured into a large amount of hexane to obtain a white precipitate. A part of the white precipitate was then sampled (sample 3).

[0390] NMR measurement, DSC measurement, and GPC (gel permeation chromatography) measurement were performed on each polymer in the above samples 1 to 3. Then, based on the measurement results, the number average molecular weight (Mn), PMMA / PnBA (polymethyl methacrylate block / polyn-butyl acrylate block) ratio, etc. were obtained, and it was confirmed that the above white precipitate was a triblock copolymer of polymethyl methacrylate (PMMA) block-polyn-butyl acrylate (PnBA) block-polymethyl methacrylate (PMMA) block (PMMA-b-PnBA-b-PMMA, hereinafter referred to as triblock copolymer (1)). It was also confirmed that the syndiotacticity of the PMMA block of the triblock copolymer (1) was 71%, the glass transition temperature of the PMMA block was 113.7°C, the glass transition temperature of the PnBA block was -46.8°C, the Mn of the entire copolymer was 95,936, the Mw / Mn (molecular weight distribution) of the entire copolymer was 1.09, and the proportions of the polymer blocks were PMMA (11% by weight)-PnBA (78% by weight)-PMMA (11% by weight). The white precipitate obtained above was diluted with ethyl acetate to obtain a pressure-sensitive adhesive resin solution (2) containing a solid content of 45 mass % of the pressure-sensitive adhesive resin (2).

[0391] <Adhesive composition> Adhesive composition (1) 30 parts by mass of filler particles (1) were added to 100 parts by mass of solid content of the adhesive resin solution (1) obtained above. Next, 1.3 parts by mass of a crosslinking agent (Burnoc D-40, manufactured by DIC Corporation; trimethylolpropane adduct of tolylene diisocyanate, isocyanate group content 7% by mass, non-volatile content 40% by mass) was added to the solution containing the filler particles (1) based on 100 parts by mass of the adhesive resin solution (1), and the mixture was stirred and mixed uniformly, and then ethyl acetate was added to obtain an adhesive composition (1) with a solid content of 40% by mass.

[0392] Adhesive composition (2) To 100 parts by mass of the solid content of the adhesive resin solution (2) obtained above, 30 parts by mass of filler particles (1) were added and stirred and mixed uniformly, and then ethyl acetate was added to obtain an adhesive composition (2) with a solid content of 45% by mass.

[0393] Adhesive composition (3) 30 parts by mass of filler particles (2) were added to 100 parts by mass of the solid content of the adhesive resin solution (1) obtained above. Next, 1.3 parts by mass of a crosslinking agent (Burnoc D-40, manufactured by DIC Corporation; trimethylolpropane adduct of tolylene diisocyanate, isocyanate group content 7% by mass, non-volatile content 40% by mass) was added to the solution containing the filler particles (2) based on 100 parts by mass of the adhesive resin solution (1), and the mixture was stirred and mixed uniformly, followed by adding ethyl acetate to obtain an adhesive composition (3) with a solid content of 40% by mass.

[0394] Adhesive composition (4) A pressure-sensitive adhesive composition (4) having a solid content of 40% by mass was obtained by adding 1.3 parts by mass of a crosslinking agent (Burnoc D-40, manufactured by DIC Corporation; trimethylolpropane adduct of tolylene diisocyanate, isocyanate group content 7% by mass, non-volatile content 40% by mass) and ethyl acetate to 100 parts by mass of the solid content of the pressure-sensitive adhesive resin solution (1) obtained above.

[0395] <Foam> Foam (1) (PE foam) A black polyolefin foam (thickness: 150 μm, expansion ratio: 3 times, 25% compressive strength: 70 kPa, tensile strength: 10 MPa) was prepared.

[0396] Foam (2) (PE foam) A black polyolefin foam (thickness: 150 μm, expansion ratio: 2.2 times, 25% compressive strength: 150 kPa, tensile strength: 14 MPa) was prepared.

[0397] Foam (3) (PE foam) A black polyolefin foam (thickness: 150 μm, expansion ratio: 5 times, 25% compressive strength: 190 kPa, tensile strength: 5 MPa) was prepared.

[0398] Foam (4) (PE foam) A black polyolefin foam (thickness: 100 μm, expansion ratio: 1.9, 25% compressive strength: 50 kPa, tensile strength: 16 MPa) was prepared.

[0399] Next, examples and comparative examples will be described. Example 1 The adhesive composition (1) was applied to a release liner (Film Bina 75E-0010GT, manufactured by Fujimori Kogyo Co., Ltd., the same applies below) using an applicator so that the thickness after drying was 50 μm, and the adhesive composition (1) was dried at 80° C. for 3 minutes to prepare adhesive layers for the first adhesive layer and the second adhesive layer. Next, toluene was added to the substrate material (1) and stirred to make it uniform, and the mixture was applied onto a release liner using an applicator so that the thickness after drying would be 50 μm, and then dried at 60° C. for 5 minutes to produce a first substrate layer. After peeling off the release liner from the first base layer, the adhesive layer from which the release liner had been peeled off was bonded to both sides of the first base layer, the surface of which had been corona treated to give a wetting index of 60 mN / m, to form a first adhesive layer and a second adhesive layer. The layers were then laminated using a roll with a linear pressure of 5 kg / cm and aged at 40°C for 48 hours. Next, the pressure-sensitive adhesive composition (4) was applied onto a release liner so as to give a dry thickness of 50 μm, and dried at 80° C. for 3 minutes to form pressure-sensitive adhesive layers for the third and fourth adhesive layers. Next, foam (1) was prepared as a foam layer, and one adhesive layer for the third adhesive layer and one adhesive layer for the fourth adhesive layer were bonded to both sides of the foam (1) which had been corona treated to give a wetting index of 60 mN / m. The resulting laminate was then laminated with a roll at a linear pressure of 5 kg / cm and aged at 40°C for 48 hours. Next, the substrate material (4) was prepared as a second substrate layer, and the second adhesive layer that had been aged as described above was bonded to one side of the second substrate layer. The fourth adhesive layer that had been aged as described above was then bonded to the other side of the second substrate layer, and the resulting mixture was laminated with a roll at a linear pressure of 5 kg / cm to produce an adhesive tape (1)....

Claims

1. A first adhesive layer, a first base layer, a foam layer, and a third adhesive layer are provided in this order, The first base layer has a breaking strength of 1.0 to 100.0 MPa and a breaking elongation of 400 to 1500%, A pressure-sensitive adhesive tape, wherein the foam of the foam layer has a 25% compressive strength of 40 to 160 kPa and a tensile strength of 3.0 to 15.0 MPa.

2. The first adhesive layer adjacent to the first base layer is formed from an adhesive composition containing filler particles having an average particle size of 10 to 40 μm and an adhesive resin; The pressure-sensitive adhesive tape according to claim 1, wherein the content of the filler particles in the pressure-sensitive adhesive layer containing the filler particles is 3 to 50 parts by mass per 100 parts by mass of the pressure-sensitive adhesive resin.

3. An adhesive tape as described in claim 1 or 2, wherein the first base layer has a rubber hardness of 20 to 90A.

4. An adhesive tape described in any of claims 1 to 3, wherein the first base layer has a 100% modulus of 1 to 5 MPa.

5. The first substrate material of the first substrate layer comprises a styrene-based resin, The pressure-sensitive adhesive tape according to any one of claims 1 to 4, wherein the styrene-based resin is a hydrogenated copolymer obtained by hydrogenating a block copolymer composed of at least a polymer block (A) mainly composed of a styrene-based compound unit and a polymer block (B) mainly composed of an isoprene unit, a butadiene unit, or an isoprene and butadiene unit.

6. An adhesive tape described in any of claims 3 to 5, comprising a second adhesive layer between the first substrate layer and the foam layer.

7. The second adhesive layer adjacent to the first base layer is formed from an adhesive composition containing filler particles having an average particle size of 10 to 40 μm and an adhesive resin; The pressure-sensitive adhesive tape according to claim 6, wherein the content of the filler particles in the pressure-sensitive adhesive layer containing the filler particles is 3 to 50 parts by mass per 100 parts by mass of the pressure-sensitive adhesive resin.

8. An adhesive tape as described in either claim 6 or 7, comprising a fourth adhesive layer between the second adhesive layer and the foam layer.

9. The adhesive tape described in claim 8, comprising a second base layer between the second adhesive layer and the fourth adhesive layer.

10. A joint comprising an adhesive tape as described in any one of claims 1 to 9, a first adherend adhered onto the surface of the first adhesive layer of the adhesive tape, and a second adherend adhered onto the surface of the third adhesive layer of the adhesive tape.

11. A method for dismantling the joint body according to claim 10, comprising the steps of: A method for dismantling a bonded body, comprising a step of stretching at least the first base material layer of the pressure-sensitive adhesive tape to separate the second adherend from the first adherend.

12. A method for dismantling a joint comprising the adhesive tape of claim 9, a first adherend adhered onto a surface of the first adhesive layer of the adhesive tape, and a second adherend adhered onto a surface of the third adhesive layer of the adhesive tape, comprising: a step of separating the second adherend from the first adherend by stretching at least the first base material layer of the adhesive tape while leaving the second base material layer of the adhesive tape on a surface of the second adherend.